Alternative splicing is coordinated through interconnected response pathways to direct major features of fungal cell physiology - João Neves-da-Rocha; Marcos E.R. Lopes; Mayara I.G. Azevedo; Monise F. Petrucelli; Maria J. Santos-Saboya; Antonio Rossi; Nilce M. Martinez-Rossi (Fungal Biology Reviews, 2026)

Environmental drivers of pico- and nanophytoplankton distribution in the coastal zone of Ubatuba, Brazil - Silvana B. Penninck; Luciana R. Frazão; Rubens M. Lopes (Estuarine, Coastal and Shelf Science, 2026)

Bridging soil mapping units and digital soil mapping through probability-driven machine learning: an uncertainty-aware framework for soil class prediction in Antarctica - Rafael G. Siqueira; Cássio M. Moquedace; Márcio R. Francelino; Carlos Ernesto G.R. Schaefer; Roberto F.M. Michel; Daniela Schmitz; Flávia R. Ferrari; Caroline Delpupo; Eduardo O. Senra; Heitor P. Palma; Daniel N. Krum; Fábio S. de Oliveira; et al. (CATENA, 2026)

Terrestrial environmental change across the Permian-Triassic boundary in the Karoo Zambezi Basin, Mozambique: Integrating palynological, sedimentological and carbon isotope evidence - P. Fernandes; Z. Pereira; J.E. Spangenberg; M. Mendes; G. Lopes; R.C.G.S. Jorge; L. Albardeiro; E. Font; T. Adatte; T. Vennemann; J. Marques (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Analysis of a large-hail producing supercell and its merger with a nascent supercell on 6 october 2015 - Maurício I. Oliveira; Vitor Goede; Eliton L. Figueiredo; Murilo M. Lopes; Rafael J. C. Santana; Ernani L. Nascimento; Ming Xue; Lucas I. G. Oliveira; Franciano S. Puhales; Vanessa Ferreira (Meteorology and Atmospheric Physics, 2026)
This study documents the lifecycle and large-scale environment of a large-hail producing supercell that occurred in southern Brazil (SB) on 6 October 2015. The supercell underwent a merger with a nascent supercell near a Doppler weather radar and rapidly intensified shortly after the interaction. The original (premerger) supercell developed in a high-shear, high-instability pre-cyclogenesis environment and remained isolated until the merger due to the presence of a relatively rare elevated mixed layer that helped suppress widespread convection and provided steep lapse rates for robust updrafts. A small cell developed ~ 30 km to the north of the original supercell and merged in between its inflow and forward-flank regions, resulting in a new (postmerger) supercell that inherited the main features of the intensifying nascent cell. Radar-derived quantities related to supercell intensity reveal that the updraft and mesocyclone intensified significantly within 30 min of the merger, resulting in a large episode of hailfall with 6 + cm hail reported at the surface. After reaching peak intensity, the postmerger supercell and its attendant low-level mesocyclone rapidly decayed, likely as a result of a hailfall-induced outflow surge and large convective inhibition. This case illustrates the importance of mergers between mature and nascent supercells to the short-term forecasting of severe weather, a topic that received little attention in studies and prediction of storms in SB.

The role of metals in cancer and the use of metal chelators as a potential treatment strategy - M. Fernanda C. Leal; Daniela A. Rocha; Inês Lopes Cardoso (BioMetals, 2026)
Biometals such as iron, copper, zinc, manganese, cobalt, and selenium play crucial roles in cellular respiration, immunity, apoptosis, and signaling. However, their excessive accumulation can induce chronic inflammation, oxidative stress, and trigger carcinogenesis. Iron addiction stands out for its importance in tumor cell replication and survival. Cancer remains one of the leading causes of mortality worldwide. Given the limitations of conventional therapies, new approaches have been explored, namely the use of metal chelators, with the aim of selectively modulating metal homeostasis in tumor cells. Metal chelation represents a promising therapeutic approach in the treatment of cancer. Metal chelators such as DFO and DFX demonstrate antineoplastic activity, although limited by low selectivity and systemic toxicity. Thiosemicarbazones, particularly Triapine, have demonstrated anticancer and antimetastatic activity in preclinical models, with clinical trials currently underway to treat tumors. SK4 appears to be a promising alternative, with greater selectivity for tumor cells, inducing apoptosis, demonstrating superior efficacy and lower toxicity. Its efficacy in preclinical models and selective profile support the need for clinical validation, potentially integrating more targeted, safe, and effective oncological therapy. Thus, the aim of this manuscript is to analyze the role of metals in cancer and evaluate the therapeutic potential of metal chelators.

Predicting Craniospinal Surgery in Pediatric Achondroplasia: Benchmarking Statistical Inference and Explainable AI Under Rare-Disease Constraints - Seifollah Gholampour; Jesse Huang; Dylan Keusch; Carolina Lopes; Aseel Masarwy; James Obayashi; Marcella Ruppert-Gomez; Christina M. Sayama; Lissa C. Baird; Moise Danielpour; David F. Bauer (Annals of Biomedical Engineering, 2026)

Cryptobenthic reef fishes may not be safe from invasive lionfish ( Pterois spp. Oken, 1817) - Liana F. Mendes; Ariston P. Santos; Thaisa A. Souza; Lorena S. Agostinho; Ana B. A. Bennemann; Jorge Cortés; Maria S. Toro; Juliana S. S. Luz; Clara B. P. E. Silva; Carlos. E. R. D. Alencar; Priscila F. M. Lopes (Journal of Fish Biology, 2026)
Lionfish ( Pterois spp.) are hypothesized to negatively influence cryptobenthic reef fish assemblages through predation. We evaluated these potential effects on Caribbean reefs in Costa Rica and tropical reefs in Brazil. Brazil provided a reference condition for cryptobenthic assemblages prior to lionfish invasion, while the Costa Rica sites enabled comparisons between reefs inside marine protected areas (MPAs), where lionfish removal did not occur for several years, and adjacent fished reefs where removals occurred. Visual censuses (30 m × 2 m transects, 0.5–4 m depth) were complemented by simplified assessments of reef structure and benthic cover. Cryptobenthic fish abundance was consistently higher in Brazil than in Costa Rica. Within Costa Rica, abundance was significantly lower inside MPAs, where higher lionfish densities were recorded, compared to adjacent fished reefs. This pattern indicates differences in cryptobenthic fish abundance across sites with contrasting lionfish presence. Our findings reinforce concerns that MPAs may inadvertently function as refuges for invasive species, highlighting the importance of adaptive management strategies, including targeted removals and monitoring, to mitigate ecological impacts and protect reef biodiversity.

Disentangling natural and anthropogenic sedimentation: current and past pollution impact on Sepetiba Bay (southeastern Brazil) - Fabrício Leandro Damasceno; Maria Virgínia Alves Martins; Denise Lara Terroso; Miguel Angelo Mane; Caroline Adolphsson do Nascimento; Egberto Pereira; Rubens Cesar Lopes Figueira; João Graciano Mendonça Filho; Thaise M. Senez-Mello; Michael Martínez-Colón; Miguel Tupinamba; Renata Cardia Rebouças; et al. (Estuarine, Coastal and Shelf Science, 2026)

Sequential recovery of fish silage lipids and proteins for biodiesel production and marine microalgae cultivation - Regina M. González-Balderas; Isabel Martínez-Apodaca; Julio C. Sacramento-Rivero; Mariela C. Lope Navarrete; Ruby Valdez-Ojeda (Algal Research, 2026)

In vitro anthelmintic effect of anacardic acid and ivermectin, individually and in combination, against Haemonchus contortus - Gracielle A. Frota; Andreza P. Braga; Wildson M.B. Silva; Francisco F.S. Lopes; Wesley L.C. Ribeiro; Letícia O. Rocha; Luiz S. Vieira; Marcel Texeira; Lorena M.B. Oliveira; Jomar P. Monteiro; Selene M. Morais (Veterinary Parasitology, 2026)

The feasibility of using machine learning to estimate rock permeability from nuclear magnetic resonance T$$_{2}$$ and the role of the surface relaxivity - Alexsander M. Cunha; Rafael S. Vianna; Pedro M. Vianna; Andre Souza; Pedro C. F. Lopes; Andre M. B. Pereira; Ricardo Leiderman (Computational Geosciences, 2026)
Predicting permeability from Nuclear Magnetic Resonance (NMR) data is a fundamental yet challenging task in reservoir characterization, primarily due to the uncertainty associated with surface relaxivity ( $$ρ $$ ρ ) parameters. In this work, we investigate the feasibility of using Machine Learning (ML) to estimate permeability from $$T_2$$ T 2 distributions and quantify how $$ρ $$ ρ uncertainty affects predictive accuracy. To address this, we generated a dataset of 15,000 synthetic 3D porous media representing granular sedimentary rock samples. We employed efficient in-house implementations of a Random Walk algorithm (governed by Bloch-Torrey physics) to simulate magnetization decay and obtain $$T_2$$ T 2 distributions, alongside a Finite Element Method (FEM) solver for the Stokes equations to compute absolute permeability, assuming 100% water saturation. The study comprises three computational experiments designed to isolate the impact of $$ρ $$ ρ . In the first experiment, we simulated $$T_2$$ T 2 distributions by assigning a constant $$ρ $$ ρ value for all synthetic porous media. In the second experiment, we applied a different $$ρ $$ ρ value to each synthetic porous medium to emulate real-world uncertainty, representing the scenario where $$ρ $$ ρ is unknown. The third experiment extends the second by converting the $$T_2$$ T 2 distributions into surface-to-volume ratio distributions using the specific $$ρ $$ ρ value assigned in the second experiment to each medium. We systematically compared the Multilayer Perceptron (MLP) performance against the industry-standard Schlumberger-Doll-Research (SDR) model. Overall, the MLP yielded strong predictive performance. The second experiment presented a performance drop for both models, confirming the impact of $$ρ $$ ρ uncertainty. The main contribution of this work is the systematic quantification of the sensitivity of predictive permeability models to $$ρ $$ ρ , establishing a controlled benchmark that addresses and reduces existing uncertainties. Additionally, these findings demonstrate that the MLP provides a robust and competitive alternative for permeability estimation in scenarios where $$ρ $$ ρ is unknown.

An extraordinary new genus and species of horseshoe crab beetle (Ptiliidae: Cephaloplectini) from the Brazilian Atlantic biome - Júlio C. M. Chaul; Artur Orsetti; Cristiano Lopes-Andrade (Biologia, 2026)
Clepsammia gaia Chaul & Lopes-Andrade gen. et sp. n. is described herein, representing the first new taxon of Cephaloplectini (Ptiliidae) proposed in more than 80 years. The species is blind and flightless, as are all other known members of the tribe, but it exhibits a highly distinctive morphology, characterized by a conspicuous mid-body constriction bearing spongiform setae. The description is based on five specimens collected from a single locality in the Brazilian Atlantic Forest, found 30–40 cm deep below the soil surface. An updated identification key to the genera of Cephaloplectini is provided. We also compile an extensive list of putative or confirmed ant hosts of Cephaloplectini species, which indicates a broad host spectrum, spanning multiple ant subfamilies and genera across the tribe’s geographic range. Finally, we discuss possible explanations for the morphological modifications observed in C. gaia relative to other members of the tribe.

Blue carbon inventories of Spain and Portugal for their inclusion in national climate mitigation strategies - Nerea Piñeiro-Juncal; Oscar Serrano; Carmen B. de los Santos; Nuria Marbà; Elena Díaz-Almela; Fernando Tuya; Inés Mazarrasa; Joxe Mikel Garmendia; Xosé Lois Otero; Karina Inostroza; Jordi F. Pagès; Gonzalo Mendez-Martínez; et al. (Marine Pollution Bulletin, 2026)

The ecology and evolution of cues and signals in animal interspecies cooperation - K. Dunkley; M. Cantor; A.I. Afan; D.S. Ahlibi; S.J. Allen; J. Amphaeris; S. Atkins; M.C. Attwood; K. Bankhead; C.J. Blair; J.L. Bronstein; Y.R.R. Camargo; et al. (Animal Behaviour, 2026)

Synthesis, cytotoxicity and in vitro and in silico anthelmintic activity of eugenol and derivatives against Haemonchus contortus - Raphael F. Oliveira; Andreza P. Braga; Matheus L.F. Barbosa; Karin V.M.M. Ferreira; Sara S.S. Cardoso; Francisco F.S. Lopes; Victor B. Fernandes; Selene M. Morais; Bruno C. Cavalcanti; Wesley L.C. Ribeiro; Letícia O. Rocha; Francisco J.M. Pinto; et al. (Veterinary Parasitology, 2026)

An Overview of the “Vento Norte” Experiment (VNorEx): Observations of Downslope Windstorms over Modest Terrain in Southern Brazil - Michel Stefanello; Murilo M. Lopes; Eberton C. De Souza; Mateus S. Rebelo; Daniel C. Santos; Tamíres Zimmer; Cinara E. Da Rosa; Rafael Santana; João A. V. Da Silva; Hector V. B. Da Rosa; Richard Lobato; Beatriz F. Mota; et al. (Advances in Atmospheric Sciences, 2026)

Testing the linkages between participatory monitoring, perception and compliance as a pathway to conserve threatened species - Antoine O. H. C. Leduc; Nigel E. Hussey; Priscila F. M. Lopes; José Amorim Reis-Filho (Biodiversity and Conservation, 2026)

Underway Shadowgraphic Imaging for Plankton Detection and Classification - Rubens M. Lopes; Leandro T. De-La-Cruz; Luis F. Baldasso; Josiane Lima; Stelamari Y. Ito; Gelaysi Moreno; Paulo S. Polito (Journal of Marine Science and Engineering, 2026)
Technological advances in hardware and software have enabled the development of novel in situ plankton imaging systems to investigate the spatial and temporal distribution of plankton communities. State-of-the-art machine learning approaches have been applied for automated image classification, effectively handling the complex and highly variable morphology of plankton while maintaining high accuracy. Despite these advances, few instruments can acquire zooplankton images autonomously in a continuous underway mode, which is essential for large-scale oceanographic surveys conducted aboard research vessels or ships of opportunity. Here, we present SiMFlux, an underway shadowgraphic imaging system developed at the University of São Paulo, and report results from the Orient Expedition. Observations were conducted aboard an 80-foot sailing vessel navigating across the Indian and Atlantic Oceans. A total of 193 videos were analyzed from daily route segments, yielding over 1.2 million regions of interest (ROIs) containing organisms and detrital particles. Particles were automatically classified and subsequently validated by plankton experts.

Assessment of PAH-associated health risk and food safety in high-value fish species following one of the largest and most extensive oil spills on the Atlantic Coast of South America (Coast of Ceará State, Brazil) - Antônia D.F. Lima; Beatriz D. Lopes; Lígia M.B.M. Santana; Mario M. Martins; Arlene B.S. Nossol; Luiz R. Goulart; Rivelino M. Cavalcante (Marine Environmental Research, 2026)

On how to make aquaponics more circular - Ze Zhu; Sara M Pinho; Oliver Körner; Giovanni M Turchini; Ivã Guidini Lopes; Paul B Brown; Zhangying Ye; Jian Zhao; Guozhi Luo; Hendrik Monsees; Karel J Keesman; Amit Gross (Bioresource Technology, 2026)

Does visiting an urban park in a large city influence people’s perception of common birds? - Gabriely M. Duarte; Daniela Biondi; Iran J.C. Lopes; Eduardo R. Alexandrino (Urban Ecosystems, 2026)
Many urban parks in large cities are created to promote human recreation and well-being by offering nature-like environments. Over time, urban-tolerant birds establish populations in these spaces. Although strengthening citizens’ connections with urban birds may enhance park-related well-being, it remains a central question whether visit frequency among the general public (i.e., non-birders) increases their perception and interest of local common species. Using an urban park in a large Brazilian city as a case study (Barigui Park, Curitiba), we selected seven very common local species to create a picture-based interview, which we administered to 242 visitors. We asked whether they had seen or heard these species and whether they could correctly name them. Most respondents perceived between two and four species (3.4 ± 1.5 species). Rare visitors (fewer than 12 visits per year, with no regular frequency) perceived significantly fewer species than frequent visitors, however, visiting more than monthly did not result in significant differences. Importantly, visit frequency showed no association with the ability to correctly name species, suggesting that park visitation may not be the only factor to foster interest in local common birds. The lack of consistent perception also suggests a gap in public awareness that may not be overcome by passive exposure alone. Therefore, we advocate that park management should incorporate educational actions—such as providing informational materials about birds and offering periodic birdwatching tours—to prevent citizens’ disconnection from this component of urban biodiversity.

Green area size rather than urbanization ecological index modulates the specialization of flower-visitor networks of Leguminosae trees in a tropical metropolis in Brazil - Thaís Caroline M. de Andrade; Jéssica Luiza S. e Silva; Luanda Pinheiro; Talita Câmara; Ariadna Valentina Lopes (Urban Ecosystems, 2026)
Urbanization and the size of green areas can alter numerous environmental and biological factors, including the ecological interactions between plants and animals in urban areas. Urban green areas contribute positively to the maintenance of biodiversity, provide resources for pollinators, and bring numerous benefits to the population in terms of ecosystem services. This study aimed to evaluate the effect of urbanization and the size of green areas on the interaction networks between Leguminosae trees pollinated by bees and their floral visitors. The study was carried out in eight urban green spaces in Recife, a Brazilian metropolis, in northeastern Brazil, with 10 species of native and exotic Leguminosae trees. In general, (1) Trigona spinipes and Xylocopa frontalis showed greater interaction with the Leguminosae; (2) increases in urbanization reduces the number of flower/inflorescence, the number of total visits and the generality, despite increasing interaction evenness between the Leguminosae pollinated by bees and their floral visitors; (3) increases in the size of urban green areas favours the interaction evenness of networks, the selectivity of occasional pollinators and harbour more specialized plant species; (4) simultaneously, reductions in urbanization and increases in urban green area size are associated with increased specialization of Leguminosae species. Our study highlights that urban green areas in tropical cities have enormous potential to sustain plant communities and floral visitors/pollinators, especially native bees. To manage urban biodiversity in the long term, cooperation between policymakers, conservation organizations, scientists and the population is essential to understand how species interact in complex and diverse urban landscapes and their importance for human well-being.

Comparative genomic analysis of satellite DNA families in the leaf-cutting ant Acromyrmex octospinosus and its social parasite Acromyrmex insinuator: evolutionary perspectives - G. A. Teixeira; J. A. Pereira; S. P. Cerqueira-Júnior; D. M. Lopes (Insectes Sociaux, 2026)

Predictive validation of the repeated low-dose reserpine rodent model of parkinsonism - Vinicius Bioni; Alvaro C. Lima; Debora M. G. Cunha; Narriman Gonçalves; Leonardo B. Lopes-Silva; João P. Kurita; Manuela B. L. Soares; Marcela Becegato; Aline C. Ramos; Anderson H. F. F. Leão; Regina H. Silva (Experimental Brain Research, 2026)
L-DOPA (LD) is the gold-standard treatment of motor symptoms in Parkinson’s disease (PD), conventionally used to prove the predictive value of PD animal models. This study aimed to investigate the predictive validity of an adaptation of the conventional reserpine model of PD: the repeated low-dose reserpine administration in rodents, which promotes progressive motor impairment in catalepsy, vacuous chewing behavior tests, and neurochemical deficits. Specifically, we investigated the effects of acute and chronic treatment with LD on motor alterations induced in mice by this modified protocol. Swiss mice were treated with 20 reserpine injections (0.1 mg/kg, s.c., every other day). Acute LD (25, 50, 100, and 200 mg/kg) administration was performed at the end of reserpine protocol to assess immediate motor recovery. Additionally, concomitant chronic LD (50 and 100 mg/kg) treatment was conducted to investigate potential attenuation of motor impairment and dopamine depletion quantified by HPLC. Repeated reserpine protocol induced motor deficits in catalepsy and vacuous chewing evaluations and striatal dopamine depletion. Acute LD administration significantly improved catalepsy in higher doses, while chronic LD treatment attenuated motor impairments and reduced dopamine depletion in the striatum. These findings support the predictive validity of the reserpine rodent model for studying parkinsonism. Together with the ability to promote chronic and progressive parkinsonian alterations, the reversion of these deficits by LD reinforces the potential of the repeated low-dose reserpine protocol for studies of potential therapies and the pathophysiology underlying neurodegenerative processes in PD.

Reassessing and Updating Regulatory Standards on the Declaration of Storage Conditions in the Product Information of Medicinal Products: An Evidence-Based Proposal under EMA Guidance - Helena Pericão; Henrique Cavaco; Miguel Dias; Luís Sarmento; Mário Magalhães; Bernardo Filipe; Herivelto Vieira; João Rita; Pedro Gonçalves; Matilde Vaz; Beatriz Coimbra; Beatriz Monteiro; et al. (Pharmaceutical Research, 2026)
Purpose The European Medicines Agency (EMA) guideline Declaration of Storage Conditions in the Product Information of Medicinal Products (CPMP/QWP/609/96/Rev.2) was last revised in 2007. Since then, advances in stability science, increased climatic variability, and evolving regulatory expectations have highlighted limitations in the framework, particularly the use of vague descriptors such as “room temperature” or “no special storage conditions.” This work reassesses the scientific and regulatory basis for storage statements, integrating current understanding of mean kinetic temperature (MKT), climate-related risks, and developments in ICH and WHO guidance, and proposes a harmonized revision (Rev.3). Methods A structured analysis of regulatory and scientific principles was conducted, incorporating MKT, climate-related risks, and developments in ICH and WHO guidance. These elements informed a revised framework and model storage statements, including a decision table linking stability outcomes to label statements. Results The proposed update introduces explicit temperature-based statements, strengthens the linkage between stability data and label wording, clarifies requirements for moisture- and light-sensitive products, expands guidance for sterile and reconstituted preparations, and provides contingency instructions for temperature excursions. A decision table mapping stability outcomes to label statements is included to support regulatory implementation. Conclusion This revision provides an updated synthesis of EMA, ICH, and WHO requirements, translating regulatory principles into clear storage statements and contingency guidance. It offers a more precise framework reducing ambiguity, supports justification of storage conditions through stability data and MKT-informed risk assessment, aiming to improve understanding among patients and healthcare professionals, strengthening real-world product quality and contributing to future EMA guideline development. Highlights Identifies scientific and regulatory limitations in current “no special storage conditions” terminology; Links ICH stability guidelines and climatic variability to precise storage statements; Proposes harmonised core label phrases for room temperature, fridge, and freezer; Introduces contingency labelling for climate-related and cold-chain excursions.

Corporations and financial institutions driving coastal conflicts involving Indigenous Peoples - Sebastian Villasante; Julia Tovar Verba; Veronica Relano; Sílvia Gómez; José Bakit; Nathan J. Bennett; Anthony Charles; Rafael Calderón-Contreras; Andrés M. Cisneros-Montemayor; Bernardo M. Flores; Lucas A. Garibaldi; Maria Grazia Pennino; et al. (Ambio, 2026)
Socio-environmental conflicts associated with large-scale economic projects in Indigenous territories are well documented, but conflicts in coastal areas remain largely unexplored, despite the crucial differences between inland and coastal ecosystems. While the empirical literature about socio-environmental conflicts in Indigenous territories in coastal areas is growing, the role of financial institutions and corporations in these conflicts is often overlooked. This study addresses this gap by examining the financial institutions and corporations associated with more than 400 reported socio-environmental conflicts affecting Indigenous Peoples in coastal areas worldwide. Our results show that most financial institutions supporting projects linked to conflicts are based in West Europe and North America, with North American financial institutions linked to multiple projects. The energy sector accounts for the highest number of socio-environmental conflicts, particularly those involving corporations operating across continents. Many European and North American corporations operate mostly in Africa, but also globally. Corporations with overseas operations are associated with a higher intensity of conflicts. These findings highlight the need to scrutinize financial investments and corporate practices driving socio-environmental conflicts in coastal Indigenous territories, where human rights are often at risk. The lack of due diligence and accountability in applying environmental and social safeguards weakens protections for both ecosystems and Indigenous communities. Strengthening the enforcement of national and international laws on environmental sustainability, human rights and Indigenous rights is therefore essential for coastal development projects.

Radiological risk assessment of natural radionuclides in the whitemouth croaker (Micropogonias furnieri Desmarest, 1823) in Brazilian tropical seas - Wagner Pereira; Alphonse Kelecom; José M. Lopes; Cleber B. Espindola; Alessander S. Carmo; Ademir X. Silva (Marine Pollution Bulletin, 2026)

Titan’s refractory core evolution: Implications for organics in its subsurface ocean - Kelly E. Miller; Mohit Melwani Daswani; Christophe Sotin; Charles S. Cockell; Catherine Neish; Michael J. Malaska; Kendra K. Farnsworth; Conor A. Nixon; Krista M. Soderlund; Peter M. Higgins; Antonin Affholder; Rosaly M.C. Lopes (Icarus, 2026)

Corrigendum to “Production of sustainable aviation fuel precursors using the oleaginous yeast Rhodotorula toruloides PYCC 5615 cultivated on eucalyptus bark hydrolysate” [Biomass Bioenergy 197 (2025) 107790] - Teresa Lopes da Silva; Francisca Dutra; Susana Marques; Miguel Gomes; Paula Costa; Filipe Paradela; Frederico Castelo Ferreira; Nuno Torres Faria; Paula Mugica; Helena M. Pinheiro; Isabel Sá-Correia; Francisco Gírio (Biomass and Bioenergy, 2026)

The impact of reduced precipitation on methane emissions in the Amazon and its role in the global methane balance - Raiane A.L. Neves; Luciana V. Gatti; Camilla L. Cunha; Caio S.C. Correia; Francine M. Silva; Guilherme B.M. Machado; Christiane S. Morais; Filipe Loyola Lopes; Lucas Gatti Domingues; Alber H. Sanches; Egidio Arai; Marcio Malacarne; et al. (Atmospheric Environment, 2026)

Intrinsic microRNA regulatory programs define lineage-specific differentiation in human mesenchymal stem cells of different origin – dental pulp- and fat tissue-derived - Carla Cristina G. Pinheiro; Camila M. Lopes-Ramos; Taro Inagaki; Paula Fontes Asprino; José Ricardo M. Ferreira; Ygor Gonçalves Félix de Mattos; Helena Coutinho Geiger Campos; Jamil Award Shibli; Raphael B. Parmigiani; Reza Jarrahy; Akishige Hokugo; Alessandra V. S. Faria; et al. (Stem Cell Reviews and Reports, 2026)
Cell fate determination and terminal differentiation are shaped by intrinsic molecular programs that coordinate lineage-specific gene expression. In mesenchymal stem cells (MSCs), variability in osteogenic efficiency among distinct tissue sources remains poorly understood and cannot be fully explained by differentiation conditions alone. Increasing evidence indicates that post-transcriptional regulatory mechanisms, particularly those mediated by microRNAs (miRNAs), are closely associated with differentiation outcomes. Here, we investigated whether intrinsic miRNA expression landscapes are associated with lineage-associated differences in late-stage mineralization, in the context of potential donor-related variability of human MSCs. Dental pulp stem cells (DPSCs) and processed lipoaspirate (PLA)-derived MSCs were cultured under identical osteogenic induction conditions and analyzed longitudinally throughout differentiation. Both cell populations fulfilled established mesenchymal phenotypic criteria and successfully initiated osteogenic commitment. However, DPSCs exhibited significantly enhanced extracellular matrix mineralization at mid-to-late stages of differentiation, suggesting divergence at later stages of extracellular matrix mineralization rather than at early lineage commitment. Temporal small RNA sequencing performed at days 0, 7, 14, and 21 revealed progressive remodeling of miRNA expression in both MSC sources. Direct comparison at the mature osteoblast stage identified a discrete set of ten miRNAs differentially expressed between DPSCs and PLA-derived cells. DPSCs displayed reduced expression of several miRNAs previously associated with inhibitory roles in osteogenic pathways. Network-based analyses indicated convergence of these miRNAs on gene programs involved in skeletal development and extracellular matrix organization. Targeted validation confirmed decreased expression of miR-10a-5p and miR-196a-5p, accompanied by increased expression of osteogenesis-associated genes, including BMP1 and MMP16, in DPSCs. Collectively, these findings show that lineage-specific miRNA expression patterns are associated with distinct osteogenic maturation trajectories in human MSCs. This work identifies an intrinsic post-transcriptional signature through which cellular origin may influence terminal differentiation outcomes and suggests that such miRNA profiles may serve as informative molecular biomarkers in the future for the selection and characterization of mesenchymal stem cells intended for human bone tissue engineering applications.

Slow Progress Under Brazil’s Native Vegetation Protection Law in the Southeastern Amazon - Hellen Kezia Almada; Rosane Barbosa Lopes Cavalcante; Pedro M. Walfir Souza-Filho; Wilson Nascimento; Sâmia Nunes (Environmental Management, 2026)
There is limited evaluation of the effectiveness of legal environmental protection on private properties in Brazil. This study updates the implementation progress and compensation potential under the Native Vegetation Protection Law (LPVN) in the Itacaiúnas River Basin (BHRI, 41,300 km²), located in Pará, the state with the highest deforestation rates in the Amazon over the past two decades. In 2021, the total Legal Reserve (RL) deficit in BHRI exceeded the surplus by 413 km². A significant portion of this deficit (55% or 2399 km²) could be addressed through compensation, with 3721 km² available within the basin, often in the same or neighboring municipalities. Despite nearly fifteen years since the enactment of the LPVN, progress remains slow in halting deforestation and restoring vegetation. By 2021, 1496 km² of RL deficit should have been under restoration or compensation for medium and large properties. However, only half of the 2008 RL deficit had been addressed. Likewise, just 25% of the 2008 Permanent Preservation Area (APP) deficit had been restored by 2021. Meanwhile, ongoing deforestation in RL and APPs, especially in settlements and small properties, highlights the need for more effective implementation mechanisms. While the state of Pará has made strides in registering and analyzing the Rural Environmental Registry (CAR), implementation of the Environmental Regularization Program (PRA) still faces major challenges. Innovative approaches, such as agroforestry, could help align restoration goals with landowners’ economic interests. Overcoming barriers to regulatory compliance will require coordinated efforts and stronger enforcement mechanisms.

Understanding the impacts of hydropower development on people, fish and the environment on the Madeira River of Amazonia, Brazil - Shannon H. Clarke; Maria Clara B. T. Cavalcanti; Vivian M. Nguyen; Taylor D. Ward; Eduardo G. Martins; Michael Power; Gustavo Hallwass; Priscila F. M. Lopes; Steven J. Cooke (Environmental Management, 2026)

Plant Functional Traits and Vegetation Structure Explain Pollination Networks at Scale - Kendall M. Jefferys; Luísa G. Carvalheiro; Adrian González Chaves; Jacobus Petersen; Xiongjie Deng; Waira S. Machida; Katherine C. R. Baldock; Danilo Boscolo; Daniel W. Carstensen; Alice Classen; Patrícia Alves Ferreira; Breno M. Freitas; et al. (Ecology Letters, 2026)
Quantifying biotic interactions at scale is critical to understanding ecosystem functions, such as plant‐pollinator interactions. Here, we demonstrate how woody plant functional traits and vegetation structure gathered with remote sensing can aid in predicting plant‐pollinator network indices from fine to broad spatial extents. We analysed 209 tropical plant‐pollinator networks, where vegetation characteristics were generated using spectral and LiDAR data. We found that pollination network structures were correlated to plant traits reflective of drought‐adaptive strategies and nutrient availability. Networks were predicted to be more nested and less specialised with increasing leaf nitrogen content. Further, relationships between leaf thickness, photosynthetic capacity, and water content indicate that networks may be more modular and less connected under arid, high‐light conditions where plants invest in water‐conserving tissues yet maintain high photosynthetic rates. Our findings reveal plant functional strategies as underlying environmental mechanisms that structure plant‐pollinator networks, paving the way to predict interactions using remote sensing.

Presence of micro-mesoplastics in beaches and sediments of São Francisco do Sul (Brazil) - Elisângela S. Lopes-Ricardo; Amarildo O. Martins; Uberson B. Rossa; Eduardo A. W. Ribeiro; André R. Prado; Erik N. Gomes; Claudemir M. Radetski (Environmental Monitoring and Assessment, 2026)
The coastal environment is a critical interface for monitoring plastic pollution. This study investigated microplastics (MPs, < 5 mm) and mesoplastics (MePs, 5–25 mm) in Praia Grande, São Francisco do Sul (SC State, Brazil), using stereomicroscopy and ATR-FTIR spectroscopy. Two sites with contrasting urbanization and tourism levels were assessed. Area #1, the more urbanized site, exhibited higher concentrations of MPs (70.44 particles·m⁻ 2 ) and MePs (25.11 particles·m⁻ 2 ) than Area #2 (19.11 MPs·m⁻ 2 ; 6.67 MePs·m⁻ 2 ). Morphological analysis revealed predominance of fragments in Area #1 and fibers (MPs) or foam (MePs) in Area #2. White, blue, and translucent particles were most abundant, while polymer identification highlighted the dominance of polyethylene, polypropylene, and styrene-butadiene copolymer, reflecting both global production patterns and local anthropogenic inputs. Sediment granulometry and hydrodynamics emerged as primary drivers of plastic retention, modulated by urbanization and tourism. Positive correlations between MePs and MPs indicate that MePs act as transitional reservoirs, contributing to secondary microplastic formation. These findings emphasize the hierarchical interplay of physical and anthropogenic factors in shaping coastal plastic distribution and provide a process-based framework to inform monitoring and management strategies.

Polyphasic characterization and biotechnological potential of three novel Prochlorococcaceae (Cyanobacteria) genera: An integrative taxonomic approach combining 16S rRNA gene, genomic and chemotaxonomic analyses - Flavio Oliveira; Guilherme Scotta Hentschke; Graciliana Lopes; Aimone Duarte; Teresa De Rosa; Ruben Luz; Alexandre Campos; Vitor M. Vasconcelos (Algal Research, 2026)

Genetic deletion of adenosine A2A receptors attenuates memory deterioration and alterations of synaptic plasticity and metabolic controllers in the hippocampus and prefrontal cortex of aged mice - Cátia R. Lopes; Daniela Madeira; Madalena Piteira; Pedro Valada; Joana Santos; Henrique B. Silva; Francisco Q. Gonçalves; Ângelo R. Tomé; Paula M. Canas; João Pedro Lopes; Samira G. Ferreira; Paula Agostinho; et al. (GeroScience, 2026)
The incidence of brain diseases increases with aging, but the biological basis of brain aging is still poorly explored. Synaptic dysfunction occurs at the onset of brain diseases and synaptic neuromodulation systems, such as adenosine A 2A receptors (A 2A R), are necessary and sufficient to trigger brain dysfunction. Since A 2A R are upregulated upon aging, we compared wild-type and A 2A R global knockout mice to test if brain aging involves synaptic senescence linked to A 2A R overfunction, leading to synaptic and cognitive deterioration. Aging impacted different behavioral outputs, namely spatial learning and memory, coupled to aberrant synaptic plasticity in the hippocampus and prefrontal cortex. Moreover, aging led to an imbalance between excitation and inhibition markers and dysregulated key metabolic coordinators, including sirtuin-1, sirtuin-3, AMPK and p38MAPK. These cognitive impairments and synaptic and metabolic signaling alterations were not observed in aged mice with A 2A R genetic elimination. These findings suggest that A 2A R overfunction can be a key driver of age-associated memory deterioration and A 2A R blockade might promote healthy brain aging. Graphical abstract Aging affected memory and synaptic plasticity, disrupted the balance between excitation and inhibition markers and deregulated key metabolic regulators, namely SIRT1, SIRT3, AMPK and p38MAPK, in the hippocampus and prefrontal cortex of aged mice. A 2A R elimination prevented memory deterioration and most synaptic and metabolic-related alterations in both cortical regions were no longer present. Thus, A 2A R upregulation might be a driver of synaptic senescence-like metabolic and A 2A R blockade may help prevent synaptic dysfunction and, consequently, promote healthy aging.

Mapping the difficulties in implementing resource efficiency measures of European Companies - Sofia Gomes; João M. Lopes; Elisabete Nogueira (Resources Policy, 2026)

High-resolution temporal dynamics of diatoms in a large and well-mixed tropical estuary - Paula Birocchi; Wilson Oliveira-Souza; Caio Braz; Danilo Augusto Silva; Luciana Rocha Frazão; José Juan Barrera-Alba; Guilherme C. Lessa; Rubens M. Lopes (Marine Environmental Research, 2026)

Reliability-based assessment of knot impact and safety factor calibration for axial timber elements with knots - Matheus S. Martins; Wanderlei M. Pereira Junior; João Paulo M. Lopes; Davidson O. França; André L. Christoforo; Marcos L. Henrique; António A. Henriques (Engineering Structures, 2026)

Prospection of Autochthonous Lactic Acid Bacteria Displaying Probiotic Potential to Enhance Colossoma macropomum Larvae Growth and Immunoprotection Against Aeromonas hydrophila - Thayná M. dos Santos; Layana A. B. Pereira; Laine P. C. dos Santos; Andrya L. Lopes; Larissa A. F. Sampaio; Graziella V. G. de Matos Silva; Juliana N. Ferreira; Gleika T. J. Dos Reis; Jonny B. Teixeira; Raimundo J. T. Diniz‐Neto; Laura G. M. de Carvalho; Michelle Midori Sena Fugimura; et al. (Journal of Fish Diseases, 2026)
This study assessed the functional potential of autochthonous lactic acid bacteria isolated from the gastrointestinal tract of tambaqui ( Colossoma macropomum ) as larviculture probiotics. Five strains were selected and identified as belonging to the genus Weissella . In vitro assays revealed high tolerance to acidic pH (2.0–3.0), resistance to bile salts (10%), biofilm formation capacity, hydrophobicity and direct Aeromonas hydrophila inhibition. In in vivo tests, strains M13 and M14 promoted significant increases in tambaqui survival (72.2% and 68.7%; p

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Surface-functionalized g-C3N4/3D-printed alkali-activated materials for the removal of emerging water pollutants - J.G. Cuadra; Nuno P.F. Gonçalves; K. Ben Tayeb; Catia Venâncio; S. Costa; I. Lopes; T. Trindade; J.A. Labrincha; Rui M. Novais (Chemical Engineering Journal, 2026)

Adjuvant effects on spray deposition and efficacy of diquat and glufosinate against Euphorbia heterophylla and Digitaria insularis - Agatha S. Argioli; Marina Funichello; Paulo H. Pagliari; Ronaldo C. Lima; Fernando S. Galindo; Paulo R. M. Lopes; Vagner Nascimento; Carlos G. Raetano; José F. V. Sierra; Evandro P. Prado (Journal of Plant Diseases and Protection, 2026)

Postfire oak afforestation in Portugal reveals trade-offs in the supply of ecosystem services - Luís F. Lopes; Erika S. Santos; Leónia Nunes; Paulo M. Fernandes; Vanda Acácio (European Journal of Forest Research, 2026)

Ecological networks reveal strong pest suppression complementarity between birds and bats within rice-dominated agroecosystems in West Africa - Patrícia P. Chaves; Vanessa A. Mata; Paula Lopes; Mutaro Camará; Daniel Coimbra; Djunco Dabo; Ricardo F. de Lima; Miguel Lecoq; Gonçalo Fernandes; Patrícia Guedes; Inês Lacerda; Mark Massaad; et al. (Agriculture, Ecosystems & Environment, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Comprehensive review of polycyclic aromatic hydrocarbons (PAHs) in biota: Analytical methods and associated health and ecological risks in oiled and non-oiled areas - Antônia D.F. Lima; Davi A. Martins; Íthala S. de Santiago; Luíza C. Mello; Marília G.G. Menezes; Rafael P. dos Santos; Rafaella N. Garcia; Beatriz D. Lopes; Antônio D.S. Pereira; Rivelino M. Cavalcante (Marine Pollution Bulletin, 2026)

Seamounts of Cabo Verde: A review of their ecological and economic significance, anthropogenic impacts, and conservation needs - Covadonga Orejas; Beatriz Vinha; Gillian B. Ainsworth; Sarah Saldanha; Teresa Militão; Christian Mohn; Thor H. Hansteen; Sara S. Ratão; Henk-Jan Hoving; Teresa Amaro; Dominique M.J. Anderson; Deusa Araújo; et al. (Progress in Oceanography, 2026)

Trait-mediated effects of Macoma balthica (L.) on nitrogen and carbon biogeochemistry in estuarine ecosystems - Gabriel Pereira; Calli M. Wise; Katrina M. Pagenkopp Lohan; Genevieve L. Noyce; Marta L. Lopes; Luísa Magalhães (Marine Environmental Research, 2026)

Cellulose nanofibers as stabilizer of Pickering emulsions and reinforcement of pectin films covering tomatoes - Raquel Costa Chevalier; Jorge M. Vieira; Joana T. Martins; Rosiane Lopes Cunha; António A. Vicente (Food and Bioproducts Processing, 2026)

Scalable thermal imaging and processing framework for water status monitoring in vineyards - André Pires; Alexandre Bernardino; Gonçalo Victorino; J. Miguel Costa; Carlos M. Lopes; José Santos-Victor (Computers and Electronics in Agriculture, 2025)

Computational and spectrofluorimetric validation on glyphosate interactions with zebrafish (Danio rerio) acetylcholinesterase: Mechanistic and ecotoxicological implications - Andressa Rubim Lopes; Michael González-Durruthy; Maria Natália D.S. Cordeiro; Ana S. Moura; Ramón Rial; Juan M. Ruso; Juliana Zomer Sandrini; Carlos Eduardo da Rosa; Camila de Martinez Gaspar Martins (Toxicology in Vitro, 2025)

A sedimentary record of paleodirectional and relative paleointensity variations of the Earth's magnetic field from offshore South Brazil spanning the time from 46.15 to 5.36 ka - Camila T. Lopes; Jairo F. Savian; Everton Frigo; Gelvam A. Hartmann; Maria A.G. Pivel; Sanja Panovska; Jaime Y. Suárez-Ibarra; Caroline A. Pontel; João C. Coimbra; Sandro M. Petró; Adriana Leonhardt; Ricardo I.F. Trindade (Quaternary Science Reviews, 2025)

Urban resilience to floods in the context of the disaster risk management cycle: a literature review - Ana Cristina R. Lopes; Osvaldo M. Rezende; Marcelo G. Miguez (Journal of Hydrology, 2025)

Reproductive success over Calliandra fasciculata Benth. floral anthesis: evidence of adaptive generalization - Rodrigo Santiago; Pedro J. Bergamo; Vinícius L.G. Brito; Marsal D. Amorim; Lucas B. Castro; Sabrina A. Lopes; Cinthia S. Novaes; Larissa C. Mendes; Gizele C.A. Silva; Danila M. Silva; Ilmara A.O. Ferreira; Bernardo O. Dias; et al. (Flora, 2025)

Impact of large events on microplastic pollution on sandy beaches: a case study of Carnival in Rio de Janeiro, Brazil - G.I. Sodré; G. Martins; M.G. Lopes; R.R.S. Abude; M. Augusto; M.M. Cunha; C.W.C. Branco; S.G.M. Portugal; T.M.B. Cabrini (Estuarine, Coastal and Shelf Science, 2025)

Population structure and divergence time among East Greenland and West Greenland/Eastern Canadian Arctic narwhals, Monodon monoceros - Xênia M. Lopes; Martine Bérubé; Kit M. Kovacs; Rune Dietz; Steven H. Ferguson; Mads Peter Heide-Jørgensen; Christian Lydersen; Per J. Palsbøll (Polar Biology, 2025)
The narwhal ( Monodon monoceros ) is an Arctic endemic odontocete that is particularly sensitive to climate change. Narwhals are also a key species in subsistence hunts in both Canada and Greenland. Understanding the genetic population structure is crucial to help management authorities set sustainable harvest quotas to avoid overexploitation of vulnerable narwhal groups. Additionally, estimates of population divergence times and their correlation with potential environmental drivers may be informative regarding the effects of environmental change. Herein, 2236 genome-wide single-nucleotide polymorphisms from 40 narwhals were used to infer population structure and divergence times. Samples were collected in six localities, one in East Greenland, four in West Greenland and one in the Eastern Canadian Arctic. The highest degree of genetic differentiation was observed between narwhals from Kangertittivaq (East Greenland) and Tasiujaq (Eastern Canadian Arctic), with a θ of 0.021 (95% confidence interval (CI): 0.014–0.028). While some locations in West Greenland also exhibited significant levels of differentiation (e.g., Uummannaq vs Qeqertarsuaq, θ = 0.011, 95% CI: 0.004–0.020), the East Greenland narwhals were most distinct based on both θ (varying from 0.01, 95% CI: 0–0.01 with Uummannaq to 0.021 95% CI: 0.014–0.028 with Tasiujaq) and clustering analyses. Our results are relevant to the management of narwhals in East Greenland, where current hunting levels are likely unsustainable. The divergence time estimated between East Greenland and West Greenland/Eastern Canadian Arctic suggests that narwhals in these two areas became separated during the Last Glacial Maximum, offering additional insight into the long-term population dynamics during climate change.

The G allele of the rs4344 polymorphism of the angiotensin-converting enzyme gene is associated with alanine aminotransferase (ALT) and gamma glutamyl transferase (GGT) in Brazilian hypertensive patients - Lívia da C. Agostini; Renata B. M. e Silva; Nayara N. T. Silva; Ana Cláudia F. Lopes; Vanessa de A. Belo; Wendel Coura-Vital; Luiz Fernando de M. Teixeira; Angélica A. Lima; Glenda Nicioli da Silva (Molecular Biology Reports, 2025)

Dysregulation of AR and ERα caused ovarian alterations in gerbils prenatally exposed to 17α-ethinylestradiol and pequi oil - Amanda M. de Campos; Jordana S. Dias; Gabriel F. Lopes; Thaisla M. Pires; Daniele C. da Silva; Thalles F. Rocha Ruiz; Tracy M. M. Martins; Ana P. S. Perez (Histochemistry and Cell Biology, 2025)

Comparative analysis of isoprostanoid profiles in Chlorella sorokiniana grown under autotrophic and heterotrophic conditions - Tiago Conde; Diana Lopes; Valérie Gros; Guillaume Reversat; Camille Oger; Jean-Marie Galano; Claire Vigor; Alexandre M.C. Rodrigues; Natacha Coelho; Helena Cardoso; M. Rosário Domingues; Thierry Durand (Algal Research, 2025)

Effect of latitudinal gradient on plant mite communities: disentangling the role of environmental and spatial processes on predators and phytophagous mites - Tainá J. Antunes; Elfany R.N. Lopes; Felipe M. Nuvoloni (Acta Oecologica, 2025)

Blackberry, an Attractive Deep Purple Potato Variety with Resistance to Common Scab and Extreme Resistance to Potato Virus Y - David S. Douches; Joseph J. Coombs; William L. Behling; Gregory E. Steere; Matthew L. Zuehlke; Tomás D. Lopes; Joseph I. Ulasi; Christopher M. Long (American Journal of Potato Research, 2025)
Blackberry is a tablestock variety with uniquely deep purple skin and flesh. The tubers have an attractive, uniform, round shape with common scab resistance and low incidence of internal defects. It also carries the Rysto marker for extreme resistance to potato virus Y. When baked or microwaved, the tuber flesh is a brilliant deep purple with an enjoyable mild taste. It was selected in 2011 from a cross between two breeding lines COMN07-W112BG1 and MSU200-5PP. Although primarily oriented towards the fresh market, Blackberry is an all-purpose variety that also has the ability to chip out of the field. Yields are high under irrigated conditions and specific gravity averaged 1.068 in on-farm trials in Michigan.

Antibacterial and antibiofilm activity of ruthenium polypyridine complex against Staphylococcus strains - Leonardo Silva de Sousa; Alexandre Lopes Andrade; Aryane de Azevedo Pinheiro; Felipe Diógenes Abreu; Eduardo Henrique Silva Sousa; Idalina Maria Moreira de Carvalho; Débora S. C. M. Castelo-Branco; Mayron Alves de Vasconcelos; Edson Holanda Teixeira (Biofouling, 2025)

Humpback whale (Megaptera novaeangliae) maturity and body condition in Ireland, Norway and Cabo Verde based on UAS photogrammetry data - Miguel Blázquez; Nick Massett; Seán O’Callaghan; Marcus Hogan; Pedro López-Suárez; Katia Lopes; Pádraig Whooley; Joanne M. O’Brien; Frederick W. Wenzel; Ian O’Connor; Simon D. Berrow (Frontiers in Marine Science, 2025)
Animal morphometrics are essential for understanding a species’ life history and its ecological interactions with the environment. This study investigates the maturity status and body condition of humpback whales ( Megaptera novaeangliae ) across understudied areas of the Northeastern Atlantic Ocean. Uncrewed Aerial Systems (UAS or drones) were used to collect photogrammetry data from humpback whales in Ireland, Norway, and Cabo Verde between 2022 and 2024. Body length and condition metrics were derived from aerial imagery and analyzed using Bayesian modeling to estimate and propagate measurement uncertainty. The resulting measurements were evaluated to infer maturity status, migratory patterns, and habitat use. Photogrammetric measurements indicated potential variability in whale body length and condition across study areas, with individuals in Cabo Verde appearing larger and in better condition. In Irish waters, body length was positively correlated with offshore habitat preference, while shorter (younger) individuals tended to inhabit nearshore waters, potentially increasing their exposure to anthropogenic pressures. Additionally, body condition improved intra-seasonally at both the population and individual levels in Irish waters. These findings demonstrate the utility of UAS photogrammetry for assessing the maturity and body condition of humpback whales across diverse habitats. The observed geographical and temporal trends in condition provide valuable insights into habitat use and underscore the importance of Ireland as a feeding ground in the Northeastern Atlantic. This study also highlights the value of UAS photogrammetry in advancing our understanding of baleen whale population ecology in understudied regions, providing relevant information for species conservation and management.

Changes in gut microbiota signatures associated with the epidemiological dynamics of wild European rabbits facing haemorrhagic disease outbreaks - Carlos Rouco; Xavier Triadó-Margarit; Joana Abrantes; Ana M. Lopes; Tereza Almeida; Julio Isla; Gabriela de la Fuente; Oscar Rodriguez; Emilio O. Casamayor (Veterinary Microbiology, 2025)

The Zoo Sphere of Influence Model - Sarah L. Spooner; Susan L. Walker; Simon Dowell; Mara Cristina Marques; Marina Somenzari; Fabiana Lopes Rocha; Eugenia Cordero-Schmidt; Charlotte Hughes; Christine Lee; Charlotte Smith; Jennifer Kelly; Linda Salim; et al. (Biological Conservation, 2025)

Unveiling Gender Disparities: The Role of Women in Transforming Small‐Scale Fisheries - Letícia Maria Cavole; Maisha Gragnolati; Rosani V. M. Matoso Silva; Priscila F. M. Lopes; Tommaso Giarrizzo; José Amorim Reis‐Filho (Fish and Fisheries, 2025)
Issues of equity and social justice have never been more urgent than they are today, as global social disparity continues to rise. The small‐scale fisheries (SSF) sector, long neglected by top‐down policies and mainstream markets, remains essential to the livelihoods of millions worldwide. In this context, equity challenges are particularly pressing. This study examines Brazil's SSF sector, focusing on gender dynamics and disparities. Home to the largest SSF population in the Americas, Brazil ranks among the top countries globally in fisherwomen—with nearly 900,000 women engaged in the sector, representing half of its SSF workforce. Despite their numbers and contributions to sustainable practices, such as low bycatch rates and minimal fuel usage, fisherwomen consistently earn less than men and are largely overlooked in social protection policies. Our analysis reveals a historical and persistent underrepresentation in policy, fishery‐dependent research, and social science, culminating in legal and economic imbalances—particularly in regions where fisherwomen form the majority, such as the North and Northeast. This results in reduced access to fisheries‐derived income and management benefits compared to fishermen. Moreover, fisherwomen remain underrepresented in decision‐making processes, despite their work aligning with key Sustainable Development Goals, including poverty reduction, gender equality, and sustainable resource management. This study offers recommendations beyond policy, including capacity‐building initiatives and implementation of gender‐disaggregated data systems to advance equity and social justice for Brazilian fisherwomen, providing a potential model for nations facing similar socio‐environmental challenges. It aims to catalyse global dialogue and inclusive reforms that recognise, protect, and empower women in small‐scale fisheries.

Enhanced antimicrobial and antibiofilm activities of ruthenium complexes with fluorine- and bromine-substituted ligands against staphylococcal strains - Alexandre Lopes Andrade; Mayron Alves de Vasconcelos; Isa Maria Ferreira Azevedo; Tatiane Gomes da Silva; Paula Victoria Soares; Ellen Araújo Malveira; José Marcos da Silveira Carvalho; Débora S. C. M. Castelo-Branco; Luiz Gonzaga de França Lopes; Eduardo Henrique Silva Sousa; Edson Holanda Teixeira (Biofouling, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Combining residual iron dust and biomass fly ash as in-situ waste-based catalysts to promote tar reduction and enhance producer gas quality from biomass steam gasification - Helena G.M.F. Gomes; Daniela V. Lopes; João P. Ribeiro; Jéssica M. Moura; Nuno M.C. Cruz; Aleksey Yaremchenko; Maria I. Nunes; Manuel A.A. Matos; Luís A.C. Tarelho (Journal of Cleaner Production, 2025)

Ecotoxicological impact of residual polycyclic aromatic hydrocarbon pollution in the largest Brazilian marine protected area: A multibiomarker approach in the marine clam Tivela mactroides - Bianca Leite Carnib; Jerusa Maria de Oliveira; Zaíne Marcyelle F. do Nascimento; Gabriel Tenório T. Garibaldi; Taciana Kramer Pinto; Thiago Lopes Rocha; Rivelino M. Cavalcante; Viviane Lemos; Luciana M. Bastos; Arlene B.S. Nossol; Mário M. Martins; Otoniel D. Santana; et al. (Environmental Pollution, 2025)

Simultaneous removal of bisphenol S, carbamazepine, and clonazepam from water applying composites formed by titanium oxide and coconut shell–based material: statistical and AI-based approaches for real wastewater treatment - Marina M. G. Pastre; Deivisson Lopes Cunha; Rodrigo Coutinho; Sandra M. Landi; Adriana M. da Silva; Braulio S. Archanjo; Alexei Kuznetsov; Marcia Marques (Environmental Science and Pollution Research, 2025)

P28-12 Stronger together: achieving scalability for a novel in vitro human male reproductive toxicity assay by deep learning image analysis pipelines - R.J. Postma; M. Trimp; S.M. Chuva de Sousa Lopes (Toxicology Letters, 2025)

Integrating epidemiological and economic models to estimate the cost of simulated foot-and-mouth disease outbreaks in Brazil - Nicolas C. Cardenas; Taís C. de Menezes; Amanda M. Countryman; Francisco P.N. Lopes; Fernando H.S. Groff; Grazziane M. Rigon; Marcelo Gocks; Gustavo Machado (Preventive Veterinary Medicine, 2025)

Removing pollutants and recovering resources in treatment wetlands cultivated with ora-pro-nobis and citronella - L. S. Lopes; T. S. Alves; A. M. Araújo; F. F. Cunha; A. P. Rosa; A. C. Borges (International Journal of Environmental Science and Technology, 2025)

Climate projections and the future of invasive plants in the Caatinga - Carlos Leandro Costa Silva; Michele S. Dechoum; Rebecca Luna Lucena; Priscila F. M. Lopes (Biological Invasions, 2025)
The increasing prevalence of invasive plants thriving under changing climates underscores a major ecological concern. While many studies address invasions at broad taxonomic scales, our approach emphasizes the simultaneous projection of multiple species grouped by functional traits. In addition to modeling their joint distribution, we evaluated the persistence and spatial overlap between functionally distinct invaders as a possible indicator of future ecological shifts. Ecosystems like the Brazilian Caatinga, a seasonally dry tropical forest spanning 833,000 km 2 , may be especially vulnerable to invasions and climate change due to widespread land degradation. We projected the future distribution of 11 invasive species under both optimistic and pessimistic climate scenarios, spanning 2021 to 2100. Potential distribution changes were assessed considering the joint invasion of all species, grouped into woody and non-woody categories. Areas with annual mean temperatures between 24 and 27 °C and higher precipitation were more prone to invasions. Non-woody species are projected to occupy the largest high-suitability areas throughout the century. Cenchrus ciliaris L. and Prosopis juliflora (Sw.) are examples of major invaders under both scenarios. One region in the Caatinga remained suitable for both woody and non-woody invaders, reflecting a localized zone of functional co-occurrence retention despite overall habitat contraction. Even with projected declines in suitable areas (−36.4% optimistic, −28.2% pessimistic), the continued presence of invasive species poses risks to native flora, which is generally more sensitive to environmental change. These results highlight the urgency of proactive management to safeguard biodiversity.

Novel phenanthroline-based ruthenium complex as a promising antimicrobial agent - Pedro L. N. Teixeira; Ana C. S. Gondim; Tercio F. Paulo; Eduardo H. S. Sousa; Luiz G. F. Lopes; Alejandro P. Ayala; Ellen A. Malveira; Edson H. Teixeira; Mayron A. Vasconcelos; Alda K. M. Holanda (JBIC Journal of Biological Inorganic Chemistry, 2025)

The future of citizen science for marine litter research: What are the benefits to be realised and the challenges to be overcome? - M. Peacock; N.P. Ghilardi-Lopes; A. Turra; T.F. Rech; L.A. Kawabe; B. Gatersleben; K.J. Wyles (Marine Pollution Bulletin, 2025)

CFD modelling of an urban microclimate during a heat wave: Coupling solar radiation and heat transfer - D. Nascimento; A. Ascenso; D. Lopes; M. Lopes; V. Rodrigues (Urban Climate, 2025)

Improving wildfire simulation accuracy using satellite active fire data for interval reinitialization and rate of spread adjustment - Shahab M. Beyki; António Manuel Gameiro Lopes; Aldina Santiago; Luís Laím (Remote Sensing Applications: Society and Environment, 2025)

Reproductive performance of yearling Bos indicus heifers submitted to programs for induction of ovulation prior to a timed-artificial insemination protocol - Ana Luíza M. Lopes; Giselly B. Kolling; Lucas O. e Silva; Rodrigo L.O.R. Alves; Fabiana M. de Assumpção; Suzane K.M. Leite; Akyra Terra; Roger de M. M. Wutke; Antonio C.S. Rezende; José R.S. Rezende; Lainer Leite; Roberto Sartori (Theriogenology, 2025)

Sedimentary facies drive the development of organic-rich Podzols from a tropical barrier island - Pedro Martinez; Paulo César Fonseca Giannini; Josiane M. Lopes-Mazzeto; Gabriel Ramatis Pugliese Andrade; Rosana Gandini; Fillipe S. Marini; Pablo Vidal-Torrado (CATENA, 2025)

Review on biological and biochemical pesticides as a sustainable alternative in organic agriculture - Lissara P. Ody; Maicon S.N. dos Santos; Aline M. Lopes; Marcio A. Mazutti; Marcus V. Tres; Giovani L. Zabot (Biocatalysis and Agricultural Biotechnology, 2025)

Effect of the genotype and environment interaction on body weight traits in Nelore cattle (Bos indicus) - Raimundo Nonato Colares Camargo-Júnior; Cláudio Vieira de Araújo; Caio de Souza Teixeira; Simone Inoe de Araújo; Raysildo Barbosa Lôbo; Lílian Roberta Matimoto Nakabashi; Letícia M. Mendes de Castro; Flávio Luiz Menezes; André Guimarães Maciel e Silva; José Ribamar Felipe Marques; Welligton Conceição da Silva; Marco Aurélio Lopes Della Flora; et al. (Tropical Animal Health and Production, 2025)

Characterizing pioneer plants for phytoremediation of mercury-contaminated urban soils - C. dos Santos Soares; V. J. Santos Lopes; F. de Freitas; M. O. Córdova; L. Cavalheiro; L. D. Battirola; R. L. T. de Andrade (International Journal of Environmental Science and Technology, 2025)

Unveiling CYP450 inhibition by the pesticide prothioconazole through integrated in vitro studies and PBPK modeling - Icaro S. Perovani; Priscila A. Yamamoto; Rodrigo M. da Silva; Norberto P. Lopes; Natalia V. de Moraes; Anderson R. M. de Oliveira (Archives of Toxicology, 2025)

Drought-induced changes in antioxidant capacity, mineral content, and plant development in basal leafy cactus: comparisons between Pereskia aculeata miller and Pereskia bahiensis Gürke - Daniel S. Gomes; Antônio N. Andrade; Estephanni F.O. Dantas; Vanessa A. Soares; Damiana J. Araujo; Sabrina K. Santos; Adriano S. Lopes; José E.S. Ribeiro; Valquiria C.S. Ferreira; Juliane M. Henschel; Walter E. Pereira; Thiago J. Dias; et al. (Journal of Plant Physiology, 2025)

Production of sustainable aviation fuel precursors using the oleaginous yeast Rhodotorula toruloides PYCC 5615 cultivated on eucalyptus bark hydrolysate - Teresa Lopes da Silva; Francisca Dutra; Susana Marques; Miguel Gomes; Paula Costa; Filipe Paradela; Frederico Castelo Ferreira; Nuno Torres Faria; Paula Mugica; Helena M. Pinheiro; Isabel Sá-Correia; Francisco Gírio (Biomass and Bioenergy, 2025)

Changes in the swimming behavior of Temora turbinata (Copepoda, Calanoida) in response to sub-lethal concentrations of caffeine and triclosan - Gelaysi Moreno-Vega; Luciana Rocha Frazão; Leandro Ticlia De-La-Cruz; Rubens M. Lopes (Aquatic Toxicology, 2025)

Soybean Seed Priming with Brassinosteroids Mitigates the Effects of Drought Stress - Sebastião de O. Maia Júnior; Jailma Ribeiro de Andrade; Patrick Costa Silva; Danielle Lopes Aguiar; Florine Alves S. Pinheiro; Lorena Silva Campos; Daniel Cutrim Diniz; Antônio Moisés de S. Torres; Fábio Afonso M. M. de Assis Figueiredo; Fabrício de Oliveira Reis; Tiago Massi Ferraz (Journal of Plant Growth Regulation, 2025)

Assessing the efficacy and generational stability of commercial transgenic maize resistance against key stored-product insect pests - J. Parsons; J. Riudavets; M. S. Lopes (Journal of Pest Science, 2025)
Genetic resistance, particularly through transgenic Bt maize, has demonstrated high efficacy in pest control under field conditions. However, in storage conditions, maize is susceptible to different pest species, which compromises its quality. It is unknown how effectively the Bt maize functions in storage environments or if resistance is being inherited in later generations. This study investigates two commercial maize genotypes: a transgenic genotype expressing the Cry1Ab protein and its near-isoline counterpart. It utilizes commercial seeds of both genotypes (F1), along with seeds obtained from field-grown transgenic and near-isoline plants (F2), which represent the seeds stored by farmers and the agricultural industry. The aim is to assess their vulnerability to common insect pests that affect stored products. By assessing grain damage and insect population dynamics, we identify differences in resistance among these different maize genotypes and generations. Our findings show that transgenic maize exhibits strong resistance against Sitotroga cerealella but lower resistance against Sitophilus zeamais . The impact of Oryzaephilus surinamensis on both genotypes was negligible. Additionally, the resistance diminishes in the F2 generation. With S. cerealella the F2 transgenic experienced 55% more damage compared to the F1. Similarly, in the case of S. zeamais , the F2 maize produced five times more frass than the F1, highlighting a significant reduction in resistance. This research identifies the resistance characteristics of maize, highlighting the most suitable traits for assessing pest resistance in stored maize. It emphasizes the need for sustainable pest control with genetic resistance, ensuring long-term protection of stored grains, and minimizing post-harvest losses.

The caatinga dry tropical forest: A highly efficient carbon sink in South America - Keila R. Mendes; Pablo E.S. Oliveira; José Romualdo S. Lima; Magna S.B. Moura; Eduardo S. Souza; Aldrin M. Perez-Marin; John Elton B.L. Cunha; Pedro R. Mutti; Gabriel B. Costa; Thales N. Martins de Sá; Paula A.A. Araujo; Rosaria R. Ferreira; et al. (Agricultural and Forest Meteorology, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

Socioenvironmental impacts of the Belo Monte hydroelectric power plant as revealed by Indigenous and ribeirinho monitoring - Josiel Jacinto Pereira Juruna; Raimundo da Cruz e Silva; Orcylene Barbosa dos Reis; Amildon Moura Assunção; Anderson Sampaio da Silva; Helio Bezerra da Silva; Jailson Jacinto Pereira Juruna; Josimary Abreu Nunes; Micaele Souza Santos Kleme; Paulo Passos Ferreira; Ronald Txakui Viana da Silva Juruna; Rosilene Sousa dos Santos; et al. (Conservation Biology, 2025)
Hydroelectric dams, once seen as clean and renewable energy sources, have been the subject of extensive research, particularly concerning their socioenvironmental impacts. The Belo Monte hydroelectric power plant (HPP) relies on the operation of 2 dams that divert water from a 130‐km stretch of the Xingu River to generate energy. The dam has disrupted the seasonal flooding cycle (flood pulse) along the Volta Grande do Xingu (VGX) and created a reduced discharge condition analogous to a prolonged and extreme dry season in the watershed. Before the Belo Monte HPP, local communities relied on the highly diverse and abundant fish assemblage supported by seasonal flooding of the ecosystem. Local VGX residents sought partnerships and established the Independent Territorial Environmental Monitoring Program (MATI‐VGX). Through this program, locals monitored fish spawning sites and fishing dynamics. This monitoring complemented and quantified local communities’ perceptions about the environmental impacts caused by the Belo Monte HPP. The HPP was associated with a water discharge shortage that critically undermined the river's capacity to sustain vital ecosystem processes that support local people's lives. Drastic transformations of traditional lifestyles, shifts in fishing practices, and a significant decline in fishing yield occurred that jeopardized food sovereignty and security. The Belo Monte HPP environmental licensing process ignored local ecological knowledge and the vital links among the river's flood pulse, the aquatic and seasonally flooded ecosystems, and the traditional lifestyles of VGX residents. To ensure the ecological sustainability of the VGX, the Belo Monte HPP operation needs to change to support key spawning areas, maintain water discharge, avoid short‐term water fluctuations, and emulate natural interannual discharge variability to mitigate flood pulse disruption. Local ecological knowledge should never be ignored in projects where local communities are the most affected. These communities should be central in decision‐making regarding socioenvironmental impact assessment, mitigation, and monitoring.

Pathological and serological insights into Lagovirus diseases dynamics in the European brown hare (Lepus europaeus): A nine-year longitudinal study - Josep Estruch; Patrizia Cavadini; Antonio Lavazza; Lorenzo Capucci; Joana Abrantes; Ana M. Lopes; Tereza Almeida; Aleksija Neimanis; Santiago Lavín; Carlos Rouco; Emmanuel Serrano; Roser Velarde (Veterinary Microbiology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Interplay between quantitative trait loci for stem strength and agronomic traits in a wheat doubled-haploid population - J. Allan Feurtado; Letitia M. Da Ros; Shola H. Kareem; Breenah Mulligan; Daiqing Huang; Lanette Ehman; Parul Jain; Leah K. Flatman; Hanna Hovland; Jeff Hovland; Brett Beckie; Richard D. Cuthbert; et al. (Field Crops Research, 2025)

Microplastics in the deep: Suspended particles affect the model species Mytilus galloprovincialis under hyperbaric conditions - Marlene Pinheiro; Clara Lopes; Nélson Alves; Eunice Almeida; Hugo Morais; Marta Ribeiro; Susana Barros; Joana Raimundo; Miguel Caetano; Teresa Neuparth; Miguel M. Santos (Environmental Pollution, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Pharmaceuticals and personal care products in the coastal zone of Ubatuba (Brazil): An ecological and touristic hotspot facing high contamination - Luciana Rocha Frazão; Silvana Batista Penninck; Camila Negrão Signori; Rubens M. Lopes (Science of The Total Environment, 2025)

Salmonella enterica Senftenberg (IOC 2319) and Salmonella enterica Typhimurium (ATCC 14028) under low water activity stress: Effects on culturability and cell viability - Syllas B.S. Oliveira; Mayara M. Oliveira; Leticia S. Lopes; Arthur K.R. Pia; João Victor Virgilio-da-Silva; Anderson S. Sant'Ana (International Journal of Food Microbiology, 2025)

A multiscale analysis of the Dolores, Uruguay, tornadoes of 6 December 2012 and 15 April 2016 - Maurício I. Oliveira; Murilo M. Lopes; Vitor Goede; Marcelo Barreiro; Paola M. Salio; Eliton L. Figueiredo; Ming Xue (Atmospheric Research, 2025)

Time Dimension Influences Severity of Stroke and Heightened Immune Response in Mice - Pradip K. Kamat; Mohammad Badruzzaman Khan; Shahneela Siddiqui; Dylan Williams; Evila da Silva Lopes Salles; Sahar Emami Naeini; Ali S. Arbab; Daniel R. Rudic; Babak Baban; Krishnan M. Dhandapani; David C. Hess (Translational Stroke Research, 2025)

Uncovering miRNA-Mediated Regulation in Phellem Versus Xylem Differentiation in Quercus suber L. - Susana T. Lopes; Bruno Costa; Inês Chaves; Augusta Costa; Célia M. Miguel (Journal of Plant Growth Regulation, 2025)
Several regulators of phellem/cork formation have been identified in recent years, using mainly transcriptomic approaches. However, this developmental process, showing parallels to the functioning of vascular cambium, remains poorly understood. The cork oak tree ( Quercus suber L.) exhibits a remarkable ability to form a traumatic phellogen after debarking, enabling sustainable cork production. We aimed at uncovering post-transcriptional mechanisms controlled by miRNAs, specifically involved in regulating phellogen functioning and phellem differentiation in cork oak. To achieve this, we conducted a comparative analysis of the small RNA transcriptome between differentiating phellem and xylem, both originating from secondary meristems (phellogen and vascular cambium). In addition to identifying miRNAs exclusive to phellogen/phellem tissues, we discovered 246 differentially expressed miRNAs between the two tissues, of which 74 are conserved. The most abundant miRNA families found in phellem tissues were MIR165/166, MIR167, MIR168 and MIR390. By analysing miRNA predicted targets and their expression in the same tissues, many of the differentially expressed miRNAs were found associated with sequence-specific DNA binding functions. Within these, transcription factor families HD-ZIP III, WRKY, NAC and MYB were highlighted as key in phellem differentiation. Furthermore, hormone-mediated signalling pathways, particularly involving auxin, appeared as an enriched biological process, as several ARF transcripts, among other auxin signalling genes like IAA11, ARF18 and ARF19, were identified as putative targets of conserved or novel miRNAs. Overall, our results provide a comprehensive overview of the miRNA landscape during cork formation, providing valuable knowledge for further functional studies and potential practical applications in forest management. Graphical Abstract

Unraveling the lipidome of Pavlova gyrans, a natural reservoir of bioactive lipids for biotechnological applications - Tiago Conde; Diana Lopes; Marisa Pinho; Tânia Melo; Natacha Coelho; Alexandre M. C. Rodrigues; Hugo Pereira; Pedro Domingues; Rosário Domingues (Journal of Applied Phycology, 2025)

Epidemiological surveillance of myxoma virus in European hares (Lepus europaeus) in the Iberian Peninsula: First evidence of infection by the emerging ha-MYXV - Beatriz Cardoso; Sabrina Castro-Scholten; Roser Velarde; Salvador Rejón-Segura; Remigio Martínez; Ana M. Lopes; Lorena Pereira; Kevin P. Dalton; Andrea Menéndez-Manjón; Josep Estruch; Vanesa Alzaga; Jacinto Román; et al. (Veterinary Microbiology, 2025)

Homologous acetylenic acetogenins from Porcelia macrocarpa R.E. (Fries) displayed potent activity against amastigotes from Trypanosoma cruzi - Ivanildo A. Brito; Erica V. Castro Levatti; Luis O. Regasini; Edgard A. Ferreira; Flavia B. Lopes; João Paulo S. Fernandes; João M. Batista; Andre G. Tempone; João Henrique G. Lago (Phytochemistry, 2025)

Chemical characterization and antioxidant potential of Arthrospira sp., Thalassiosira sp., and Raphidonema sp. - Vera Castro; Ana Teixeira; Luara Simões; Franklin Chamorro; Catarina Lourenço-Lopes; Celina Parreira; Sara M. Badenes; Luís Costa; Miguel A. Prieto; Rui Oliveira; Alberto C.P. Dias (Food Chemistry, 2025)

Microwave-assisted microscale acid decomposition for determination of essential elements in processed meats by MIP OES - Ana Claudia B. Luckow; Yasmin R. Bloedorn; Daisa H. Bonemann; Sabrina H. Scherdien; Charlie G. Gomes; Emanoelli R. Lopes; Anderson S. Ribeiro; Adriane M. Nunes (Food Control, 2025)

Impact of the estrous cycle on brain monoamines and behavioral and respiratory responses to CO2 in mice - Beatriz Dominiquini-Moraes; Mariana Bernardes-Ribeiro; Luis Gustavo A. Patrone; Elisa M. Fonseca; Alana T. Frias; Kaoma S. Costa Silva; Roberta Araujo-Lopes; Raphael E. Szawka; Kênia C. Bícego; Hélio Zangrossi; Luciane H. Gargaglioni (Pflügers Archiv - European Journal of Physiology, 2025)

A new early diverging lepisosteid fish (Lepisosteiformes) from the Late Cretaceous of southeastern Brazil - Agustín G. Martinelli; Thiago da Silva Marinho; Karen M. Panzeri; Sergio Bogan; Fabiano V. Iori; João de Magalhães Lopes; Francisco Macedo Neto; Pedro H. Fonseca; Giorgio Basilici; Nahuel Vega; Luiz Carlos Borges Ribeiro (Journal of South American Earth Sciences, 2025)

Addressing the urgent climate and biodiversity crisis through strategic ecosystem restoration in Brazil - Luisa Fernanda Liévano-Latorre; Juliana M. de Almeida-Rocha; Alberto Akama; Hernani Alves Almeida; Ricardo Teixeira Gregório Andrade; Marcelo Rodrigues dos Anjos; Yasmine Antonini; Thaise de Oliveira Bahia; Flavia Rodrigues Barbosa; Reinaldo Imbrozio Barbosa; Claudia Franca Barros; Helena Godoy Bergallo; et al. (Biological Conservation, 2025)

Transforming Traditional Industry Advisory Boards Into Mutually Beneficial Strategic Think Tanks: A Peer Review Council Case Series and Best Practices - Todd Williamson; John Fox; Scott Ramsey; Maria Martins-Lopes; Kevin M. Pantalone; C. Daniel Mullins; Kenneth Schaecher; Sean D. Sullivan (Journal of Pharmaceutical Innovation, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

HiDaFernPT : Historical data of spore availability for 121 fern and lycopod taxa in Portugal (1926–2013) - Sérgio Timóteo; Ruben Heleno; Filipe Covelo; Joaquim Santos; Pedro Lopes; António C. Gouveia; Arménio Matos; Agostinho Salgado; M. Teresa Girão da Cruz; João Farminhão; Marta Horta; Guilherme Barreto; et al. (Ecology, 2025)
Species phenology is being altered by ongoing climate changes with yet underappreciated consequences for ecological processes and ecosystem stability. Contrary to what happens with some key life events of flowering plants, comparatively little information exists about fern and lycophyte phenology and how it is affected by the current climatic changes. In part, this stems from the lack of long‐term datasets. Here we provide information on the collection day and site of the spores of 121 native and introduced fern (Polypodiopsida) and lycopod (Lycopodiopsida) taxa for the Index Seminum of the Botanic Garden of the University of Coimbra. Spores were collected from spontaneous and cultivated individuals across Portugal between 1926 and 2013. The database includes 3383 curated records with information on the species, or infraspecific taxa (including authority), and are fully georeferenced and provided with a confidence interval for the collection site. Taxonomy was first curated manually by in‐house botanists and then harmonized according to the Global Biodiversity Information Facility (GBIF) backbone taxonomy. The data are released under a Creative Commons Attribution Non Commercial (CC‐BY‐NC 4.0) license.

“Together is better”: the contribution of academy, citizen science and gray literature for the knowledge of the urban avifauna of a megadiverse easternmost Amazonian ecotonal border - Sara Miranda Almeida; Gustavo Gonsioroski; Nubia Carla Santos Marques; Fernanda Guimarães Fava; João Marcelo da Silva Abreu; Letícia Gomes da Silva; Rafaela Velloso Missagia; Vanessa Guimarães Lopes; Verônica Maria de Oliveira; Erick Cristofore Guimarães; Pedro Walfir M. Souza-Filho; Valéria da Cunha Tavares (Ornithology Research, 2025)

Evaluation of dried blood spots for serological surveys of myxoma and rabbit hemorrhagic disease viruses in their wild reservoir - Joana Ferreira-e-Silva; Saúl Jiménez-Ruiz; Marisa Rodrigues; Emídio Santos; Sabrina Castro-Scholten; Vitor Lizana; Alba Martí-Marco; Tereza Almeida; Ana M. Lopes; Joana Abrantes; Juan Bárcena; Esther Blanco; et al. (Preventive Veterinary Medicine, 2025)

Extraction, characterization, and use of edible insect oil – A review - Vanessa Aparecida Cruz; Carolina M. Vicentini-Polette; Danielle Rodrigues Magalhaes; Alessandra Lopes de Oliveira (Food Chemistry, 2025)

Conventional environmental assessments are inadequate for predicting and mitigating impacts of dams on migratory fish in Brazil: an integrative assessment approach for the Neotropics - J. M. Lopes; A. Peressin; F. R. de Andrade; M. F. Moreira; S. Ludwig; J. S. M. Pimentel; L. Wouters; I. G. Prado; F. M. Suzuki; C. B. M. Alves; P. S. Pompeu (Aquatic Sciences, 2025)

Retraction notice to “Cellulose microcrystalline: A promising ecofriendly approach to control Culex quinquefasciatus larvae” [STOTEN 901 (2023) 165952] - Sindoval Silva de Souza; Alex Rodrigues Gomes; Abraão Tiago Batista Guimarães; Aline Sueli de Lima Rodrigues; Letícia Paiva de Matos; Juliana dos Santos Mendonça; Thiarlen Marinho da Luz; Stênio Gonçalves da Silva Matos; M. Safiur Rahman; Chinnasamy Ragavendran; Sengottayan Senthil-Nathan; Ajay Guru; et al. (Science of The Total Environment, 2024)

Food macroalgae: scoping review of aspects related to research and consumption - Lara Juliane Guedes da Silva; Alice Medeiros Souza; Priscila F. M. Lopes; Michelle Cristine Medeiros Jacob (Journal of Applied Phycology, 2024)

Polymorphic pseudogenes in the human genome - a comprehensive assessment - Mónica Lopes-Marques; M. João Peixoto; David N. Cooper; M. João Prata; Luísa Azevedo; L. Filipe C. Castro (Human Genetics, 2024)
Background: Over the past decade, variations of the coding portion of the human genome have become increasingly evident. In this study, we focus on polymorphic pseudogenes, a unique and relatively unexplored type of pseudogene whose inactivating mutations have not yet been fixed in the human genome at the global population level. Thus, polymorphic pseudogenes are characterized by the presence in the population of both coding alleles and non-coding alleles originating from Loss-of-Function (LoF) mutations. These alleles can be found both in heterozygosity and in homozygosity in different human populations and thus represent pseudogenes that have not yet been fixed in the population. Results: A methodical cross-population analysis of 232 polymorphic pseudogenes, including 35 new examples, reveals that human olfactory signalling, drug metabolism and immunity are among the systems most impacted by the variable presence of LoF variants at high frequencies. Within this dataset, a total of 179 genes presented polymorphic LoF variants in all analysed populations. Transcriptome and proteome analysis confirmed that although these genes may harbour LoF alleles, when the coding allele is present, the gene remains active and can play a functional role in various metabolic pathways, including drug/xenobiotic metabolism and immunity. The observation that many polymorphic pseudogenes are members of multigene families argues that genetic redundancy may play a key role in compensating for the inactivation of one paralogue. Conclusions: The distribution, expression and integration of cellular/biological networks in relation to human polymorphic pseudogenes, provide novel insights into the architecture of the human genome and the dynamics of gene gain and loss with likely functional impact.

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Honey bee viruses in the yellow-legged hornet Vespa velutina (Lepelieter 1836): Prevalence, loads, and detection of replicative DWV and LSV forms - M. Shantal Rodríguez-Flores; Ana R. Lopes; Ana Diéguez-Antón; M Carmen Seijo; M. Alice Pinto (Journal of Invertebrate Pathology, 2024)

Nano-hydroxyapatite Pickering emulsions as edible mayonnaise-like food sauce templates: A novel approach for food design - Maria Eduarda Relvas; Larissa C. Ghirro; Isabel M. Martins; Jose Carlos B. Lopes; Madalena M. Dias; Maria Filomena Barreiro; Andreia Ribeiro (Journal of Food Engineering, 2024)

Nanoencapsulation of quinoa oil enhanced the antioxidant potential and inhibited digestive enzymes - Bruna Lorena Meneses Marques; Thaís Souza Passos; Alyne Ingrydid Dantas; Malu Andrade Alves de Lima; Susana Margarida Gomes Moreira; Victor M. Rodrigues; Marina R. do Nascimento Dantas; Patrícia Santos Lopes; Ana Paula Barreto Gomes; Rafael da Silva Fernandes; Francisco Humberto Xavier Júnior; Francisco Canindé de Sousa Júnior; et al. (Food Research International, 2024)

Inhibitors of gastric acid secretion increase oxidative stress and matrix metalloproteinase-2 activity leading to vascular remodeling - Renato C. Nogueira; Jéssica M. Sanches-lopes; Gustavo H. Oliveira-Paula; Jose E. Tanus-Santos (Molecular and Cellular Biochemistry, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Evaluation of NETmix geometrical properties on gas-liquid mass transfer performance - Paulo H. Marrocos; Isabel S. Fernandes; José C.B. Lopes; Madalena M. Dias; Ricardo J. Santos; Vítor J.P. Vilar (Journal of Environmental Chemical Engineering, 2024)

Selective electrochemical oxidation of organic compounds in a mass transfer-enhanced electrochemical flow reactor (eNETmix) - Clarissa H. Rosa; Daniela F.S. Morais; Gilber R. Rosa; João H.Z. dos Santos; José Carlos B. Lopes; Madalena M. Dias; Rosa Montes; Rosario Rodil; José Benito Quintana; Gabriel Antonio Cerrón-Calle; Sergi Garcia-Segura; Carlos J. Tavares; et al. (Journal of Environmental Chemical Engineering, 2024)

Yarrowia lipolytica growth, lipids, and protease production in medium with higher alkanes and alkenes - Sílvia M. Miranda; Isabel Belo; Marlene Lopes (World Journal of Microbiology and Biotechnology, 2024)
Two strains of Yarrowia lipolytica (CBS 2075 and DSM 8218) were first studied in bioreactor batch cultures, under different controlled dissolved oxygen concentrations (DOC), to assess their ability to assimilate aliphatic hydrocarbons (HC) as a carbon source in a mixture containing 2 g·L −1 of each alkane (dodecane and hexadecane), and 2 g·L −1 hexadecene. Both strains grew in the HC mixture without a lag phase, and for both strains, 30 % DOC was sufficient to reach the maximum values of biomass and lipids. To enhance lipid-rich biomass and enzyme production, a pulse fed-batch strategy was tested, for the first time, with the addition of one or three pulses of concentrated HC medium. The addition of three pulses of the HC mixture (total of 24 g·L −1 HC) did not hinder cell proliferation, and high protease (> 3000 U·L −1 ) and lipids concentrations of 3.4 g·L −1 and 4.3 g·L −1 were achieved in Y. lipolytica CBS 2075 and DSM 8218 cultures, respectively. Lipids from the CBS 2075 strain are rich in C16:0 and C18:1, resembling the composition of palm oil, considered suitable for the biodiesel industry. Lipids from the DSM 8218 strain were predominantly composed of C16:0 and C16:1, the latter being a valuable monounsaturated fatty acid used in the pharmaceutical industry. Y. lipolytica cells exhibited high intrinsic surface hydrophobicity (> 69 %), which increased in the presence of HC. A reduction in surface tension was observed in both Y. lipolytica cultures, suggesting the production of extracellular biosurfactants, even at low amounts. This study marks a significant advancement in the valorization of HC for producing high-value products by exploring the hydrophobic compounds metabolism of Y. lipolytica .

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Correction: Synopsis of the European Freshwater Mussels: Pseudunio auricularius (Spengler, 1793), the Giant Freshwater Pearl Mussel - Keiko Nakamura; Karl M. Wantzen; Joaquin Soler; Ronaldo Sousa; Karl-Otto Nagel; David C. Aldridge; Manuel Lopes-Lima; Vincent Prié (Hydrobiologia, 2024)

Enhancing multi-mode transport emission inventories: Combining open-source data with traditional approaches - D. Lopes; M. Rosa; D. Graça; S. Rafael; J. Ferreira; M. Lopes (Urban Climate, 2024)

Evaluation of behavioral and neurochemical changes induced by carbofuran in zebrafish (Danio rerio) - Giovana R. Oliveira; Matheus Gallas-Lopes; Rafael Chitolina; Leonardo M. Bastos; Stefani M. Portela; Thailana Stahlhofer-Buss; Darlan Gusso; Rosane Gomez; Angela T.S. Wyse; Ana P. Herrmann; Angelo Piato (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

CO2 methanation under more realistic conditions: Influence of O2 and H2O on Ni-based catalysts’ performance - Daniela Spataru; Gilda Carvalho; Adrián Quindimil; José M. Lopes; Carlos Henriques; Carmen Bacariza (Chemical Engineering Journal, 2024)

The study of galactomannans with different molecular weights and their ability to form microparticles suitable for pulmonary delivery - Miguel F. Galrinho; Lisete M. Silva; Guido R. Lopes; Bernardo A.C. Ferreira; Sara A. Valente; Isabel Ferreira; Benedita A. Pinheiro; Angelina S. Palma; Dmitry V. Evtuguin; José A. Lopes da Silva; Margarida Almeida; Paula Ferreira; et al. (Carbohydrate Polymers, 2024)

The Effect of Ultrasound Waves on the Pre-Settlement Behavior of Barnacle Cyprid Larvae - Rubens M. Lopes; Claudia Guimarães; Felipe M. Neves; Leandro T. De-La-Cruz; Gelaysi Moreno Vega; Damián Mizrahi; Julio Cesar Adamowski (Journal of Marine Science and Engineering, 2024)
Ultrasound waves have been employed to control marine biofouling but their effects on fouling organisms remain poorly understood. This study investigated the influence of ultrasound waves on barnacle (Tetraclita stalactifera cyprid larvae) pre-settlement behavior. Substrate inspection constituted most of the larval time budget, with a focus on the bottom surface rather than lateral or air–water interfaces. The frequency of substrate inspection decreased at 10 kPa when compared to higher acoustic pressures, while the time spent in the water column had an opposite trend. Various larval swimming modes were observed, including rotating, sinking, walking, and cruising, with rotating being dominant. Barnacle larvae exhibited higher speeds and less complex trajectories when subjected to ultrasound in comparison to controls. The impact of ultrasound waves on barnacle cyprid larvae behavior had a non-linear pattern, with lower acoustic pressure (10 kPa) inducing more effective substrate rejection than higher (15 and 20 kPa) intensities.

Lumpfish physiological response to chronic stress - Tiago da Santa Lopes; Benjamin Costas; Lourenço Ramos-Pinto; Patrick Reynolds; Albert K. D. Imsland; Cláudia Aragão; Jorge M. O. Fernandes (Frontiers in Marine Science, 2024)
In this study, we explored the effects of chronic stress on lumpfish ( Cyclopterus lumpus ) physiological, immune response, health, and plasma free amino acids. 3 groups of lumpfish were exposed to 1-minute air exposure. 1 group was exposed to stress once per week, a second group exposed 2 times per week, and a third group exposed 4 times per week. The present study revealed significant alterations in immunity and increased nutritional demands, particularly the branched chain amino acids and lysine. Cortisol levels fluctuated, with significantly higher levels halfway through the experiment on the groups that were stressed more often. Though, by the end of the experiment, there were no significant differences in cortisol levels between groups. Regardless of stress exposure, cataract developed in virtually all sampled fish, pointing toward a potential dietary imbalance. A transient immunomodulation of stress was visible. While in early stages stress had an immune enhancing effect, as seen by the increase in plasma nitric oxide and peroxidase in the group most frequently exposed to stress, these differences were not apparent by the end of the experiment. Additionally, the worst health condition was found in this group. Our results underscore the complex interplay between stress, immunity and nutrition, highlighting the need for tailored dietary strategies and improved rearing practices.

Application of remote sensing methods for monitoring extent, condition and blue carbon storage in salt marshes - Angelina Freitas; João M. Dias; Carina L. Lopes (Remote Sensing Applications: Society and Environment, 2024)

Clinical Characterization and Underlying Genetic Findings in Brazilian Patients with Syndromic Microcephaly Associated with Neurodevelopmental Disorders - Giovanna Cantini Tolezano; Giovanna Civitate Bastos; Silvia Souza da Costa; Marília de Oliveira Scliar; Carolina Fischinger Moura de Souza; Hélio Van Der Linden Jr; Walter Luiz Magalhães Fernandes; Paulo Alberto Otto; Angela M. Vianna-Morgante; Luciana Amaral Haddad; Rachel Sayuri Honjo; Guilherme Lopes Yamamoto; et al. (Molecular Neurobiology, 2024)

Synopsis of the European Freshwater Mussels: Pseudunio auricularius (Spengler, 1793), the Giant Freshwater Pearl Mussel - Keiko Nakamura; Karl M. Wantzen; Joaquin Soler; Ronaldo Sousa; Karl-Otto Nagel; David C. Aldridge; Manuel Lopes-Lima; Vincent Prié (Hydrobiologia, 2024)

Integrated behavioural and physiological responses of sand smelt larvae to the effects of warming and hypoxia as combined stressors - André R.A. Lima; Ana Rita Lopes; Sara Martins-Cardoso; Ariana B. Moutinho; Marco F.L. Lemos; Sara C. Novais; Ana M. Faria (Marine Environmental Research, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Movement Behavior of the Dusky Grouper Epinephelus marginatus (Lowe, 1834) in Early Life Stages - Cássia Gongora Goçalo; Rubens M. Lopes (Journal of Marine Science and Engineering, 2024)
The dusky grouper (Epinephelus marginatus) is a vulnerable predatory fish found in the Atlantic and Indian oceans, and in the Mediterranean Sea. This study investigates the movement patterns of grouper larvae (151 individuals) during their first feeding period (three to ten days post hatching) through laboratory experiments offering rotifers (Brachionus sp.) and copepod nauplii as food. High-speed cameras and imaging techniques including bright field microscopy, matched filters, and holography captured rapid displacements (up to 25 body lengths per second), peduncle caudal beats (up to 40 beats s−1), turns, and resting periods. Reynolds numbers ranged from

Integrative phylogenetic, phylogeographic and morphological characterisation of the Unio crassus species complex reveals cryptic diversity with important conservation implications - M. Lopes-Lima; J. Geist; S. Egg; L. Beran; A. Bikashvili; B. Van Bocxlaer; A.E. Bogan; I.N. Bolotov; O.A. Chelpanovskaya; K. Douda; V. Fernandes; A. Gomes-dos-Santos; et al. (Molecular Phylogenetics and Evolution, 2024)

Possible plant-based solutions for skin yeast infections - Ana I. Lopes; Maria M. Pintado; Freni K. Tavaria (Fungal Biology Reviews, 2024)

Obesity and polycystic ovary syndrome influence on intestinal permeability at fasting, and modify the effect of diverse macronutrients on the gut barrier - M.Ángeles Martínez-García; Alejandra Quintero-Tobar; Sara de Lope Quiñones; María Insenser; Elena Fernández-Durán; Héctor Francisco Escobar-Morreale; Manuel Luque-Ramírez (Food Research International, 2024)

Correction to: Regulation of TrkB receptor translocation to lipid rafts by adenosine A2A receptors and its functional implications for BDNF-induced regulation of synaptic plasticity - Natália Assaife-Lopes; Vasco C. Sousa; Daniela B. Pereira; Joaquim A. Ribeiro; Ana M. Sebastião (Purinergic Signalling, 2024)

A remote sensing assessment of oak forest recovery after postfire restoration - L. F. Lopes; F. S. Dias; P. M. Fernandes; V. Acácio (European Journal of Forest Research, 2024)
Mediterranean Europe is experiencing a rise in severe wildfires, resulting in growing socioeconomic and ecological impacts. Postfire restoration has become a crucial approach to mitigate these impacts and promote ecosystem recovery. However, the ecological effects of such interventions are still not well understood. We employed remote sensing techniques to evaluate the impact of postfire emergency stabilization on the recovery of deciduous oak forests in Portugal. Our study encompassed 3013 sampling points located in areas with and without postfire interventions. We chose the Normalized Difference Vegetation Index (NDVI) as an indicator of oak forest recovery over a four-year period following wildfires that took place in 2016 and 2017. We used a Generalized Additive Mixed Model (GAMM) to assess how NDVI changed over time as a function of postfire restoration, fire characteristics, topography, and postfire drought events. We found that postfire restoration had a significant positive effect on NDVI recovery over time, although this effect was small. Severe drought and fire recurrence up to six fires had a negative effect on the recovery of NDVI. Conversely, severe wetness and either low or high burn severities had a positive effect on recovery. Our study emphasizes the importance of monitoring postfire restoration effects on forest recovery to guide restoration planning and improve forest management in burned areas. This becomes even more relevant under increased wildfire severity predicted for the Mediterranean region interacting with other climate-driven disturbances, which will further negatively affect forest recovery.

Freezing and thawing in Antarctica: characterization of antifreeze protein (AFP) producing microorganisms isolated from King George Island, Antarctica - J. C. Lopes; V. P. Veiga; B. Seminiuk; L. O. F. Santos; A. M. C. Luiz; C. A. Fernandes; C. T. Kinasz; V. H. Pellizari; R. T. D. Duarte (Brazilian Journal of Microbiology, 2024)

Integrating fishers’ knowledge on fish use with ecological networks to assess the ‘silent threat’ of mercury contamination in tropical marine and freshwater fisheries - Paula Evelyn Rubira Pereyra; Andrés Ospina‑Alvarez; Márcia Caroline Friedl Dutra; Bárbara Heck Schallenberger; Gustavo Hallwass; Alpina Begossi; Mariana Clauzet; Priscila F. M. Lopes; Renato Azevedo Matias Silvano (Environment, Development and Sustainability, 2024)

Sleep deprivation induces late deleterious effects in a pharmacological model of Parkinsonism - L. B. Lopes-Silva; D. M. G. Cunha; A. C. Lima; V. S. Bioni; N. Gonçalves; J. P. F. Kurita; R. Wuo-Silva; R. H. Silva (Experimental Brain Research, 2024)

Sodium bicarbonate induces alkalosis, but improves high-intensity cycling performance only when participants expect a beneficial effect: a placebo and nocebo study - Alessandro Moura Zagatto; Vithor Hugo Fialho Lopes; Yago Medeiros Dutra; Rodrigo Araujo Bonetti de Poli; Eimear Dolan; Letizia Rasica; Juan M. Murias; Paulo Henrique Silva Marques de Azevedo (European Journal of Applied Physiology, 2024)

Atmospheric environments associated with tornadoes in southern Brazil and neighboring areas as compared to other modes of convective hazards - Murilo M. Lopes; Ernani L. Nascimento (Climate Dynamics, 2024)

Pressurized liquid extraction assisted by high-intensity ultrasound to obtain hesperidin from lime waste: Integration of in-line purification and on-line chromatographic analysis - Vitor L. Sanches; Monique Martins Strieder; Marcia Cristina Breitkreitz; Rosângela Maria Neves Bezerra; Jaísa O. Chaves; Isadora Lopes de Oliveira; Leonardo M. de Souza Mesquita; Juliane Viganó; Letícia Sanches Contieri; Rodrigo Stein Pizani; Maurício A. Rostagno (Food Research International, 2024)

Horizontal migration of zooplankton in lake–wetland interfaces. Can temperature-driven surface exchange flows modulate its patterns? - Joana Luísa Pereira; Ana Sofia Lopes; Júlia Silva; Tânia Vidal; Nelson Abrantes; Daniela Santos; Moisés Brito; Rui M. L. Ferreira; Fernando J. M. Gonçalves; Ana Margarida Ricardo (Aquatic Sciences, 2024)
Lake ecology can be affected by exchange flows driven by horizontal temperature gradients in lake–wetland interfaces. In this work, we investigate the hypothesis that thermally driven flows modulate the horizontal migration patterns of freshwater zooplankters. A 48-h field campaign in a shallow lake (Lake Vela, Quiaios, Portugal) was carried out to test this hypothesis. Thermal differences between the littoral and limnetic areas were measured along two transects featuring a Schoenoplectus lacustris and a Myriophyllum aquaticum stand in the littoral. In parallel, the physiochemistry and chlorophyll a, as a proxy for food availability differences between the littoral and the limnetic zones, were monitored. Zooplankton samples were collected for assessing overall and group-specific number-density differences. The diel period (day or night) and the site (littoral or limnetic zone) did not interact significantly to modulate the variation patterns for the studied physiochemical variables, indicating that these parameters should not explain horizontal zooplankton distribution patterns. The expected patterns for zooplankton diel horizontal migration as driven by the presence of visual predators were occasionally confirmed by our limnetic versus littoral abundance records through time, depending on the transect. Group-specific abundance patterns indicate particular features: copepods always preferred the littoral over the limnetic zone regardless of the diel period; chydorids always preferred the littoral zone regardless of the macrophyte stand involved; bosminids tended to preferentially concentrate in the limnetic zone. No consistent relationship was identified between the expected flow direction due to temperature differences and zooplankton abundance changes, although it occasionally occurred through the dataset.

Stretch-Induced Injury Affects Cortical Neuronal Networks in a Time- and Severity-Dependent Manner - Dylan Sullivan; Brandon J. Vaglio; Marina M. Cararo-Lopes; Ruben D. Ponce Wong; Oliver Graudejus; Bonnie L. Firestein (Annals of Biomedical Engineering, 2024)

Paleontological study of the Oligocene/Miocene boundary in the Ilha de Santana and Pirabas formations, Pará-Maranhão Basin on the Northwest equatorial platform of Brazil - Beatriz Teixeira Guimarães; Orangel Aguilera; Ana Paula Linhares; Olga M. Oliveira de Araújo; Isadora Mello; Hilton Tulio Costi; Dayana Alvarado Sierra; Vinicius Kutter; Daniel Lima; Geize Carolinne Correia Andrade Oliveira; Ricardo Lopes (Journal of South American Earth Sciences, 2024)

Environmental DNA survey does not detect additional populations of a critically endangered leaf frog, but reveal another threat to the species - Julia R. Ernetti; Carla Martins Lopes; Luisa P. Ribeiro; Veluma I.M. De Bastiani; Elaine M. Lucas; Luís Felipe Toledo (Journal for Nature Conservation, 2024)

Complexities of reef fisheries in Brazil: a retrospective and functional approach - Linda Eggertsen; André L. Luza; César A. M. M. Cordeiro; Cristian Dambros; Carlos E. L. Ferreira; Sergio R. Floeter; Ronaldo B. Francini-Filho; Kátia M. F. Freire; Maria A. Gasalla; Tommaso Giarrizzo; Vinicius J. Giglio; Natalia Hanazaki; et al. (Reviews in Fish Biology and Fisheries, 2024)

West Atlantic coastal marine biodiversity: the contribution of the platform iNaturalist - R. M. Rocha; F. Azevedo; U. Oliveira; M. N. M. Cardoso; P. H. B. Clerier; R. R. Fortes; E. A. P. Lopes-Filho; M. L. Lorini; L. S. Miranda; R. B. Moura; A. R. Senna; F. M. Silva; et al. (Aquatic Ecology, 2024)

Phosphorus removal from urban wastewater through adsorption using biogenic calcium carbonate - Andreia F. Santos; Daniela V. Lopes; Paula Alvarenga; Licínio M. Gando-Ferreira; Margarida J. Quina (Journal of Environmental Management, 2024)

e–NETmix: A pioneering electrochemical flow reactor with enhanced mass transfer - Daniela F.S. Morais; José Carlos B. Lopes; Madalena M. Dias; Vítor J.P. Vilar; Francisca C. Moreira (Chemical Engineering Journal, 2024)

Droplet size and hydraulic spray nozzles in peanut plant spray deposition - Gabriela G. P. Buosi; Arthur D. R. Neto; Paulo R. M. Lopes; Samuel Ferrari; Júlio C. Guerreiro; Pedro J. F. Filho; Ronaldo C. Lima; Vagner Nascimento; Marina Funichello; Carlos G. Raetano; Evandro P. Prado (Journal of Plant Diseases and Protection, 2024)

Cardioprotective Effects of Leucine Supplementation against Doxorubicin-Induced Cardiotoxicity - Lucas C. Guimarães; Thiago M. Fidale; Talita C. R. Pereira; Paulo R. Lopes; Marcos D. Ferreira-Junior; Simone R. Deconte; Marcos L. Ferreira-Neto; Willams S. Brito; Rodrigo M. Gomes; Fernanda R. de Souza; Keilah V. N. Cavalcante; Gustavo C. Herrera; et al. (Cardiovascular Toxicology, 2024)

Toxicity of carbon nanofibers in earthworms (Lumbricus terrestris) naturally infected with Monocystis sp. - Mateus Flores Montalvão; Alex Rodrigues Gomes; Abraão Tiago Batista Guimarães; Aline Sueli de Lima Rodrigues; Letícia Paiva de Matos; Juliana dos Santos Mendonça; Thiarlen Marinho da Luz; Stênio Gonçalves da Silva Matos; M. Safiur Rahman; Chinnasamy Ragavendran; Sengottayan Senthil-Nathan; Ajay Guru; et al. (Science of The Total Environment, 2024)

Functional leaf-trait variability and herbivory in oaks along a Mexican avocado agrosystem mosaic - Marcela Sofía Vaca-Sánchez; Mário M. Espírito-Santo; Yurixhi Maldonado-López; Ken Oyama; Abel Pérez-Solache; Maurício Lopes de Faria; Magno Augusto Zazá Borges; G. Wilson Fernandes; Pablo Cuevas-Reyes (Flora, 2024)

Early life stage mechanisms of an active fish species to cope with ocean warming and hypoxia as interacting stressors - André R.A. Lima; Emily M. Booms; Ana Rita Lopes; Sara Martins-Cardoso; Sara C. Novais; Marco F.L. Lemos; Laura Ribeiro; Sara Castanho; Ana Candeias-Mendes; Pedro Pousão-Ferreira; Ana M. Faria (Environmental Pollution, 2024)

Recyclable liquid metal – Graphene supercapacitor - Afsaneh L. Sanati; Pedro Alhais Lopes; Alexandre Chambel; André F. Silva; Diogo M. Oliveira; Carmel Majidi; Anibal T. de Almeida; Mahmoud Tavakoli (Chemical Engineering Journal, 2024)

Enhancing the taxonomic delimitation of Lippia origanoides Kunth (Verbenaceae) by analyzing volatile terpenes and molecular markers in micropropagated accessions - Laís M. Frattini; Arthur A. Oliveira; Jhoão S. Kotsubo; Íris B. Gorne; Isabel C. Silva; Jober C. E. Freitas; Cristiano F. Resende; Ana C. Mezzonato-Pires; Elyabe M. Matos; Juliana M. L. Lopes; Lyderson F. Viccini; Richard M. Grazul; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Octopus crawling on land: physiological and biochemical responses of Octopus vulgaris to emersion - Janina Leonie Röckner; Vanessa M. Lopes; José Ricardo Paula; Maria Rita Pegado; Martim Costa Seco; Mário Diniz; Tiago Repolho; Rui Rosa (Marine Biology, 2024)

Lipidomic fingerprinting of the red seaweed Asparagopsis spp. evidencing specific profiling in gametophyte and tetrasporophyte life stages - Diana Lopes; Felisa Rey; Tânia Melo; Marisa Pinho; Ana S.P. Moreira; Katia Pes; Leonardo Mata; M. Rosário Domingues (Algal Research, 2024)

Groundwater is a hidden global keystone ecosystem - Mattia Saccò; Stefano Mammola; Florian Altermatt; Roman Alther; Rossano Bolpagni; Anton Brancelj; David Brankovits; Cene Fišer; Vasilis Gerovasileiou; Christian Griebler; Simone Guareschi; Grant C. Hose; et al. (Global Change Biology, 2024)
Groundwater is a vital ecosystem of the global water cycle, hosting unique biodiversity and providing essential services to societies. Despite being the largest unfrozen freshwater resource, in a period of depletion by extraction and pollution, groundwater environments have been repeatedly overlooked in global biodiversity conservation agendas. Disregarding the importance of groundwater as an ecosystem ignores its critical role in preserving surface biomes. To foster timely global conservation of groundwater, we propose elevating the concept of keystone species into the realm of ecosystems, claiming groundwater as a keystone ecosystem that influences the integrity of many dependent ecosystems. Our global analysis shows that over half of land surface areas (52.6%) has a medium‐to‐high interaction with groundwater, reaching up to 74.9% when deserts and high mountains are excluded. We postulate that the intrinsic transboundary features of groundwater are critical for shifting perspectives towards more holistic approaches in aquatic ecology and beyond. Furthermore, we propose eight key themes to develop a science‐policy integrated groundwater conservation agenda. Given ecosystems above and below the ground intersect at many levels, considering groundwater as an essential component of planetary health is pivotal to reduce biodiversity loss and buffer against climate change.

Impacts of acute hypoxia on the short-snouted seahorse metabolism and behaviour - Matilde Gomes; Vanessa M. Lopes; Monica G. Mai; José R. Paula; Regina Bispo; Hugo Batista; Catarina Barraca; Núria Baylina; Rui Rosa; Marta S. Pimentel (Science of The Total Environment, 2023)

The cost of living in Notosuchia (Crocodyliformes, Mesoeucrocodylia) - Mariana Valéria de Araújo Sena; Felipe C. Montefeltro; Thiago S. Marinho; Max C. Langer; Thiago S. Fachini; André E. Piacentini Pinheiro; Alessandra S. Machado; Ricardo T. Lopes; Romain Pellarin; Juliana M. Sayão; Gustavo R. Oliveira; Jorge Cubo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Characterization and predictors of the zooplankton community in the Veredas wetlands in Brazilian savanna - Vanessa Guimarães Lopes; Rosângela Gama Strutz; Luciano B. Lima; Cleide Carnicer; Fagner Junior M. Oliveira; Dilermando Pereira Lima-Junior (Wetlands Ecology and Management, 2023)

Biological properties and potential of compounds extracted from red seaweeds - M. Carpena; P. Garcia-Perez; P. Garcia-Oliveira; F. Chamorro; Paz Otero; C. Lourenço-Lopes; Hui Cao; J. Simal-Gandara; M. A. Prieto (Phytochemistry Reviews, 2023)
Macroalgae have been recently used for different applications in the food, cosmetic and pharmaceutical industry since they do not compete for land and freshwater against other resources. Moreover, they have been highlighted as a potential source of bioactive compounds. Red algae (Rhodophyta) are the largest group of seaweeds, including around 6000 different species, thus it can be hypothesized that they are a potential source of bioactive compounds. Sulfated polysaccharides, mainly agar and carrageenans, are the most relevant and exploited compounds of red algae. Other potential molecules are essential fatty acids, phycobiliproteins, vitamins, minerals, and other secondary metabolites. All these compounds have been demonstrated to exert several biological activities, among which antioxidant, anti-inflammatory, antitumor, and antimicrobial properties can be highlighted. Nevertheless, these properties need to be further tested on in vivo experiments and go in-depth in the study of the mechanism of action of the specific molecules and the understanding of the structure–activity relation. At last, the extraction technologies are essential for the correct isolation of the molecules, in a cost-effective way, to facilitate the scale-up of the processes and their further application by the industry. This manuscript is aimed at describing the fundamental composition of red algae and their most studied biological properties to pave the way to the utilization of this underused resource.

Correction to: Using commercial high-resolution satellite imagery to monitor a nuisance macroalga in the largest marine protected area in the USA - Kauaoa M. S. Fraiola; Tomoaki Miura; Jonathan Martinez; Keolohilani H. Lopes; Fred Amidon; Juan Torres-Pérez; Heather L. Spalding; Taylor Williams; Khemarith So; Elyse Sachs; Randall K. Kosaki (Coral Reefs, 2023)

Small shrubby patches increase bird taxonomic and functional richness of wood-pastures - Paula C. Lopes; Jorge M. Palmeirim; Ana I. Leal (Agroforestry Systems, 2023)
Wood-pastures are semi-natural systems that combine a grazed grassland with a tree layer. Shrubs are often controlled, mostly to improve grazing potential, resulting in a reduction of the available ecological niches. From a conservation perspective, it is thus important to identify management practices that counter this reduction. Our overall objective was to determine the value of small shrubby patches to increase the richness of wood-pasture bird communities. As study model we used Mediterranean oak wood-pastures in southern Portugal, locally known as montados . Birds and environmental variables were sampled in 50 m radius plots of wood-pasture with and without small shrubby patches (128–3748 m 2 , covering less than 0.5% of the study area), in winter (n = 54) and spring (n = 65). Species assemblages’ composition changed between seasons, but in both seasons the assemblages in plots with and without patches were statistically different. Seven species were statistically associated to the presence of patches, in winter and spring, increasing the richness of the respective assemblages. A comparison of the functional composition of communities of patches and matrix revealed that patches increased richness of landscapes by boosting the presence of species with functional traits uncommon in the ecologically simplified matrix. Their presence is promoted by resources added by the patches (e.g. nesting sites, protection, food), but the ranges of individual birds in general extended well beyond the patches. This study demonstrated that the presence of few and small shrubby patches can significantly enrich the bird communities of wood-pastures, both taxonomically and functionally, indicating that promoting them is a cost-effective management measure for these valuable systems.

Microplastic distribution in different tissues of small pelagic fish of the Northeast Atlantic Ocean - Clara Lopes; Ana C. Ambrosino; Cátia Figueiredo; Miguel Caetano; Miguel M. Santos; Susana Garrido; Joana Raimundo (Science of The Total Environment, 2023)

RETRACTED: Cellulose microcrystalline: A promising ecofriendly approach to control Culex quinquefasciatus larvae - Sindoval Silva de Souza; Alex Rodrigues Gomes; Abraão Tiago Batista Guimarães; Aline Sueli de Lima Rodrigues; Letícia Paiva de Matos; Juliana dos Santos Mendonça; Thiarlen Marinho da Luz; Stênio Gonçalves da Silva Matos; M. Safiur Rahman; Chinnasamy Ragavendran; Sengottayan Senthil-Nathan; Ajay Guru; et al. (Science of The Total Environment, 2023)

Insights on the combination of off-line and on-line measurement approaches for source apportionment studies - Alice C. Forello; Inés Cunha-Lopes; Susana M. Almeida; Célia A. Alves; Oxana Tchepel; Federica Crova; Roberta Vecchi (Science of The Total Environment, 2023)

A meta-regression analysis of environmental sustainability practices and firm performance - Elisabete Nogueira; Sofia Gomes; João M. Lopes (Journal of Cleaner Production, 2023)

An exploratory approach to estimate point emission sources - D. Lopes; D. Graça; S. Rafael; M. Rosa; H. Relvas; J. Ferreira; J. Reis; M. Lopes (Atmospheric Environment, 2023)

Sun coral larval release following mechanical removal: a 2-year study on the southeast Brazilian coast - Damián Mizrahi; Alessandra C. S. Gomes; Milena C. da Silva; Rubens M. Lopes (Marine Biology, 2023)

Global patterns in sandy beach erosion: unraveling the roles of anthropogenic, climatic and morphodynamic factors - Fabio Bozzeda; Leonardo Ortega; Leonardo Lopes Costa; Lucia Fanini; Carlos A. M. Barboza; Anton McLachlan; Omar Defeo (Frontiers in Marine Science, 2023)
Beach erosion is a complex process influenced by multiple factors operating at different spatial scales. Local (e.g., waves, tides, grain size, beach width and coastal development) and regional (e.g., sea level rise and mean sea level pressure) factors both shape erosion processes. A comprehensive understanding of how these drivers collectively impact sandy beach erosion is needed. To address this on a global-scale we assembled a database with in-situ information on key physical variables from 315 sandy beaches covering a wide morphodynamic range and complemented by satellite data on regional variables. Our results revealed the combined influence of local and regional factors on beach erosion rates. Primary drivers were regional anomalies in mean sea level pressure and variations in mean sea level, and local factors such as tide range, beach slope and width, and Dean’s parameter. By analyzing morphodynamic characteristics, we identified five distinct clusters of sandy beaches ranging from wave-dominated microtidal reflective beaches to tide-modified ultradissipative beaches. This energy dissipation gradient emerged as a critical factor, with erosion rates increasing with beach width and dissipativeness. Our study also highlighted the tangible impact of climate change on beach erosion patterns. Hotspots were identified, where intensification of regional anomalies in mean sea level pressure, increasing onshore winds and warming rates, and rising sea levels synergistically accelerated erosion rates. However, local variables were found to either amplify the effects of regional factors on erosion or enhance a beach’s resistance, mitigating erosive trends initiated by regional drivers. Our analysis showed that more than one-fifth of the analyzed beaches are experiencing intense, extreme, or severe erosion rates, and highlighted the significant role of human activities in explaining erosion trends, particularly in microtidal reflective and intermediate beaches. This underscores the long-term threat of coastal squeeze faced by sandy beaches worldwide and emphasizes the need to consider both local and regional drivers in order to understand erosion processes. Integrating localized measurements with broader satellite observations is required for a comprehensive understanding of the main drivers behind coastal evolution, which in turn is needed to manage and preserve these fragile ecosystems that are at risk.

Green to gold: consumer circular choices may boost circular business models - João M. Lopes; Micaela Pinho; Sofia Gomes (Environment, Development and Sustainability, 2023)
Consumers are the true agents of transformation in the circular economy. By making conscious and sustainable choices, they drive the development of circular business models, challenging the status quo and inspiring change for a more sustainable future. The main purpose of this paper is to assess the role of consumers in the circular economy as drivers of the development of circular business models. In detail, we explore whether Portuguese citizens make circular consumption choices and what factors influence these choices. An online questionnaire was used to collect data from a sample of 826 Portuguese. The quantitative analysis was performed using the Partial Least Square (PLS) method. Overall, we found that: (i) both pro-environmental habits and environmental concerns positively influence their circular consumption choices, (ii) pro-environmental habits positively influence consumers’ greenwashing perception, and (iii) greenwashing perception highlights environmental concerns. This study demonstrates that by adopting pro-environmental habits, consumers can play a central role in transforming companies’ traditional business models into circular business models. Consequently, a model is proposed where consumers’ motivations for adopting circular behaviors are used to convert the companies’ business model from linear to circular. The model emphasizes the active participation of consumers.

Tarballs on the Brazilian coast in late 2022 sustain Lepas anatifera Linnaeus, 1758 (Crustacea: Cirripedia): Occurrence and risk of petroleum hydrocarbon ingestion - Luiza C. Mello; Adriana P. Nascimento; Beatriz D. Lopes; Antônia D.F. Lima; Luís E.A. Bezerra; Liana de F. Mendes; Luciana M. Bastos; Arlene B.S. Nossol; Mário M. Martins; Laercio L. Martins; Rivelino M. Cavalcante (Science of The Total Environment, 2023)

Cenozoic biostratigraphy of larger foraminifera from equatorial carbonate platform of northwestern Brazil - Dayana Alvarado Sierra; Orangel Aguilera; Olga M. Oliveira de Araújo; Ricardo Tadeu Lopes; Mauro Geraldes; Maria Virginia Alves Martins; Giovanni Coletti; Beatriz Teixeira Guimarães; Ana Paula Linhares; Vinicius Tavares Kütter (Marine and Petroleum Geology, 2023)

Effects of processing technologies on the antioxidant properties of common bean (Phaseolus vulgaris L.) and lentil (Lens culinaris) proteins and their hydrolysates - Caroline Lopes; Cláudia Akel Ferruccio; Anne Caroline de Albuquerque Sales; Guilherme M. Tavares; Ruann Janser Soares de Castro (Food Research International, 2023)

On the path to improve lignin depolymerization and functionalization into bio-based platform chemicals: A short review - André M. da Costa Lopes; Armando J.D. Silvestre; João A.P. Coutinho (Current Opinion in Green and Sustainable Chemistry, 2023)

Treatment of wastewater for reuse using advanced oxidation process: a bacterial inactivation mechanism approach - R. O. Ramos; W. S. Lopes; Y. H. D. M. Luna; M. V. da C. Albuquerque; V. D. Leite; J. T. de Sousa; M. C. U. Araújo; W. S. Lopes (International Journal of Environmental Science and Technology, 2023)

P20-11: Thalassophryne nattereri peptide (TnP) and the Aryl hydrocarbon receptor (Ahr): intertwined regulation of zebrafish inflammatory response - G.R. Disner; E. Wincent; C. Lima; M. Lopes-Ferreira (Toxicology Letters, 2023)

First evidence of microplastic ingestion in the ocean giant sunfish (Mola mola) - Clara Lopes; Cátia Figueiredo; Miguel Baptista; Miguel Caetano; Miguel M. Santos; Joana Raimundo (Marine Environmental Research, 2023)

The silent extinction of freshwater mussels in Portugal - Manuel Lopes-Lima; Joaquim Reis; Maria G. Alvarez; Pedro M. Anastácio; Filipe Banha; Pedro Beja; Paulo Castro; Mafalda Gama; Maria G. Gil; André Gomes-dos-Santos; Fernando Miranda; Joana Garrido Nogueira; et al. (Biological Conservation, 2023)

Adaptive factors and strategies in small-scale fisheries economies - Ludmila M. A. Damasio; Maria Grazia Pennino; Sebastián Villasante; Adriana Rosa Carvalho; Priscila F. M. Lopes (Reviews in Fish Biology and Fisheries, 2023)

Morphological and Genetic Variation Among Callithrix Hybrids in Rio de Janeiro, Brazil - A. M. Cezar; G. S. Lopes; S. S. Cardim; C. Bueno; M. Weksler; J. A. Oliveira (Evolutionary Biology, 2023)

Multiple Stool Sampling and Specific Parasitological Technique are Crucial to Diagnose Strongyloidiasis in Alcoholic Patients - Alana A. S. Gonçalves; Camila A. Lopes; Marcelo A. Levenhagen; Henrique T. Gonzaga; Luiz Carlos M. Oliveira; Julia Maria Costa-Cruz (Acta Parasitologica, 2023)

Ticking time bombs: The MENA and SSA regions' geopolitical risks - João J. Ferreira; Sofia Gomes; João M. Lopes; Justin Z. Zhang (Resources Policy, 2023)

Miocene tropical storms: Carbonate framework approaches and geochemistry proxies in a reservoir model - Orangel Aguilera; Olga M. Oliveira De Araújo; Ricardo Tadeu Lopes; Marcelo Cohen; Dayana Alvarado Sierra; Beatriz Teixeira Guimarães; Ana Paula Linhares; Félix Rodriguez; Manuel Moreira; Rut Díaz; Hamilton Santos Gama Filho; Marcelino Jose Dos Anjos; et al. (Marine and Petroleum Geology, 2023)

Starch-based films doped with porphyrinoid photosensitizers for active skin wound healing - Paloma Lopes; A. Sofia M. Joaquinito; Artur Ribeiro; Nuno M.M. Moura; Ana T.P. Gomes; Susana G. Guerreiro; M. Amparo F. Faustino; Adelaide Almeida; Paula Ferreira; Manuel A. Coimbra; M. Graça P.M.S. Neves; Idalina Gonçalves (Carbohydrate Polymers, 2023)

Chemical speciation of PM emissions from heavy-duty vehicles - I. Cunha-Lopes; K. Lehtoranta; S.M. Almeida; M. Evtyugina; A. Vicente; E. Vicente; H. Kuutti; F. Amato; C.A. Alves (Atmospheric Environment, 2023)

Effect of the racial group and body condition score at calving on production performance and metabolic profile of buffaloes during the transition period - R. D. G.e Silva; M. V. G. Loiola; A. L. Ribeiro Filho; D. C. Cotrim; B. S. dos Santos Rekowsky; I. M. S. Lopes; L. F. de A. Bulcão; M. L. G. M. L. de Araújo; D. dos S. Pina; G. G. P. de Carvalho; J. E. de Freitas (Tropical Animal Health and Production, 2023)

Computational Oil-Slick Hub for Offshore Petroleum Studies - Nelson F. F. Ebecken; Fernando Pellon de Miranda; Luiz Landau; Carlos Beisl; Patrícia M. Silva; Gerson Cunha; Maria Célia Santos Lopes; Lucas Moreira Dias; Gustavo de Araújo Carvalho (Journal of Marine Science and Engineering, 2023)
The paper introduces the Oil-Slick Hub (OSH), a computational platform to facilitate the data visualization of a large database of petroleum signatures observed on the surface of the ocean with synthetic aperture radar (SAR) measurements. This Internet platform offers an information search and retrieval system of a database resulting from >20 years of scientific projects that interpreted ~15 thousand offshore mineral oil “slicks”: natural oil “seeps” versus operational oil “spills”. Such a Digital Mega-Collection Database consists of satellite images and oil-slick polygons identified in the Gulf of Mexico (GMex) and the Brazilian Continental Margin (BCM). A series of attributes describing the interpreted slicks are also included, along with technical reports and scientific papers. Two experiments illustrate the use of the OSH to facilitate the selection of data subsets from the mega collection (GMex variables and BCM samples), in which artificial intelligence techniques—machine learning (ML)—classify slicks into seeps or spills. The GMex variable dataset was analyzed with simple linear discriminant analyses (LDAs), and a three-fold accuracy performance pattern was observed: (i) the least accurate subset (~65%) solely used acquisition aspects (e.g., acquisition beam mode, date, and time, satellite name, etc.); (ii) the best results (>90%) were achieved with the inclusion of location attributes (i.e., latitude, longitude, and bathymetry); and (iii) moderate performances (~70%) were reached using only morphological information (e.g., area, perimeter, perimeter to area ratio, etc.). The BCM sample dataset was analyzed with six traditional ML methods, namely naive Bayes (NB), K-nearest neighbors (KNN), decision trees (DT), random forests (RF), support vector machines (SVM), and artificial neural networks (ANN), and the most effective algorithms per sample subsets were: (i) RF (86.8%) for Campos, Santos, and Ceará Basins; (ii) NB (87.2%) for Campos with Santos Basins; (iii) SVM (86.9%) for Campos with Ceará Basins; and (iv) SVM (87.8%) for only Campos Basin. The OSH can assist in different concerns (general public, social, economic, political, ecological, and scientific) related to petroleum exploration and production activities, serving as an important aid in discovering new offshore exploratory frontiers, avoiding legal penalties on oil-seep events, supporting oceanic monitoring systems, and providing valuable information to environmental studies.

Deep Learning-Based Approaches for Oil Spill Detection: A Bibliometric Review of Research Trends and Challenges - Rodrigo N. Vasconcelos; André T. Cunha Lima; Carlos A. D. Lentini; José Garcia V. Miranda; Luís F. F. de Mendonça; José M. Lopes; Mariana M. M. Santana; Elaine C. B. Cambuí; Deorgia T. M. Souza; Diego P. Costa; Soltan G. Duverger; Washington S. Franca-Rocha (Journal of Marine Science and Engineering, 2023)
Oil spill detection and mapping using deep learning (OSDMDL) is crucial for assessing its impact on coastal and marine ecosystems. A novel approach was employed in this study to evaluate the scientific literature in this field through bibliometric analysis and literature review. The Scopus database was used to evaluate the relevant scientific literature in this field, followed by a bibliometric analysis to extract additional information, such as architecture type, country collaboration, and most cited papers. The findings highlight significant advancements in oil detection at sea, with a strong correlation between technological evolution in detection methods and improved remote sensing data acquisition. Multilayer perceptrons (MLP) emerged as the most prominent neural network architecture in 11 studies, followed by a convolutional neural network (CNN) in 5 studies. U-Net, DeepLabv3+, and fully convolutional network (FCN) were each used in three studies, demonstrating their relative significance too. The analysis provides insights into collaboration, interdisciplinarity, and research methodology and contributes to the development of more effective policies, strategies, and technologies for mitigating the environmental impact of oil spills in OSDMDL.

Use of granules and free salts for Fe and Zn fortification of leafy vegetables: Improvements in trace element bioaccessibility and fulfillment of Dietary Reference Intakes - J. Martínez-Castro; F. Cámara-Martos; A. Moreno-Ortega; M. Victorio-Sánchez; A. Krstova; J. Almeida Lopes; F. Pérez-Rodríguez (Journal of Trace Elements in Medicine and Biology, 2023)

Hair mercury is associated with dyslipidemia and cardiovascular risk: An anthropometric, biochemical and genetic cross-sectional study of Amazonian vulnerable populations. - Amanda Lopes-Araújo; Gabriela P. Arrifano; Barbarella M. Macchi; Marcus Augusto-Oliveira; Letícia Santos-Sacramento; Rosa C. Rodríguez Martín-Doimeadios; María Jiménez-Moreno; Arnaldo J. Martins Filho; Jacqueline I. Alvarez-Leite; Reinaldo B. Oriá; José Luiz M. do Nascimento; Maria Elena Crespo-Lopez (Environmental Research, 2023)

Linear time-invariant filtering for real-time monitoring of ionospheric scintillation in GNSS receivers - Rafael A. M. Lopes; Felix Antreich; Friederike Fohlmeister; Martin Kriegel; Helio K. Kuga (GPS Solutions, 2023)

Survey-based atmospheric emission inventory for the residential sector: Santiago Island, Cabo Verde - D. Lopes; E. Semedo; D. Graça; S. Rafael; S. M. Freire; M. Lopes (Air Quality, Atmosphere & Health, 2023)

Gold nanoparticle intratesticular injections as a potential animal sterilization tool: Long-term reproductive and toxicological implications - John L.P. Coimbra; Graziela de P.F. Dantas; Lídia M. de Andrade; Marcos.R.G. Brener; Pedro I.M. Viana; Roberta.A. Lopes; Daniele. O.G Gontijo; Luiz.O.G. Ervilha; Mirian.Q. Assis; Luciola.S. Barcelos; Raphael. E. Szawka; Débora C. Damasceno; et al. (Toxicology, 2023)

The effect of ultrasound on improving the extraction of tannins from the Stryphnodendron adstringens bark - Maurício M. de Souza Ribeiro; Juliane Viganó; Nathália Stahl de Novais; Leonardo M. de Souza Mesquita; Renan Canute Kamikawachi; Wagner Vilegas; Patricia Santos Lopes; Camila Soares da Silva; Maurício Ariel Rostagno; Priscila Carvalho Veggi (Sustainable Chemistry and Pharmacy, 2023)

Facing the challenges of air quality and health in a future climate: The Aveiro Region case study - S. Coelho; J. Ferreira; D. Lopes; D. Carvalho; M. Lopes (Science of The Total Environment, 2023)

Industry 4.0 implementation: Environmental and social sustainability in manufacturing multinational enterprises - João J. Ferreira; João M. Lopes; Sofia Gomes; Hussain G. Rammal (Journal of Cleaner Production, 2023)

Magnetic solid phase extraction as a nonchromatographic method for the quantification of ultratrace inorganic arsenic in rice by inductively coupled plasma-optical emission spectrometry (ICP OES) - Francisco L.F. da Silva; Francisco E.H. Lima; Davino M. Andrade Neto; Fernando L. de Menezes; Lillian M.U.D. Fechine; Abdullah Akhdhar; Livia P.D. Ribeiro; Ana R.A. Nogueira; Pierre B.A. Fechine; Gisele S. Lopes; Wladiana O. Matos (Food Chemistry, 2023)

Authentication of incense (Pittosporum undulatum Vent.) honey from the Azores (Mel dos Açores) by a novel real-time PCR approach - Ana R. Lopes; Mónica B.M.V. Moura; Liliana Grazina; Joana Costa; Joana S. Amaral; M. Alice Pinto; Isabel Mafra (Food Chemistry, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

New, fast, and precise method of COVID-19 detection in nasopharyngeal and tracheal aspirate samples combining optical spectroscopy and machine learning - Denny M. Ceccon; Paulo Henrique R. Amaral; Lídia M. Andrade; Maria I. N. da Silva; Luis A. F. Andrade; Thais F. S. Moraes; Flavia F. Bagno; Raissa P. Rocha; Daisymara Priscila de Almeida Marques; Geovane Marques Ferreira; Alice Aparecida Lourenço; Ágata Lopes Ribeiro; et al. (Brazilian Journal of Microbiology, 2023)

Source apportionment of air pollution in urban areas: a review of the most suitable source-oriented models - S. Coelho; J. Ferreira; M. Lopes (Air Quality, Atmosphere & Health, 2023)
Notwithstanding the improvements already achieved in recent decades through regional and urban scale actions implemented across Europe, air pollution is still a major environment and health concern for Europeans. The quantitative assessment of the different sources of air pollution in regional/urban areas is crucial to support the design of accurate air quality plans. Source apportionment techniques are capable to relate air pollutant concentrations to existing emission sources activities and regions. The selection of the appropriate source apportionment technique to apply to a given area should take into account the ultimate goal of the study. Despite the growing number of studies that include source apportionment techniques, there is still a lack of works that summarise information on this topic in a systematic way. In this work, a literature review of studies applying SA techniques, published between 2010 and 2021, was performed. Additionally, this review summarizes the differences among the different source apportionment techniques, with focus on source-oriented models, highlighting their purpose and their advantages and disadvantages. Results shows that the number of studies using source apportionment source-oriented models has been increasing across the years, with 59% using tagged species methods, 28% brute force methods, and 13% other methods. This source-oriented models have been mostly applied for PM2.5, to assess the causes of air pollution levels.

20-Month monitoring of SARS-CoV-2 in wastewater of Curitiba, in Southern Brazil - Ricardo Belmonte-Lopes; Carlos E. R. Barquilha; Caroline Kozak; Demian S. Barcellos; Bárbara Z. Leite; Fernanda J. O. Gomes da Costa; William L. Martins; Pâmela E. Oliveira; Edy H. R. A. Pereira; Cesar R. Mota Filho; Emanuel M. de Souza; Gustavo R. C. Possetti; et al. (Environmental Science and Pollution Research, 2023)

How the new climate scenarios will affect air quality trends: An exploratory research - S. Coelho; S. Rafael; A.P. Fernandes; M. Lopes; D. Carvalho (Urban Climate, 2023)

DNA metabarcoding to assess prey overlap between tuna and seabirds in the Eastern tropical Atlantic: Implications for an ecosystem-based management - Ana Rita Carreiro; Jaime A. Ramos; Vanessa A. Mata; Nathalie M. Almeida; Isabel Rodrigues; Ivo dos Santos; Diana M. Matos; Pedro M. Araújo; Teresa Militão; Jacob González-Sólis; Vitor H. Paiva; Ricardo Jorge Lopes (Marine Environmental Research, 2023)

Foraminiferal sandy contourite of the Limpopo Corridor (Mozambique margin): Facies characterization and paleoceanographic record - U. Lopes; N. Babonneau; R. Fierens; S. Revillon; F. Raisson; E. Miramontes; M. Rabineau; D. Aslanian; M. Moulin (Marine Geology, 2023)

Adaptive fuzzy variable fractional-order sliding mode vibration control of uncertain building structures - Kang Xu; Liping Chen; António M. Lopes; Mingwu Wang; Xiaochuan Li (Engineering Structures, 2023)

Quercetin decreases cardiac hypertrophic mediators and maladaptive coronary arterial remodeling in renovascular hypertensive rats without improving cardiac function - Eduardo Vieira da Rocha; Francisco Falchetti; Laena Pernomian; Marcela M. Blascke de Mello; Juliana M. Parente; Renato C. Nogueira; Beatriz Q. Gomes; Giuliana Bertozi; Jessica M. Sanches-Lopes; José Eduardo Tanus-Santos; Michele M. Castro (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Colchicine reduces the activation of NLRP3 inflammasome in COVID-19 patients - N. B. Amaral; T. S. Rodrigues; M. C. Giannini; M. I. Lopes; L. P. Bonjorno; P. I. S. O. Menezes; S. M. Dib; S. L. G. Gigante; M. N. Benatti; U. C. Rezek; L. L. Emrich-Filho; B. A. Sousa; et al. (Inflammation Research, 2023)

Application of radiological assessment as water quality criterion for effluent release in a Brazilian uranium mine - Wagner S. Pereira; Alphonse Kelecom; José M. Lopes; Maxime Charles-Pierre; Emanuele L. C. Campelo; Alessander S. Carmo; Lucas G. Padilha Filho; Alexandre K. S. Paiva; Ademir X. Silva (Environmental Science and Pollution Research, 2023)

Chemical characterization of Brazilian savannah Byrsonima species (muricis) and their impact on genomic instability and chemopreventive effects - Ana Flávia L. Specian; Katiuska Tuttis; Juliana M. Serpeloni; Diego L. Ribeiro; Higor Lopes Nunes; Marcelo M.P. Tangerina; Miriam Sannomiya; Eliana A. Varanda; Wagner Vilegas; Ilce Mara S. Cólus (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Three-dimensional characterization of karstic dissolution zones, fracture networks, and lithostratigraphic interfaces using GPR cubes, core logs, and petrophysics: Implications for thief zones development in carbonate reservoirs - Juliana A.G. Lopes; Walter E. Medeiros; Josibel G. Oliveira; Flávio L. Santana; Renata E.B. Araújo; Vincenzo La Bruna; Milton M. Xavier; Francisco H.R. Bezerra (Marine and Petroleum Geology, 2023)

Investigation of the chemical structure and analgesic and anti-inflammatory properties of polysaccharides that constitute the dietary fibers of soursop (Annona muricata) fruit - Carolina Lopes Leivas; Thaisa Moro Cantu-Jungles; Bruna Barbosa da Luz; Maria Fernanda de Paula Werner; Marcello Iacomini; Lucimara M. C. Cordeiro (Food Research International, 2023)

The impact of FSH stimulation and age on the ovarian and uterine traits and histomorphometry of prepubertal gilts - V.A.P. Alfradique; D.L. Souza Netto; S.V.P. Alves; A.F. Machado; C.M. Novaes; J.M. Penitente-Filho; M. Machado-Neves; M.S. Lopes; S.E.F. Guimarães (Domestic Animal Endocrinology, 2023)

Exploring the roles of starch for microbial encapsulation through a systematic mapping review - Camila C.V. Velloso; Marina M. Lopes; Alberto C. Badino; Cristiane S. Farinas (Carbohydrate Polymers, 2023)

Estimating genetic parameters of reproductive, carcass, and meat quality traits in Polled Nellore cattle - M. M. S. Mamede; G. J. M. Rosa; E. C. Eifert; F. B. Lopes; F. Baldi; M. F. Costa; R. D. Sainz; A. S. Carmo; A. S. Mascioli; C. U. Magnabosco (Tropical Animal Health and Production, 2023)

NiftyPAD - Novel Python Package for Quantitative Analysis of Dynamic PET Data - Jieqing Jiao; Fiona Heeman; Rachael Dixon; Catriona Wimberley; Isadora Lopes Alves; Juan Domingo Gispert; Adriaan A. Lammertsma; Bart N. M. van Berckel; Casper da Costa-Luis; Pawel Markiewicz; David M. Cash; M Jorge Cardoso; et al. (Neuroinformatics, 2023)
Current PET datasets are becoming larger, thereby increasing the demand for fast and reproducible processing pipelines. This paper presents a freely available, open source, Python-based software package called NiftyPAD, for versatile analyses of static, full or dual-time window dynamic brain PET data. The key novelties of NiftyPAD are the analyses of dual-time window scans with reference input processing, pharmacokinetic modelling with shortened PET acquisitions through the incorporation of arterial spin labelling (ASL)-derived relative perfusion measures, as well as optional PET data-based motion correction. Results obtained with NiftyPAD were compared with the well-established software packages PPET and QModeling for a range of kinetic models. Clinical data from eight subjects scanned with four different amyloid tracers were used to validate the computational performance. NiftyPAD achieved $$R^2>0.999$$ R 2 > 0.999 correlation with PPET, with absolute difference $$\sim 10^{-2}$$ ∼ 10 - 2 for linearised Logan and MRTM2 methods, and $$R^2>0.999999$$ R 2 > 0.999999 correlation with QModeling, with absolute difference $$\sim 10^{-4}$$ ∼ 10 - 4 for basis function based SRTM and SRTM2 models. For the recently published SRTM ASL method, which is unavailable in existing software packages, high correlations with negligible bias were observed with the full scan SRTM in terms of non-displaceable binding potential ( $$R^2=0.96$$ R 2 = 0.96 ), indicating reliable model implementation in NiftyPAD. Together, these findings illustrate that NiftyPAD is versatile, flexible, and produces comparable results with established software packages for quantification of dynamic PET data. It is freely available ( https://github.com/AMYPAD/NiftyPAD ), and allows for multi-platform usage. The modular setup makes adding new functionalities easy, and the package is lightweight with minimal dependencies, making it easy to use and integrate into existing processing pipelines.

Heavy rainfall associated with floods in southeastern Brazil in November–December 2021 - Jose A. Marengo; Marcelo E. Seluchi; Ana Paula Cunha; Luz Adriana Cuartas; Demerval Goncalves; Vinicius B. Sperling; Andrea M. Ramos; Giovanni Dolif; Silvia Saito; Fabiani Bender; Tarcio Rocha Lopes; Regina C. Alvala; et al. (Natural Hazards, 2023)

Correction to: Using commercial high‑resolution satellite imagery to monitor a nuisance macroalga in the largest marine protected area in the USA - Kauaoa M. S. Fraiola; Tomoaki Miura; Jonathan Martinez; Keolohilani H. Lopes; Fred Amidon; Juan Torres-Pérez; Heather L. Spalding; Taylor Williams; Khemarith So; Elyse Sachs; Randall K. Kosaki (Coral Reefs, 2023)

Genetic diversity goals and targets have improved, but remain insufficient for clear implementation of the post-2020 global biodiversity framework - Sean Hoban; Michael W. Bruford; Jessica M. da Silva; W. Chris Funk; Richard Frankham; Michael J. Gill; Catherine E. Grueber; Myriam Heuertz; Margaret E. Hunter; Francine Kershaw; Robert C. Lacy; Caroline Lees; et al. (Conservation Genetics, 2023)
Genetic diversity among and within populations of all species is necessary for people and nature to survive and thrive in a changing world. Over the past three years, commitments for conserving genetic diversity have become more ambitious and specific under the Convention on Biological Diversity’s (CBD) draft post-2020 global biodiversity framework (GBF). This Perspective article comments on how goals and targets of the GBF have evolved, the improvements that are still needed, lessons learned from this process, and connections between goals and targets and the actions and reporting that will be needed to maintain, protect, manage and monitor genetic diversity. It is possible and necessary that the GBF strives to maintain genetic diversity within and among populations of all species, to restore genetic connectivity, and to develop national genetic conservation strategies, and to report on these using proposed, feasible indicators.

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

A roadmap for the conservation of freshwater mussels in Europe - Ronaldo Sousa; Tadeusz Zając; Dariusz Halabowski; Olga V. Aksenova; Yulia V. Bespalaya; Francisco Carvalho; Paulo Castro; Karel Douda; Janine P. da Silva; Noé Ferreira‐Rodríguez; Juergen Geist; Clemens Gumpinger; et al. (Conservation Biology, 2023)
Europe has a long history of human pressure on freshwater ecosystems. As pressure continues to grow and new threats emerge, there is an urgent need for conservation of freshwater biodiversity and its ecosystem services. However, whilst some taxonomic groups, mainly vertebrates, have received a disproportionate amount of attention and funds, other groups remain largely off the public and scientific radar. Freshwater mussels (Bivalvia, Unionida) are an alarming example of this conservation bias and here we point out six conceptual areas that need immediate and long‐term attention: knowledge, threats, socioeconomics, conservation, governance and education. The proposed roadmap aims to advance research, policy and education by identifying the most pressing priorities for the short‐ and long‐term conservation of freshwater mussels across Europe.

The antecedents of sustainability-oriented entrepreneurial intentions: An exploratory study of Angolan higher education students - João M. Lopes; Nathalia Suchek; Sofia Gomes (Journal of Cleaner Production, 2023)

Willingness to pay more for green products: A critical challenge for Gen Z - Sofia Gomes; João M. Lopes; Sónia Nogueira (Journal of Cleaner Production, 2023)

Impact of gastrointestinal digestion simulation on brewer’s spent grain green extracts and their prebiotic activity - Teresa Bonifácio-Lopes; Luís M. G. Castro; Ana Vilas-Boas; Débora Campos; José A. Teixeira; Manuela Pintado (Food Research International, 2023)

DNA sequencing shows that tropical tuna species misidentification can be an underestimated issue in fish landings - Ana Rita Carreiro; Jaime A. Ramos; Vanessa Mata; Nathalie M. Almeida; Vítor H. Paiva; Ricardo Jorge Lopes (Food Control, 2023)

Diverging or converging to a green world? Impact of green growth measures on countries’ economic performance - João J. Ferreira; João M. Lopes; Sofia Gomes; Claudia Dias (Environment, Development and Sustainability, 2023)
Green growth has emerged in recent years to respond to environmental problems caused by climate change and the scarcity of resources. However, today’s green growth involves environmental, social and financial dimensions. In this context, many countries are currently seeking green growth for their economic development through the efficient use of their resources. This study aims to assess the impact of green growth performance on the economic development of countries. A quantitative approach was applied to a sample of 172 countries worldwide, and the formulated hypotheses were tested through multiple linear regressions estimated by the ordinary least squares method. The economic development of countries was measured by the Human Development Index (HDI) and measures the sustainability performance of countries by the Green Growth Index (GGI). The results of this study demonstrate that (i) the measures of green growth performance have a positive impact on the economic development of high-income, upper-middle-income, and lower-middle-income economies, (ii) in poorer economies, less is the contribution of green growth to economic development, mainly because they neglecting the social dimension despite the numerous existing projects in these economies for greater inclusion and (iii) green economic opportunities (green investment, green trade, green employment and green innovation) do not influence green economic development in all analysed economies. Consequently, suggestions were made for policymakers from different groups of countries to increase and accelerate their sustainable green growth. Literature on economic development and green growth is still scarce, especially at the empirical level, and few studies use the 2020 GGI data. In addition, this study also uses recent rankings of world economies to categorize the economic development of countries.

Inhalant cannabidiol impedes tumor growth through decreased tumor stemness and impaired angiogenic switch in NCI-H1437-induced human lung cancer model - Évila Lopes Salles; Sahar Emami Naeini; Hesam Khodadadi; Bidhan Bhandari; Sholeh Rezaee; Edie Threlkeld; Hannah M. Rogers; Vincenzo Costigliola; Alvin V. Terry; David C. Hess; Sumitra Deb; Swati Palit Deb; et al. (Human Cell, 2023)

A numerical methodology to predict the lateral load response of monopiles installed in SAND considering soil stiffness degradation - Guilherme K. Lopes; José Renato M. de Sousa; Maria C.F. de Almeida; Marcio S.S. de Almeida (Ocean Engineering, 2023)

Predicting future coastal land use/cover change and associated sea-level impact on habitat quality in the Northwestern Coastline of Guinea-Bissau - Namir Domingos Raimundo Lopes; Tianxin Li; Peng Zhang; Nametso Matomela; Harrison Odion Ikhumhen; Rui M. Sá (Journal of Environmental Management, 2023)

Disinfection of treated urban effluents for reuse by combination of coagulation/flocculation and Fenton processes - João P.F. Venâncio; Sara Ribeirinho-Soares; Luísa C. Lopes; Luis M. Madeira; Olga C. Nunes; Carmen S.D. Rodrigues (Environmental Research, 2023)

Activation of persulfate using copper oxide nanoparticles for the degradation of Rhodamine B containing effluents: Degradation efficiency and ecotoxicological studies - Mahsa Davarazar; Mohammadreza Kamali; Cátia Venâncio; Antonieta Gabriel; Tejraj M. Aminabhavi; Isabel Lopes (Chemical Engineering Journal, 2023)

Deep eutectic solvents for improved biomass pretreatment: Current status and future prospective towards sustainable processes - María del Mar Contreras-Gámez; Ángel Galán-Martín; Nalin Seixas; André M. da Costa Lopes; Armando Silvestre; Eulogio Castro (Bioresource Technology, 2023)

Diagnosis of Respiratory Changes in Cystic Fibrosis Using a Soft Voting Ensemble with Bayesian Networks and Machine Learning Algorithms - Noemi P. Pinto; Jorge L. M. Amaral; Agnaldo J. Lopes; Pedro L. Melo (Journal of Medical and Biological Engineering, 2023)

Structured-bed reactor with intermittent aeration and recirculation (SBRRIA) for treating UASB effluent combined with raw sewage - A. C. Wendling; J. G. B. Oliveira; N. T. Jenzura; D. D. Lopes; M. H. R. Z. Damianovic; A. C. Barana (International Journal of Environmental Science and Technology, 2023)

Guild-dependent effects of forest fragmentation in canopy arthropod diversity associated to Quercus deserticola - Silvia Ecaterina García-Jain; Yurixhi Maldonado-López; Ken Oyama; Ma. Carmen López-Maldonado; Marcílio Fagundes; Maurício Lopes de Faria; Mário M. Espírito-Santo; Marcela Sofía Vaca-Sánchez; Pablo Cuevas-Reyes (European Journal of Forest Research, 2023)

Using commercial high-resolution satellite imagery to monitor a nuisance macroalga in the largest marine protected area in the USA - Kauaoa M. S. Fraiola; Tomoaki Miura; Jonathan Martinez; Keolohilani H. Lopes; Fred Amidon; Juan Torres-Pérez; Heather L. Spalding; Taylor Williams; Khemarith So; Elyse Sachs; Randall K. Kosaki (Coral Reefs, 2023)
Satellite imagery is a useful tool for monitoring and mapping the distribution of invasive or nuisance algal species on coral reefs over the temporal and spatial scales needed for ecosystem management. Visual inspections of high-resolution satellite imagery were used to detect the newly discovered nuisance alga, Chondria tumulosa , at Manawai (Pearl and Hermes Atoll) in combination with ground-truthing surveys. Low-albedo (“dark”) survey sites on spur habitats were associated with mean C. tumulosa cover seven times higher than adjacent high-albedo (“light”) sites. There was an inverse relationship between C. tumulosa percent cover at ground-truthing sites and mean reflectance values. Archival satellite imagery showed that areas of high C. tumulosa cover (i.e., dark patches) were not evident on or before 2015 on the northeast backreef. The ability to use satellites for the detection of nuisance or invasive benthic species, such as expansive mats of C. tumulosa , provides managers with a valuable tool, especially in remote regions.

Genetic structure of the threatened Gray Parrotfish (Sparisoma axillare) in the Southwestern Atlantic - Julia Tovar Verba; Carlos E. L. Ferreira; Maria Grazia Pennino; Linda Hagberg; Priscila F. M. Lopes; Beatrice Padovani Ferreira; Sergio Maia Queiroz Lima; Adam Stow (Coral Reefs, 2023)
Despite the marine environment being typified by a lack of obvious barriers to dispersal, levels of genetic divergence can arise in marine organisms from historical changes in habitat availability, current oceanographic regimes and anthropogenic factors. Here we describe the genetic structure of the Gray Parrotfish, Sparisoma axillare , and identify environmental variables associated with patterns of genetic divergence throughout most of its distribution in Brazil. The heavily exploited Gray Parrotfish is endemic to Brazil, and there is lack of data on population structure that is needed to support sustainable management. To address this shortfall we analyzed 5429 SNPs from individuals sampled in nine locations, ranging from tropical to subtropical reef systems and costal to oceanic environments with varying levels of protection. We found low levels of genetic structure along the coast, including the oceanic island of Fernando de Noronha, and that a combination of water depth, ocean currents and geographic distance were the major drivers explaining genetic divergence. We identified a distinct genetic population around Trindade Island, 1000 km from the coast, highlighting the conservation significance of this population. Colonization of this oceanic site probably occurred during the Pleistocene periods of lower sea levels, allowing this shallow water-dependent species to use the seamount chain as stepping stones to Trindade. Our data further suggest that two protected areas, Costa dos Corais and Fernando de Noronha, likely play an important role as larval sources for much of the species distribution.

New evidence to demystify the supposed holoplanktonic life cycle in Ceriantharia (Cnidaria) - Celine S. S. Lopes; Maximiliano M. Maronna; José E. Martinelli Filho; André C. Morandini; Sérgio N. Stampar (Marine Biodiversity, 2023)

LACTB induces cancer cell death through the activation of the intrinsic caspase-independent pathway in breast cancer - Juan M. Gonzalez-Morena; Sara Escudeiro-Lopes; Jessica Mariane Ferreira-Mendes; Pavel Jakoube; Valentina Cutano; Judith Vinaixa-Forner; Petra Kralova Viziova; Andrea Hartmanova; Radislav Sedlacek; Susana Machado; Beata Malcekova; Zuzana Keckesova (Apoptosis, 2023)
Background LACTB was recently identified as a mitochondrial tumour suppressor that negatively affects cancer cell proliferation by inducing cell death and/or differentiation, depending on the cell type and tissue. However, the detailed mechanism underlying the LACTB-induced cancer cell death is largely unknown. Methods We used cell-based, either in 2D or 3D conditions, and in vivo experiments to understand the LACTB mechanisms. In this regard, protein array followed by an enrichment analysis, cell proliferation assays using different compounds, western blot analysis, flow cytometry and immunofluorescence were performed. Differences between quantitative variables following normal distribution were valuated using Student t test for paired or no-paired samples according to the experiment. For in vivo experiments differences in tumour growth were analyzed by 2-way ANOVA. Results We show, that LACTB expression leads to cell cycle arrest in G1 phase and increase of DNA oxidation that leads to activation of intrinsic caspase-independent cell death pathway. This is achieved by an increase of mitochondrial reactive oxygen species since early time points of LACTB induction. Conclusion Our work provides a deeper mechanistic insight into LACTB-mediated cancer-cell death and shows the dynamics of the cellular responses a particular tumor suppressive stimulus might evoke under different genetic landscapes.

Arsenic pools in soils under native vegetation on a steatite outcrop in Brazil - Laís L. Silva; Marina M. Feitosa; Emerson F. Vilela; Guilherme Lopes; Luiz R.G. Guilherme; Yuri L. Zinn (Environmental Research, 2023)

Low population genetic structure is consistent with high habitat connectivity in a commercially important fish species (Lutjanus jocu) - Julia Tovar Verba; Adam Stow; Bernhard Bein; Maria Grazia Pennino; Priscila F. M. Lopes; Beatrice P. Ferreira; Meghana Mortier; Sergio Maia Queiroz Lima; Ricardo J. Pereira (Marine Biology, 2023)
The level of habitat availability influences genetic divergence among populations and the genetic diversity within populations. In the marine environment, near-shore species are among the most sensitive to habitat changes. Knowledge of how historical environmental change affected habitat availability and genetic variation can be applied to the development of proactive management strategies of exploited species. Here, we modeled the contemporary and historical distribution of Lutjanus jocu in Brazil. We describe patterns of genomic diversity to better understand how climatic cycles might correlate with the species demographic history and current genetic structure. We show that during the Last Glacial Maximum, there were ecological barriers that are absent today, possibly dividing the range of the species into three geographically separated areas of suitable habitat. Consistent with a historical reduction in habitat area, our analysis of demographic changes shows that L. jocu experienced a severe bottleneck followed by a population size expansion. We also found an absence of genetic structure and similar levels of genetic diversity throughout the sampled range of the species. Collectively, our results suggest that habitat availability changes have not obviously influenced contemporary levels of genetic divergence between populations. However, our demographic analyses suggest that the high sensitivity of this species to environmental change should be taken into consideration for management strategies. Furthermore, the general low levels of genetic structure and inference of high gene flow suggest that L. jocu likely constitutes a single stock in Brazilian waters and, therefore, requires coordinated legislation and management across its distribution.

Effects of tidal emersion and marine heatwaves on cuttlefish early ontogeny - João Coelho; Mélanie Court; Eve Otjacques; Vanessa M. Lopes; José Ricardo Paula; Tiago Repolho; Mário Diniz; Rui Rosa (Marine Biology, 2023)

Soil flooding and its outcome on cadmium and nutrient uptake affect photosynthetic activity in Inga laurina plants - Namir G. M. Lopes; Rodrigo B. Kloss; Ivanildes C. dos Santos; Vânia L. Souza; Majeti N. V. Prasad; Pedro A. O. Mangabeira; Marcel G. C. França (Ecotoxicology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Unveiling mesophotic diversity in Hawai‘i: two new species in the genera Halopeltis and Leptofauchea (Rhodymeniales, Rhodophyta) - Erika A. Alvarado; Feresa P. Cabrera; Monica O. Paiano; James T. Fumo; Heather L. Spalding; Celia M. Smith; Jason C. Leonard; Keolohilani H. Lopes Jr.; Randall K. Kosaki; Alison R. Sherwood (Algae, 2022)
Two genera of the Rhodymeniales, Halopeltis and Leptofauchea, are here reported for the first time from the Hawaiian Islands and represent the deepest records for both genera. Molecular phylogenetic analyses of cytochrome oxidase subunit I (COI), rbcL, and large subunit ribosomal DNA (LSU) sequences for Hawaiian specimens of Leptofauchea revealed one well-supported clade of Hawaiian specimens and three additional lineages. One of these clades is described here as Leptofauchea huawelau sp. nov., and is thus far known only from mesophotic depths at Penguin Bank in the Main Hawaiian Islands. L. huawelau sp. nov. is up to 21 cm, and is the largest known species. An additional lineage identified in the LSU and rbcL analyses corresponds to the recently described L. lucida from Western Australia, and is a new record for Hawai‘i. Hawaiian Halopeltis formed a well-supported clade along with H. adnata from Korea, the recently described H. tanakae from mesophotic depths in Japan, and H. willisii from North Carolina, and is here described as Halopeltis nuahilihilia sp. nov. H. nuahilihilia sp. nov. has a distinctive morphology of narrow vegetative axes that harbor constrictions along their length. The current distribution of H. nuahilihilia includes mesophotic depths around W. Maui, W. Moloka‘i, and the island of Hawai‘i in the Main Hawaiian Islands. Few reproductive characters were observed because of the small number of specimens available; however, both species are distinct based on phylogeny and morphology. These descriptions further emphasize the Hawaiian mesophotic zone as a location harboring many undescribed species of marine macroalgae.

Bradyrhizobium occurrence in nodules of perennial horsegram - Mayan Blanc Amaral; Tamiris dos Santos Lopes; Caroline Bueno Feder; Thiago Gonçalves Ribeiro; Rafael Sanches Pacheco; Thiago Neves Teixeira; Edevaldo de Castro Monteiro; Israel Oliveira Ramalho; Robert de O. Macedo; Robert M. Boddey; Jerri Edson Zilli; Bruno J. R. Alves (Brazilian Journal of Microbiology, 2022)

Design of biomass-based composite photocatalysts for wastewater treatment: a review over the past decade and future prospects - Marina M. G. Pastre; Deivisson Lopes Cunha; Marcia Marques (Environmental Science and Pollution Research, 2022)

The Infection of Paracalanid Copepods by the Alveolate Parasite Ellobiopsis chattoni Caullery, 1910 in a Subtropical Coastal Area - José E. Martinelli Filho; Felipe Gusmão; Flavio A. Alves-Júnior; Rubens M. Lopes (Journal of Marine Science and Engineering, 2022)
Paracalanid copepods, common in tropical zooplankton communities, are known hosts for a variety of parasites. Nevertheless, relatively little is known about the prevalence and consequences of parasitism in these copepods. In this study, we analyzed the relationship between two paracalanid copepods, Parvocalanus crassirostris and Paracalanus spp., with a common parasite, the alveolate protist Ellobiopsis chattoni, in a subtropical environment on the south-east Brazilian coast. We assessed the frequency and abundance of parasites in juveniles and adult male and female copepods. We observed that 22 out of 4014 Paracalanus spp. (0.55%) and 98 out of 3920 P. crassirostris were infected (2.5%). E. chattoni were rarely found in other taxa (about 0.05% for Oithona spp. and Acartia lilljeborgii). The parasites were most frequently attached to cephalosome appendages (73.6%), with up to four cells per copepod. The parasites were more prevalent in adults than juveniles, and adult females were more frequently infected than males. E. chattoni had a likely negative impact on copepod growth because the infected females were smaller than the non-infected females (p

Sexual segregation in the foraging distribution, behaviour, and trophic niche of the endemic Boyd’s shearwater (Puffinus lherminieri boydi) - Ivo dos Santos; Jaime A. Ramos; Filipe R. Ceia; Isabel Rodrigues; Nathalie Almeida; Stefan Antunes; Ana R. Carreiro; Diana M. Matos; Ricardo J. Lopes; Pedro Geraldes; Vítor H. Paiva (Marine Biology, 2022)

Microalgae-derived polysaccharides: Potential building blocks for biomedical applications - Ihana A. Severo; Rosangela R. Dias; Tatiele C. do Nascimento; Mariany C. Deprá; Mariana M. Maroneze; Leila Q. Zepka; Eduardo Jacob-Lopes (World Journal of Microbiology and Biotechnology, 2022)

Influence of Parity on the Colostrum Bacterial Community Composition in Holstein Cows - J. S. Silva; D. R. G. Lopes; S. M. Moreira; T. G. R. Veloso; C. B. P. Bento; P. P. Rotta; H. C. Mantovani (Indian Journal of Microbiology, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Differential Effects of Food Restriction and Warming in the Two-Spotted Goby: Impaired Reproductive Performance and Stressed Offspring - Ana F. Lopes; Robyn Murdoch; Sara Martins-Cardoso; Carolina Madeira; Pedro M. Costa; Ana S. Félix; Rui F. Oliveira; Narcisa M. Bandarra; Catarina Vinagre; Ana R. Lopes; Emanuel J. Gonçalves; Ana Margarida Faria (Fishes, 2022)
Climate change is a growing threat to marine organisms and ecosystems, and it is already modifying ocean properties by, for example, increasing temperature and decreasing pH. Increasing water temperature may also lead to an impairment of primary productivity and an overall depletion of available zooplankton. Understanding how the crossover between warming and zooplankton availability impacts fish populations has paramount implications for conservation and mitigation strategies. Through a cross factorial design to test the effects of ocean temperature and food availability in a temperate marine teleost, Pomatochistus flavescens, we showed that hindered feeding impacted sheltering and avoidance behaviour. Also, low food availability impaired fish reproduction, particularly male reproduction, as the expression of cyp11b1, a gene with a pivotal role in the synthesis of the most important fish androgen, 11-ketotestosterone, was significantly reduced under a low food regime. In contrast, temperature alone did not affect reproductive success, but offspring showed increased saturated fatty acid content (embryos) and increased lipid peroxidation (larvae). Altogether, food availability had a stronger effect on fitness, showing that coping with elevated temperatures, an ability that may be expected in shallow-water fish, can be indirectly impacted, or even overwhelmed, by the effects of ocean warming on primary productivity and downstream ecological processes.

Water chemistry of rivers and streams from the Jaú and Uatumã basins in central Brazilian Amazon - Eduardo Antonio Ríos-Villamizar; Aline Lopes; Maria do Socorro Rocha da Silva; Nilyan Adria Santarém dos Santos; Regison Oliveira; Robson M. Calazães; Maria Teresa Fernandez Piedade; Jochen Schöngart; Bruce R. Forsberg; Florian Wittmann; Wolfgang J. Junk (Sustainable Water Resources Management, 2022)

Assessment of released natural radionuclides by waste rock pile and mining pit associated with a uranium mine at Caldas, Minas Gerais, Brazil - Wagner S. Pereira; Alphonse Kelecom; Maxime Charles-Pierre; José M. Lopes; Emanuele L. C. Campelo; Cleber B. Espindola; Alessander S. Carmo; Delcy A. Py Junior; Samuel Q. Pelegrineli; Ademir X. Silva (Environmental Science and Pollution Research, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Oil spill detection based on texture analysis: how does feature importance matter in classification? - Rodrigo N. Vasconcelos; Carlos A. D. Lentini; André T. Cunha Lima; Luís F. F. Mendonça; Garcia V. Miranda; Elaine C. B. Cambuí; Diego Pereira Costa; Soltan Galano Duverger; Mainara B. Gouveia; José M. Lopes; Milton J. Porsani (International Journal of Remote Sensing, 2022)

A neglected disease. Human sporotrichosis in a densely populated urban area in São Paulo, Brazil: clinical–epidemiological and therapeutic aspects - Amanda Azevedo Bittencourt; Luiza Keiko Matsuka Oyafuso; Roberta Figueiredo Cavalin; Renata Bacic Palhares; Gil Benard; Viviane Mazo Fávero Gimenes; Gilda Maria Barbaro Del Negro; Lumena Pereira Machado Siqueira; Roseli Santos de Freitas Xavier; Leila M. Lopes-Bezerra; Renata Buccheri; José Angelo Lauletta Lindoso (Brazilian Journal of Microbiology, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Oil Spill and Socioeconomic Vulnerability in Marine Protected Areas - Felipe Roberto da Silva; Alexandre Schiavetti; Ana Cláudia Mendes Malhado; Beatrice Ferreira; Caio Victor de Paula Sousa; Fábio Pessoa Vieira; Francisco Roberto Pinto; Gabriel Barros Gonçalves de Souza; George Olavo; Jéssica Borba Quintela dos Santos; Joao Vitor Campos-Silva; José Gilmar Cavalcante de Oliveira Júnior; et al. (Frontiers in Marine Science, 2022)
The extensive oil spill (> 2,900 km) that occurred in the southwestern Atlantic (2019/2020) increased the vulnerability of the Brazilian coast, affecting marine and coastal protected areas (MPAs). In addition to supporting conservation, MPAs are sustainably used by local populations to help maintain ocean-dependent livelihoods. In this sense, we aim to assess the socioeconomic vulnerability of human communities in MPAs affected by this major oil spill. Using digital mapping, we assessed the socioeconomic vulnerability of 68 human communities living in or near 60 MPAs of different categories that were impacted by this spill. This is the first assessment of the vulnerability status of human populations under significant levels of poverty and social inequality, which are particularly dependent on healthy and effective Brazilian MPAs. More than 6,500 enterprises and institutions were mapped, including trade activities, services, tourism, and leisure venues. Most enterprises (34.4%) were involved in the food sector, related to the ocean economy, and, therefore, highly vulnerable to oil spills. Furthermore, the majority (79.3%) of the vulnerable activities are concentrated in multiple-use MPAs, with extractive reserves coming second and accounting for 18%. This result shows the high vulnerability of this tropical coast to oil accidents and the risks to food security for traditional communities. We also found a heterogeneous vulnerability indicator along the coast, with the most vulnerable regions having an undiversified economic matrix heavily dependent on activities such as fishing, family farming, tourism, accommodation, and the food sector. Thus, this study provides a tool to help prevent and mitigate economic losses and increases the understanding of the weaknesses of MPAs in the face of large-scale disasters, thus helping to build socioeconomic and ecological resilience.

Which birds are Brazilians seeing on urban and non-urban feeders? An analysis based on a collective online birding - Eduardo Roberto Alexandrino; Thaís Abreu Camboim; Flávia Guimarães Chaves; Alex Augusto Abreu Bovo; Marco Aurélio Galvão da Silva; Daniela Alves Maia da Silva; Margi Moss; Tatiana Pongiluppi Souza; Clarissa de Oliveira Santos; Caio Bezerra de Mattos Brito; Maristela Camolesi Alcantara; Karlla V. C. Barbosa; et al. (Ornithology Research, 2022)

Resilience and Social Adaptation to Climate Change Impacts in Small-Scale Fisheries - Sebastián Villasante; Gonzalo Macho; Monalisa R. O. Silva; Priscila F. M. Lopes; Pablo Pita; Andrés Simón; José Carlos Mariño Balsa; Celia Olabarria; Elsa Vázquez; Nuria Calvo (Frontiers in Marine Science, 2022)
Small-cale fisheries are important for livelihoods, food security, jobs and income worldwide. However, they face major challenges, including the increasing effects of climate change that pose serious risks to coastal ecosystems and fishing communities. Although scientific research on climate change impacts has increased in recent years, few studies have explored the social impacts on small-scale fisheries. Using Galicia (Spain) as a case study, we investigated individual and household-level adaptive responses to climate change among fishers in three fishing guilds (Cambados, Campelo, and Redondela). Specifically, we estimated the economic vulnerability of shellfishers and assessed the diversity of social adaptive responses used to deal with climate change. Although fishers’ income strongly depends on shellfishing in all studied areas, our findings show that less fishing experience and lower engagement in fisher associations tend to increase the economic vulnerability of the fishers. The fishers’ vulnerability decreases as the size of households increases, while fishers who pay a mortgage and who live in households with fewer active members tend to be more vulnerable. The findings also show that Galician shellfishers have developed a wide range of adaptation strategies to anticipate and respond to climate change impacts, namely harvesting pricier and more abundant species, reducing household expenses and increasing social involvement in shellfishery associations. Although the adaptive strategies have helped Galician fishers to deal with climate change impacts, several threats to the sustainability of shellfisheries remain, such as a decrease in the abundance of key native shellfish species, and a high dependence on public and private aid to ensure reasonable incomes for shellfisheries. These findings are of interest and relevance to other similar small-scale fisheries around the world facing similar climate change challenges.

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

Effects of forest fragmentation on plant quality, leaf morphology and herbivory of Quercus deserticola: is fluctuating asymmetry a good indicator of environmental stress? - Silvia Ecaterina García-Jain; Yurixhi Maldonado-López; Ken Oyama; Marcílio Fagundes; Maurício Lopes de Faria; Mário M. Espírito-Santo; Pablo Cuevas-Reyes (Trees, 2022)

Formaldehyde biodegradation in an ASBR-SBR system: an effective treatment solution for furniture industry painting booth wastewater - I. B. T. M. Bolonhesi; C. L. Andreani; J. D. P. Theodoro; A. Fazolo; D. D. Lopes (International Journal of Environmental Science and Technology, 2022)

New records of soft ticks (Acari: Argasidae) in the Caatinga biome of Brazil, with a phylogenetic analysis of argasids using the nuclear Histone 3 (H3) gene - Felipe R. Jorge; Lorena M. B. de Oliveira; Meylling M. L. Magalhães; Bárbara Weck; Glauber M. B. de Oliveira; Maria Carolina A. Serpa; Francisco B. P. Moura; Romilson S. Lopes Júnior; Jessica M. L. dos Santos; Bruno M. Teixeira; Sebastián Muñoz-Leal; Marcelo B. Labruna (Experimental and Applied Acarology, 2022)

Strong and lasting impacts of past global warming on baleen whales and their prey - Andrea A. Cabrera; Elena Schall; Martine Bérubé; Pia Anderwald; Lutz Bachmann; Simon Berrow; Peter B. Best; Phillip J. Clapham; Haydée A. Cunha; Luciano Dalla Rosa; Carolina Dias; Kenneth P. Findlay; et al. (Global Change Biology, 2022)
Global warming is affecting the population dynamics and trophic interactions across a wide range of ecosystems and habitats. Translating these real‐time effects into their long‐term consequences remains a challenge. The rapid and extreme warming period that occurred after the Last Glacial Maximum (LGM) during the Pleistocene–Holocene transition (7–12 thousand years ago) provides an opportunity to gain insights into the long‐term responses of natural populations to periods with global warming. The effects of this post‐LGM warming period have been assessed in many terrestrial taxa, whereas insights into the impacts of rapid global warming on marine taxa remain limited, especially for megafauna. In order to understand how large‐scale climate fluctuations during the post‐LGM affected baleen whales and their prey, we conducted an extensive, large‐scale analysis of the long‐term effects of the post‐LGM warming on abundance and inter‐ocean connectivity in eight baleen whale and seven prey (fish and invertebrates) species across the Southern and the North Atlantic Ocean; two ocean basins that differ in key oceanographic features. The analysis was based upon 7032 mitochondrial DNA sequences as well as genome‐wide DNA sequence variation in 100 individuals. The estimated temporal changes in genetic diversity during the last 30,000 years indicated that most baleen whale populations underwent post‐LGM expansions in both ocean basins. The increase in baleen whale abundance during the Holocene was associated with simultaneous changes in their prey and climate. Highly correlated, synchronized and exponential increases in abundance in both baleen whales and their prey in the Southern Ocean were indicative of a dramatic increase in ocean productivity. In contrast, the demographic fluctuations observed in baleen whales and their prey in the North Atlantic Ocean were subtle, varying across taxa and time. Perhaps most important was the observation that the ocean‐wide expansions and decreases in abundance that were initiated by the post‐LGM global warming, continued for millennia after global temperatures stabilized, reflecting persistent, long‐lasting impacts of global warming on marine fauna.

Socio‐ecological and economic aspects of tropical tuna fisheries in the Mozambique Channel - Anildo Nataniel; Priscila F. M. Lopes; Jon Lopez; Maria Soto (Fisheries Management and Ecology, 2022)
Industrial and small‐scale tuna fisheries in Mozambique may compete over the same resources, which has potential socio‐ecological impacts. The two types of fisheries were investigated by characterising their catch trends, types of interactions, number of people they employ and revenues. Commercial landings, logbook data and all previously established tuna Fishing Partner Agreements in the country were analysed, as well as data collected from interviews with small‐scale fishers. A declining trend in catches was observed in the industrial fisheries sector, which was also perceived by small‐scale fishers, and suggests that there is some competition between these two sectors for the same tuna stocks, even when these stocks are targeted in separate grounds. While the small‐scale tuna fisheries sector provides thousands of local direct and indirect jobs and high economic benefits for fishing communities, the industrial fisheries sector may only be economically advantageous to Mozambique if Fishing Partner Agreements are improved and enforced. Although maintaining non‐overlapping fishing grounds between industrial and small‐scale fisheries may be positive for the fishers, it could result in major pressure on the tuna stocks, as they would be exploited relentlessly.

Occurrence and Molecular Identification of Hemoparasites in Wild Mammals Kept in Rehabilitation Centers in Brazil - Natália M. N. Fava; Talita Silva Alves; Marcos Gomes Lopes; Marcelo Bahia Labruna; André Quagliatto Santos; Márcia Cristina Cury (Acta Parasitologica, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Semi-natural fishway efficiency for goliath catfish (Brachyplatystoma spp.) in a large dam in the Amazon Basin - Lisiane Hahn; Eduardo G. Martins; Leonardo D. Nunes; Leonardo S. Machado; Taise M. Lopes; Luís Fernando da Câmara (Hydrobiologia, 2022)

Correction to: Relationship Between Gymnastic Rhythmic Practice and Body Composition, Physical Performance, and Trace Element Status in Young Girls - Julián Campos-Pérez; Ricardo N. M. J. Páscoa; João Almeida Lopes; Fernando Cámara-Martos (Biological Trace Element Research, 2022)

Relationship Between Gymnastic Rhythmic Practice and Body Composition, Physical Performance, and Trace Element Status in Young Girls - Julián Campos-Pérez; Ricardo N. M. J. Páscoa; João Almeida Lopes; Fernando Cámara-Martos (Biological Trace Element Research, 2022)

Influence of Nitric Oxide–Cyclic GMP and Oxidative STRESS on Amyloid-β Peptide Induced Decrease of Na,K-ATPase Activity in Rat Hippocampal Slices - E. M. Kawamoto; M. M. Cararo-Lopes; P. F. Kinoshita; L. E. M. Quintas; L. S. Lima; D. Z. Andreotti; C. Scavone (The Journal of Membrane Biology, 2021)

Implications of Synthetic Modifications of the Cardiotonic Steroid Lactone Ring on Cytotoxicity - Gisele Capanema de Oliveira; Sayonarah Carvalho Rocha; Miliane Alves da Silva Lopes; Natasha Paixão; Silmara Lúcia Grego Alves; Marco Túlio Corrêa Pessoa; François Noël; Luis Eduardo M. Quintas; Leandro Augusto Barbosa; José Augusto Ferreira Perez Villar; Vanessa Faria Cortes (The Journal of Membrane Biology, 2021)

Root cultures of Monteverdia floribunda (Reissek) Biral grown in air sparging systems are sources of quinonemethide triterpenes - Mayara Valdevite; Bianca W. Bertoni; Leonardo Biral; Eduardo J. Crevelin; Suzelei C. França; Ediedia S. Pina; Adriana A. Lopes; Ana M. S. Pereira (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Synechocystis salina: potential bioactivity and combined extraction of added-value metabolites - Joana Assunção; Helena M. Amaro; Graciliana Lopes; Tânia Tavares; F. Xavier Malcata; A. Catarina Guedes (Journal of Applied Phycology, 2021)

The air pollution modelling system URBAIR: how to use a Gaussian model to accomplish high spatial and temporal resolutions - A. P. Fernandes; S. Rafael; D. Lopes; S. Coelho; C. Borrego; M. Lopes (Air Quality, Atmosphere & Health, 2021)

Combining Knowledge Systems Helps Understand the Spatial Dynamics of Data-Limited Small-Scale Fisheries Systems in Brazil: A Methods Analysis - Rebecca Borges; Indira A. L. Eyzaguirre; Roberta Sá Leitão Barboza; Karin Boos; Marion Glaser; Priscila F. M. Lopes (Frontiers in Marine Science, 2021)
Mangrove habitats provide nursery, shelter, and feeding sites for many economically relevant fish, and invertebrates, such as crabs. Given the highly artisanal character and the patchy spatial distribution of small-scale fishing in mangroves, there is often little data available to inform management, potentially threatening the sustainability of this livelihood-supporting activity. This study assesses the combination of different data collection methods and of including published data in the analysis of the spatial dynamics. We examine crab fisheries in two sustainable-use protected areas as a case study to understand use patterns as indicated by a specific combination of mapping methods. Mangrove crab fishing grounds were mapped by overlaying crab gatherers’ tracked routes with maps produced during participatory-mapping-centered interviews. Information from the literature was used to spatialize crab carapace width and relate it to distance traveled by fishers. Results show that crabs tended to be larger if caught farther from the villages where fishers live. In terms of collection methods, even though GPS tracking is relatively time- and resource-consuming, incorporating some GPS tracking into participatory mapping helps overcome a downside of this type of mapping (e.g., lack of geographical precision) and identifies information that can be accessed through participatory techniques. This highlights the importance of linking different approaches in order to understand small-scale fisheries spatial dynamics.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Shifts in Estuarine Macroinvertebrate Communities Associated With Water Quality and Climate Change - Thomas Goulding; Pedro M. Sousa; Gilda Silva; João Paulo Medeiros; Frederico Carvalho; Inês Metelo; Catarina Freitas; Nuno Lopes; Paula Chainho; José Lino Costa (Frontiers in Marine Science, 2021)
The present work aims to identify changes in the macroinvertebrate community of the Tagus estuary (Portugal) due to improvements in water quality and to climate change. Data was collected over a period of 16 years (1998–2014) from different sites located along the estuarine gradient. The AZTI Marine Biotic Index (AMBI) was used to assess the ecological quality status based on benthic invertebrate communities and identify possible variations associated with changes in water quality. The overall distribution of each species was examined to detect possible changes associated with climate, based on species’ affinity for more temperate or subtropical climates. Results demonstrate that there was an overall improvement of AMBI scores during the assessment period. The analysis of the geographical distribution of benthic species seems to indicate that there has been an increase of species which prefer subtropical climates in the shallower waters of the estuary, whereas in the deeper estuarine sections the propensity is for species that prefer temperate climates.

North African dust intrusions and increased risk of respiratory diseases in Southern Portugal - T. Silva; M. Fragoso; R. Almendra; J. Vasconcelos; A. Lopes; A. Faleh (International Journal of Biometeorology, 2021)
The study of dust intrusions in Portugal is still a subject on which little investigation has been made, especially in terms of their effects. Thus, this work aims to achieve two goals: firstly, to characterize the dust intrusions in the study area; and secondly, to evaluate the possible statistical association between the dust intrusion days and hospital admissions due to respiratory diseases. Dust intrusions in Portugal are prevalent during the summer season. During this season, the dust plumes tend to cover broader areas than in the other seasons and they have origin in the North African countries. In the study area for the period between 2005 and 2015, the relative risk of urgent hospitalizations due to respiratory diseases was 12.6% higher during dust intrusion days. In order to obtain this statistical association, a Distributed Lag Nonlinear Model was developed. With this work, we expect to help the development of further studies regarding North African dust intrusions in Portugal, more precisely their effects on human health.

Large-scale Degradation of the Tocantins-Araguaia River Basin - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Alberto Akama; José Dilermando Andrade Filho; Valter M. Azevedo-Santos; Marcus Vinicius Moreira Barbosa; Luis Mauricio Bini; Marcelo Fulgêncio Guedes Brito; Carlos Roberto dos Anjos Candeiro; Érica Pellegrini Caramaschi; Priscilla Carvalho; Rodrigo Assis de Carvalho; et al. (Environmental Management, 2021)

Phylogenetically and morphologically close ambush piscivores can elicit different antipredatory responses in characid prey - Taise M. Lopes; Rafaela V. Granzotti; Anielly G. Oliveira; Matheus T. Baumgartner; Bruno R. S. Figueiredo; Luiz C. Gomes (Environmental Biology of Fishes, 2021)

Genome size variation in Cactaceae and its relationship with invasiveness and seed traits - Sara Lopes; Lucie Mota; Mariana Castro; Gabrielle Nobre; Ana Novoa; David M. Richardson; João Loureiro; Sílvia Castro (Biological Invasions, 2021)

What fisher diets reveal about fish stocks - Priscila F. M. Lopes; Natália Hanazaki; Elaine M. Nakamura; Svetlana Salivonchyk; Alpina Begossi (Ambio, 2021)

The inter‐annual fishing variability in Octopus insularis (Leite & Haimovici 2008) as a result of oceanographic factors - Priscila F. M. Lopes; Lorena C. A. Andrade; Maria Grazia Pennino; Tatiana S. Leite (Fisheries Oceanography, 2021)
Octopus insularis , despite being widely fished from Brazil to Mexico, has only recently been described as a different species from the sympatric Octopus vulgaris complex in the tropical Atlantic, where its occurrence is determined by different environmental factors. Using a 10‐year time series from Brazil, we modeled how topographic aspects and oceanographic variables affected the landings of O . insularis . For that we used a locally weighted scatterplot smoothing (LOESS) technique and residual autocovariate‐boosted regression trees (RAC‐BRTs). In addition to the octopus landing per unit effort (LPUE) being driven by the seafloor structure, we also observed that it was directly related to the temperature and inversely related to chlorophyll. Higher LPUEs were observed in warmer years. Although the relationship between LPUE and chlorophyll or temperature has not yet been explained under laboratorial conditions, the higher catches observed at higher temperatures may be both a result of the local fishing dynamics and a warning toward the possibility of future niche expansion, due to climate change. If the latter is confirmed, octopus fisheries in parts of the South Atlantic would need to adapt to a smaller, and thus cheaper, body‐sized species.

Acute Ecotoxicity of Exposure to Sugarcane Ashes on the Behaviour of Predator and Prey Fish Species - Katia Y. Yofukuji; Gabriel M. R. Gonino; Gustavo H. Z. Alves; Taise M. Lopes; Bruno R. S. Figueiredo (Water, Air, & Soil Pollution, 2021)

Exploration of marine genus Chroococcidiopsis sp.: a valuable source for antioxidant industry? - Joana Assunção; Helena M. Amaro; Graciliana Lopes; Tânia Tavares; F. Xavier Malcata; A. Catarina Guedes (Journal of Applied Phycology, 2021)

Variants in GCNA, X-linked germ-cell genome integrity gene, identified in men with primary spermatogenic failure - Jimmaline J. Hardy; Margot J. Wyrwoll; William Mcfadden; Agnieszka Malcher; Nadja Rotte; Nijole C. Pollock; Sarah Munyoki; Maria V. Veroli; Brendan J. Houston; Miguel J. Xavier; Laura Kasak; Margus Punab; et al. (Human Genetics, 2021)

The conservation status of the world’s freshwater molluscs - Monika Böhm; Nadia I. Dewhurst-Richman; Mary Seddon; Sophie E. H. Ledger; Christian Albrecht; David Allen; Arthur E. Bogan; Jay Cordeiro; Kevin S. Cummings; Annabelle Cuttelod; Gustavo Darrigran; Will Darwall; et al. (Hydrobiologia, 2021)

Phylogeographic study of the West Australian freshwater mussel, Westralunio carteri, uncovers evolutionarily significant units that raise new conservation concerns - M. W. Klunzinger; Manuel Lopes-Lima; Andre Gomes-dos-Santos; Elsa Froufe; A. J. Lymbery; L. Kirkendale (Hydrobiologia, 2021)

Numerical Prediction of the Boundary-Layer Flow Over the Bolund Hill: Assessment of Turbulence Models and Advection Schemes - A. M. G. Lopes; N. G. L. Duarte; O. H. Sánchez; R. Daus; H. Koch (Boundary-Layer Meteorology, 2021)

The Missing Layers: Integrating Sociocultural Values Into Marine Spatial Planning - Maria Grazia Pennino; Stephanie Brodie; André Frainer; Priscila F. M. Lopes; Jon Lopez; Kelly Ortega-Cisneros; Samiya Selim; Natasa Vaidianu (Frontiers in Marine Science, 2021)
Graphical Abstract

Look Who’s Asking—Reflections on Participatory and Transdisciplinary Marine Research Approaches - Annette Breckwoldt; Priscila F. M. Lopes; Samiya A. Selim (Frontiers in Marine Science, 2021)
Marine conservation transdisciplinary researchers often get to the field with a previously designed question, often formulated outside the actual geographical, social, cultural and ecological setting in which the research projects are supposed to be anchored. Involving people on the ground in the initial phase of formulating the questions and setting the research agenda is still uncommon. Once in the field, transdisciplinary researchers may or may not have the support of local communities to sample their data, although they will regularly need to count on these same communities if a collaborative regime is to be pursued and informed by the research outcome. This paper discusses measures that can be taken by marine fisheries and marine conservation researchers to improve participation in, and ownership of, the research by local counterparts, most importantly members of the communities where research is being conducted. The data was generated with a purposively sampled survey of 18 members of our research networks. Key proposed measures derived from this data include: (1) build rapport; (2) engage and exchange; (3) be accommodating and attentive; and (4) be respectful. Knowing who is asking the questions and assuring that all stakeholders have a voice in this process becomes especially relevant under extreme circumstances (e.g., disasters, pandemics), when problems are numerous but can only be accessed by those on the ground. We advise for faster progress in transforming academic and funding environments for true “level-playing-field” transdisciplinary and co-designed research projects that can help change top-down research tendencies.

Reassessing the Use of Undecanoic Acid as a Therapeutic Strategy for Treating Fungal Infections - Antonio Rossi; Maíra P. Martins; Tamires A. Bitencourt; Nalu T. A. Peres; Carlos H. L. Rocha; Flaviane M. G. Rocha; João Neves-da-Rocha; Marcos E. R. Lopes; Pablo R. Sanches; Júlio C. Bortolossi; Nilce M. Martinez-Rossi (Mycopathologia, 2021)

Motor Deficits Coupled to Cerebellar and Striatal Alterations in Ube3am−/p+ Mice Modelling Angelman Syndrome Are Attenuated by Adenosine A2A Receptor Blockade - Ana Moreira-de-Sá; Francisco Q. Gonçalves; João P. Lopes; Henrique B. Silva; Ângelo R. Tomé; Rodrigo A. Cunha; Paula M. Canas (Molecular Neurobiology, 2021)

The role of anthropogenic habitats in freshwater mussel conservation - Ronaldo Sousa; Dariusz Halabowski; Anna M. Labecka; Karel Douda; Olga Aksenova; Yulia Bespalaya; Ivan Bolotov; Juergen Geist; Hugh A. Jones; Ekaterina Konopleva; Michael W. Klunzinger; Carlos A. Lasso; et al. (Global Change Biology, 2021)
Anthropogenic freshwater habitats may provide undervalued prospects for long‐term conservation as part of species conservation planning. This fundamental, but overlooked, issue requires attention considering the pace that humans have been altering natural freshwater ecosystems and the accelerated levels of biodiversity decline in recent decades. We compiled 709 records of freshwater mussels (Bivalvia, Unionida) inhabiting a broad variety of anthropogenic habitat types (from small ponds to large reservoirs and canals) and reviewed their importance as refuges for this faunal group. Most records came from Europe and North America, with a clear dominance of canals and reservoirs. The dataset covered 228 species, including 34 threatened species on the IUCN Red List. We discuss the conservation importance and provide guidance on how these anthropogenic habitats could be managed to provide optimal conservation value to freshwater mussels. This review also shows that some of these habitats may function as ecological traps owing to conflicting management practices or because they act as a sink for some populations. Therefore, anthropogenic habitats should not be seen as a panacea to resolve conservation problems. More information is necessary to better understand the trade‐offs between human use and the conservation of freshwater mussels (and other biota) within anthropogenic habitats, given the low number of quantitative studies and the strong biogeographic knowledge bias that persists.

Protease-activated receptor 4 plays a role in lipopolysaccharide-induced inflammatory mechanisms in murine macrophages - A. Barra; K. M. Freitas; D. G. Marconato; P. Faria-Pinto; M. T. P. Lopes; André Klein (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Anthropogenic deposition increases nitrogen-phosphorus imbalances in tree vegetation, litter and soil of Atlantic Forest remnants - Giovanna Boccuzzi; Ricardo K. Nakazato; Milton A. G. Pereira; Mirian C. S. Rinaldi; Marcia I. M. S. Lopes; Marisa Domingos (Plant and Soil, 2021)

AMPAr GluA1 Phosphorylation at Serine 845 in Limbic System Is Associated with Cardiac Autonomic Tone - Hiago Murilo Melo; Cristiane Ribeiro de Carvalho; Alexandre Ademar Hoeller; Jefferson Luiz Brum Marques; Marcelo Neves Linhares; Mark William Lopes; Guilherme Loureiro Fialho; Peter Wolf; Katia Lin; Zuner A. Bortolotto; Jeremy M. Henley; André D’Ávila; et al. (Molecular Neurobiology, 2021)

Ingestion of anthropogenic materials by yellow-legged gulls (Larus michahellis) in natural, urban, and landfill sites along Portugal in relation to diet composition - Catarina S. Lopes; Vitor H. Paiva; Patrícia T. Vaz; Joana Pais de Faria; Joana G. Calado; Jorge M. Pereira; Jaime A. Ramos (Environmental Science and Pollution Research, 2021)

Low Densities of the Ghost Crab Ocypode quadrata Related to Large Scale Human Modification of Sandy Shores - Carlos A. M. Barboza; Gustavo Mattos; Abílio Soares-Gomes; Ilana Rosental Zalmon; Leonardo Lopes Costa (Frontiers in Marine Science, 2021)
Sandy beaches are the most common ecosystems of coastal regions and provide direct and indirect essential services for millions of people, such as coastal protection, fishing, tourism, and recreational activities. However, the natural habitats of sandy shores are being modified at rates never experienced before, making beaches key monitoring sites of marine ecosystems worldwide. The ghost crab species Ocypode quadrata is the most conspicuous crustacean of sandy beaches along the Western Atlantic coast and has been successfully used as an indicator of anthropogenic disturbance and environmental variability. To investigate the potential role of a “triple whammy” [(1) urbanization; (2) use of resources; (3) decreasing resilience] on the most common bioindicator of sandy shores, we compiled a dataset including 214 records of burrows density from 94 microtidal sandy beach sectors covering a range of over 65° of latitude. The response of burrows density to synergetic effects of human modification of natural systems and environmental changes was investigated using linear models. We used the cumulative Human Modification (HMc) index, a standardized geographic projection of changes of natural systems, as a predictor of urbanization, industrialization and use of resources. The predictor wave energy, tidal range and temperature (sea surface and air) were included as potential effects of climate changes. Literature review showed records mainly concentrated at sub-tropical and temperate regions. HMc values were clearly negatively related to burrows density, thereby supporting an effect of modification of natural habitat at large spatial scale. Sea surface temperature and air temperature were positive related with density and the lack of a general pattern of the relationship between burrows density, interactions between wave energy and tide range, supported unclear patterns reported at regional scales. Finally, we argue that ghost crabs are valuable targets for protection actions on sandy beaches that can benefit coexisting species and provide natural habitat conservation.

Allometry, Function and Shape Diversification in the Inner Ear of Platyrrhine Primates - Joaquin del Rio; Leandro Aristide; Sergio F. dos Reis; Thais M. P. dos Santos; Ricardo T. Lopes; S. Ivan Perez (Journal of Mammalian Evolution, 2021)

Application of rhamnolipid surfactant for remediation of toxic metals of long- and short-term contamination sites - C. S. C. Lopes; D. B. Teixeira; B. F. Braz; R. E. Santelli; L. V. A. de Castilho; J. G. C. Gomez; R. P. V. Castro; L. Seldin; D. M. G. Freire (International Journal of Environmental Science and Technology, 2021)

Special issue on sporotrichosis: challenges to deal with the new emerging pathogenic species - Leila M. Lopes-Bezerra; Sandro Rogério de Almeida (Brazilian Journal of Microbiology, 2021)

Guideline for the management of feline sporotrichosis caused by Sporothrix brasiliensis and literature revision - Isabella Dib Ferreira Gremião; Elisabeth Martins da Silva da Rocha; Hildebrando Montenegro; Aroldo José Borges Carneiro; Melissa Orzechowski Xavier; Marconi Rodrigues de Farias; Fabiana Monti; Wilson Mansho; Romeika Herminia de Macedo Assunção Pereira; Sandro Antonio Pereira; Leila M. Lopes-Bezerra (Brazilian Journal of Microbiology, 2021)

Promising application of the SsCBF ELISA test to monitor the therapeutic response of feline sporotrichosis caused by Sporothrix brasiliensis from Brazilian epidemics - Vivian S. Baptista; Gabriele Barros Mothé; Giulia M. P. Santos; Carla Stefany I. Melivilu; Thayana O. Santos; Emylli D. Virginio; Pãmella A. de Macêdo-Sales; Márcia Ribeiro Pinto; Ricardo Luiz D. Machado; Elisabeth M. S. Rocha; Leila Maria Lopes-Bezerra; Andréa Regina S. Baptista (Brazilian Journal of Microbiology, 2021)

Local ecological knowledge to assist conservation status assessments in data poor contexts: a case study with the threatened sharks of the Brazilian Northeast - Antoine O. H. C. Leduc; Fábio H. D. De Carvalho; Nigel E. Hussey; José Amorim Reis-Filho; Guilherme O. Longo; Priscila F. M. Lopes (Biodiversity and Conservation, 2021)

Influence of Urban Landscape on Ants and Spiders Richness and Composition in Forests - T S Melo; E F Moreira; M V A Lopes; A R S Andrade; A D Brescovit; M C L Peres; J H C Delabie (Neotropical Entomology, 2021)

Diversity of Colletotrichum species causing onion anthracnose in Brazil - Luiz Henrique R. Lopes; Leonardo S. Boiteux; Maurício Rossato; Frederick M. Aguiar; Maria E. N. Fonseca; Valter R. Oliveira; Ailton Reis (European Journal of Plant Pathology, 2021)

Chemometric tools applied to optimize a fast solid-phase microextraction method for analysis of polycyclic aromatic hydrocarbons in produced water - Pedro Hermano M. Vasconcelos; André Luiz M. Camelo; Ari Clecius A. de Lima; Hélio O. do Nascimento; Carla B. Vidal; Ronaldo F. do Nascimento; Gisele S. Lopes; Elisane Longhinotti (Environmental Science and Pollution Research, 2021)

Magnetic resonance imaging features of COVID-19-related cranial nerve lesions - Diogo Goulart Corrêa; Luiz Celso Hygino da Cruz; Fernanda Cristina Rueda Lopes; Cláudio de Carvalho Rangel; Anna Luiza de Araújo Henriques Tessarollo; Karla Cristina Godeiro Coelho; Rafael Zandonadi Brandão; Ricardo Augusto Faro Novis; Shenia Sbardellotto Colnaghi Novis; Rodrigo Silveira; Viviane T. Carvalho; Osvaldo J. M. Nascimento (Journal of NeuroVirology, 2021)

Thin layers in the coastal zone of Ubatuba, Brazil: Mechanisms of formation and dissipation - Silvana B. Penninck; Rubens M. Lopes; Josiane F. Lima; Margaret A. McManus (Limnology and Oceanography, 2021)
Thin layers are vertically compressed, horizontally extensive, highly concentrated features comprised of plankton and/or particles. They are critical components of the marine ecosystem, likely playing a key role in the life histories and evolutionary trajectories of species found in, or, interacting with them. These structures have been reported in diverse marine environments around the globe. However, the mechanisms of thin layer formation/dissipation in the southwestern Atlantic Ocean were unknown until this contribution. To assess the temporal evolution of thin phytoplankton layers on the inner shelf off Ubatuba, Brazil, we conducted two oceanographic fixed station cruises, including optics, acoustics, and imaging techniques. Over a period of 2 days, three thin layers were observed: within the pycnocline close to the maximum stratification, and below the pycnocline where phytoplankton were affected by enhanced nutrient supply provided by the South Atlantic Central Water (SACW). Changes in regional wind patterns influenced the presence of SACW, which directly affected shear and stratification: the primary physical mechanisms we attribute to thin layer formation in this region. The associated biological mechanisms contributing to thin layer formation were biomass accumulation (in situ growth) and likely the mobility of dinoflagellates. The dominant organisms in the thin layer depths and surroundings, by our in situ imaging system, were cyanobacteria, diatoms, dinoflagellates, and crustaceans. Thin Layers likely have crucial importance for meso‐oligotrophic environments, representing important feeding resources for higher trophic levels.

Water temperature control on CO 2 flux and evaporation over a subtropical seagrass meadow revealed by atmospheric eddy covariance - Bryce R. Van Dam; Christian C. Lopes; Pierre Polsenaere; René M. Price; Anna Rutgersson; James W. Fourqurean (Limnology and Oceanography, 2021)
Subtropical seagrass meadows play a major role in the coastal carbon cycle, but the nature of air–water CO 2 exchanges over these ecosystems is still poorly understood. The complex physical forcing of air–water exchange in coastal waters challenges our ability to quantify bulk exchanges of CO 2 and water (evaporation), emphasizing the need for direct measurements. We describe the first direct measurements of evaporation and CO 2 flux over a calcifying seagrass meadow near Bob Allen Keys, Florida. Over the 78‐d study, CO 2 emissions were 36% greater during the day than at night, and the site was a net CO 2 source to the atmosphere of 0.27 ± 0.17 μ mol m −2 s −1 (x̅ ± standard deviation). A quarter (23%) of the diurnal variability in CO 2 flux was caused by the effect of changing water temperature on gas solubility. Furthermore, evaporation rates were ~ 10 times greater than precipitation, causing a 14% increase in salinity, a potential precursor of seagrass die‐offs. Evaporation rates were not correlated with solar radiation, but instead with air–water temperature gradient and wind shear. We also confirm the role of convective forcing on night‐time enhancement and day‐time suppression of gas transfer. At this site, temperature trends are regulated by solar heating, combined with shallow water depth and relatively consistent air temperature. Our findings indicate that evaporation and air–water CO 2 exchange over shallow, tropical, and subtropical seagrass ecosystems may be fundamentally different than in submerged vegetated environments elsewhere, in part due to the complex physical forcing of coastal air–sea gas transfer.

Lake sedimentary processes and vegetation changes over the last 45k cal a bp in the uplands of south‐eastern Amazonia - José Tasso Felix Guimarães; Prafulla Kumar Sahoo; Mariana Maha Jana Costa De Figueiredo; Karen da Silva Lopes; Markus Gastauer; Silvio Junio Ramos; Cecilio Frois Caldeira; Pedro Walfir M. Souza‐Filho; Luiza Santos Reis; Marcio Sousa Da Silva; Paulo Rogenes Pontes; Renato Oliveira Da Silva; et al. (Journal of Quaternary Science, 2021)
This study addresses paleoclimate influences in a southern Amazonia ecotone based on multiproxy records from lakes of the Carajás region during the last 45k cal a bp. Wet and cool environmental conditions marked the initial deposition in shallow depressions with detrital sediments and high weathering rates until 40k cal a bp. Concomitantly, forest and C3 canga plants, along with cool‐adapted taxa, developed; however, short drier episodes enabled expansion of C4 plants and diagenetic formation of siderite. A massive event of siderite formation occurred approximately 30k cal a bp under strong drier conditions. Afterwards, wet and cool environmental conditions returned and persisted until the Last Glacial Maximum (LGM). The LGM was marked by lake‐level lowstands and subaerial exposure. The transition from the LGM to the Holocene is marked by the onset of oscillations in temperature and humidity, with an expansion of forest and canga plants. Cool taxa were present for the last time in the Carajás region ~ 9.5–9k cal a bp. After 10k cal a bp , shallow lakes became upland swamps due to natural infilling processes, but the current vegetation types and structures of the plateaus were acquired only after 3k cal a bp under wetter climatic conditions.

Correction to: Disruption of human meiotic telomere complex genes TERB1, TERB2 and MAJIN in men with non-obstructive azoospermia - Albert Salas-Huetos; Frank Tüttelmann; Margot J. Wyrwoll; Sabine Kliesch; Alexandra M. Lopes; João Gonçalves; Steven E. Boyden; Marius Wöste; James M. Hotaling; Liina Nagirnaja; Donald F. Conrad; Douglas T. Carrell; et al. (Human Genetics, 2021)

Disruption of human meiotic telomere complex genes TERB1, TERB2 and MAJIN in men with non-obstructive azoospermia - Albert Salas-Huetos; Frank Tüttelmann; Margot J. Wyrwoll; Sabine Kliesch; Alexandra M. Lopes; João Goncalves; Steven E. Boyden; Marius Wöste; James M. Hotaling; Liina Nagirnaja; Donald F. Conrad; Douglas T. Carrell; et al. (Human Genetics, 2021)

Serendipita restingae sp. nov. (Sebacinales): an orchid mycorrhizal agaricomycete with wide host range - Yohan Fritsche; Morgana E. Lopes; Marc-André Selosse; Valdir M. Stefenon; Miguel P. Guerra (Mycorrhiza, 2021)

Proximal sensors for monitoring seasonal changes of feeding sites selected by grazing ewes - João Serrano; E. Sales-Baptista; Shakib Shahidian; J. Marques da Silva; I. Ferraz de Oliveira; J. Lopes de Castro; Alfredo Pereira; M. Cancela d’Abreu; Mário de Carvalho (Agroforestry Systems, 2021)

Microbial valorization of waste cooking oils for valuable compounds production – a review - Marlene Lopes; Sílvia M. Miranda; Isabel Belo (Critical Reviews in Environmental Science and Technology, 2020)

Correction to: α-Phellandrene attenuates tissular damage, oxidative stress, and TNF-α levels on acute model ifosfamide-induced hemorrhagic cystitis in mice - R. L. G. Gonçalves; F. V. M. Cunha; B. P. S. Sousa-Neto; L. S. A. Oliveira; M. E. Lopes; D. C. Rezende; I. J. O. Sousa; K. M. Nogueira; L. K. M. Souza; J. V. R. Medeiros; D. V. T. Wong; V. M. P. Pereira; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Microbial Control of Leptopharsa heveae Drake & Poor (Hemiptera: Tingidae) in Brazilian Rubber Tree Plantations: a Brief Historical Account and Identification of Entomopathogenic Fungi by Means of Multigene Phylogeny - M Faria; D A de Souza; R B Lopes (Neotropical Entomology, 2020)

Factorial optimization of upstream process for Cyanobium sp. pigments production - Fernando Pagels; Daniel Salvaterra; Helena M Amaro; Graciliana Lopes; Isabel Sousa-Pinto; Vitor Vasconcelos; A. Catarina Guedes (Journal of Applied Phycology, 2020)

Macrophage polarization in intestinal inflammation and gut homeostasis - Tamara Cristina Moreira Lopes; David M. Mosser; Ricardo Gonçalves (Inflammation Research, 2020)

Selection of host plants for vector transmission assays of citrus variegated chlorosis strains of Xylella fastidiosa subsp. pauca - Mariana B. Esteves; Heloisa T. Kleina; Tiago de M. Sales; João R. S. Lopes (European Journal of Plant Pathology, 2020)

Impact of traffic emissions on air quality in Cabo Verde - Sandra M. Freire; Helder Relvas; Myriam Lopes (Environmental Monitoring and Assessment, 2020)

Acute and chronic toxicity of 2,4-D and fipronil formulations (individually and in mixture) to the Neotropical cladoceran Ceriodaphnia silvestrii - Laís C. M. Silva; Raquel A. Moreira; Thandy J. S. Pinto; Allan P. Ogura; Maria P. C. Yoshii; Laís F. P. Lopes; Cassiana C. Montagner; Bianca V. Goulart; Michiel A. Daam; Evaldo L. G. Espíndola (Ecotoxicology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Losing Genes: The Evolutionary Remodeling of Cetacea Skin - Gonçalo Espregueira Themudo; Luís Q. Alves; André M. Machado; Mónica Lopes-Marques; Rute R. da Fonseca; Miguel Fonseca; Raquel Ruivo; L. Filipe C. Castro (Frontiers in Marine Science, 2020)

α-Phellandrene attenuates tissular damage, oxidative stress, and TNF-α levels on acute model ifosfamide-induced hemorrhagic cystitis in mice - R. L. G. Gonçalves; F. V. M. Cunha; B. P. S. Sousa-Neto; L. S. A. Oliveira; M. E. Lopes; D. C. Rezende; I. J. O. Sousa; K. M. Nogueira; L. K. M. Souza; J. V. R. Medeiros; D. V. T. Wong; V. M. P. Pereira; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

First Report of HLB Causal Agent in Psyllid in State of Bahia, Brazil - E. F. M. Abreu; A. C. Lopes; A. M. Fernandes; S. X. B. Silva; C. J. Barbosa; A. S. Nascimento; F. F. Laranjeira; E. C. Andrade (Neotropical Entomology, 2020)

Differential diagnosis of asthma and restrictive respiratory diseases by combining forced oscillation measurements, machine learning and neuro-fuzzy classifiers - Jorge L. M. Amaral; Alexandre G. Sancho; Alvaro C. D. Faria; Agnaldo J. Lopes; Pedro L. Melo (Medical & Biological Engineering & Computing, 2020)

Bioactive potential of Cyanobium sp. pigment-rich extracts - Fernando Pagels; Daniel Salvaterra; Helena M. Amaro; Graciliana Lopes; Isabel Sousa-Pinto; Vitor Vasconcelos; A. Catarina Guedes (Journal of Applied Phycology, 2020)

Genome-Wide DNA Methylation Analysis Reveals a Conserved Epigenetic Response to Seasonal Environmental Variation in the Staghorn Coral Acropora cervicornis - Javier A. Rodríguez-Casariego; Alex E. Mercado-Molina; Daniel Garcia-Souto; Ivanna M. Ortiz-Rivera; Christian Lopes; Iliana B. Baums; Alberto M. Sabat; Jose M. Eirin-Lopez (Frontiers in Marine Science, 2020)

Multiorgan histopathological changes in the juvenile seabream Sparus aurata as a biomarker for zinc oxide particles toxicity - Asfina Beegam; Maria Lopes; Tiago Fernandes; Jiya Jose; Angela Barreto; Miguel Oliveira; Amadeu M. V. M. Soares; Tito Trindade; Sabu Thomas; Maria L. Pereira (Environmental Science and Pollution Research, 2020)

Low-cost small-scale distillation column: assessment of polymeric materials on its economic, chemical, mechanical, and environmental performance - C. B. Cunha; M. Brondani; F. D. Mayer; P. P. Lopes; R.Hoffmann (Clean Technologies and Environmental Policy, 2020)

The best of heavy queens: influence of post-flight weight on queens’ survival and productivity in Acromyrmex subterraneus (Forel, 1893) (Hymenoptera: Formicidae) - T. A. Sales; A. M. O. Toledo; J. F. S. Lopes (Insectes Sociaux, 2020)

Insights into the heterochromatin evolution in the genus Melipona (Apidae: Meliponini) - M. S. Cunha; L. A. O. Campos; D. M. Lopes (Insectes Sociaux, 2020)

Origin and history of Phoxinus (Cyprinidae) introductions in the Douro Basin (Iberian Peninsula): an update inferred from genetic data - Aina Garcia-Raventós; Filipa M. S. Martins; Amilcar Teixeira; Ronaldo Sousa; Elsa Froufe; Simone Varandas; Manuel Lopes-Lima; Pedro Beja; Ana Filipa Filipe (Biological Invasions, 2020)

An unusual bidentate methionine ruthenium(II) complex: photo-uncaging and antimicrobial activity - Aurideia P. de Sousa; Ana C. S. Gondim; Eduardo H. S. Sousa; Mayron A. de Vasconcelos; Edson H. Teixeira; Beatriz Pinheiro Bezerra; Alejandro Pedro Ayala; Patrícia H. R. Martins; Luiz Gonzaga de França Lopes; Alda K. M. Holanda (JBIC Journal of Biological Inorganic Chemistry, 2020)

Which are the best environmental conditions for catching the beach‐seine target species? A Portuguese case study - Célia M. Teixeira; Priscila M. Silva; Rita Gamito; Sandra Amoroso; Nuno Lopes; Catarina Freitas; Henrique N. Cabral; José L. Costa (Fisheries Oceanography, 2020)
The beach‐seine fishery is a commercial fishing activity on the Portuguese coast, with reports dating as far back as the early 15th century. The main target species of this fishery are small pelagic fish such as Atlantic chub mackerel, Atlantic horse mackerel and sardine. To identify the best conditions for fishing the target species, catches of beach seine (2007–2017) were used and generalized linear models were applied, using a binomial and gamma distributions. The logistic model explained between 36.3% and 45.7% of the catches variability; the gamma model explained 9.1% and 46.9% of the catches variability, being month and wind direction the best covariates for the occurrence and/or abundance of the three small pelagic fishes in analysis. If the effort is directed to the days that meet the conditions found for each species (sardine: between May and October, wind NW, daytime; Atlantic horse mackerel: May, NW/NE wind, 800 m from the coastline; Atlantic chub mackerel: from July to August, NW moderate wind), a reduction in bycatch and discards can be achieved. This approach can have a positive economic and social impact, since it provides information for turning fisheries more efficient.

Numerical modeling of free and submerged labyrinth weir flow for a large sidewall angle - José M. Carrillo; Jorge Matos; Ruth Lopes (Environmental Fluid Mechanics, 2020)

Urban wild meat consumption and trade in central Amazonia - Hani R. El Bizri; Thaís Q. Morcatty; João Valsecchi; Pedro Mayor; Jéssica E. S. Ribeiro; Carlos F. A. Vasconcelos Neto; Jéssica S. Oliveira; Keilla M. Furtado; Urânia C. Ferreira; Carlos F. S. Miranda; Ciclene H. Silva; Valdinei L. Lopes; et al. (Conservation Biology, 2020)
The switch from hunting wild meat for home consumption to supplying more lucrative city markets in Amazonia can adversely affect some game species. Despite this, information on the amounts of wild meat eaten in Amazonian cities is still limited. We estimated wild meat consumption rates in 5 cities in the State of Amazonas in Brazil through 1046 door‐to‐door household interviews conducted from 2004 to 2012. With these data, we modeled the relationship between wild meat use and a selection of socioeconomic indices. We then scaled up our model to determine the amounts of wild meat likely to be consumed annually in the 62 urban centers in central Amazonia. A total of 80.3% of all interviewees reported consuming wild meat during an average of 29.3 (CI 11.6) days per year. Most wild meat was reported as bought in local markets (80.1%) or hunted by a family member (14.9%). Twenty‐one taxa were cited as consumed, mostly mammals (71.6%), followed by reptiles (23.2%) and then birds (5.2%). The declared frequency of wild meat consumption was positively correlated with the proportion of rural population as well as with the per capita gross domestic product of the municipality (administrative divisions) where the cities were seated. We estimated that as much as 10,691 t of wild meat might be consumed annually in the 62 urban centers within central Amazonia, the equivalent of 6.49 kg per person per year. In monetary terms, this amounts to US$21.72 per person per year or US$35.1 million overall, the latter figure is comparable to fish and timber production in the region. Given this magnitude of wild meat trade in central Amazonia, it is fundamental to integrate this activity into the formal economy and actively develop policies that allow the trade of more resilient taxa and restrict trade in species sensitive to hunting.

Afferent innervation of the ischemic kidney contributes to renal dysfunction in renovascular hypertensive rats - Nathalia R. Lopes; Maycon I. O. Milanez; Beatriz S. Martins; Amanda C. Veiga; Giovanna R. Ferreira; Guiomar N. Gomes; Adriana C. Girardi; Polliane M. Carvalho; Fernando N. Nogueira; Ruy R. Campos; Cássia T. Bergamaschi; Erika E. Nishi (Pflügers Archiv - European Journal of Physiology, 2020)

Diversity and ecology of cultivable fungi isolated from the thermal soil gradients in Deception Island, Antarctica - Hebert M. Figueredo; Vívian N. Gonçalves; Valéria M. Godinho; Daví V. Lopes; Fabio S. Oliveira; Luiz H. Rosa (Extremophiles, 2020)

Lysophosphatidylcholine triggers cell differentiation in the protozoan parasite Herpetomonas samuelpessoai through the CK2 pathway - Fernando L. Dutra; Danielle P. Vieira; Felipe S. Coelho; Camila M. Adade; Geórgia C. Atella; Mário A. C. Silva Neto; Angela H. Lopes (Acta Parasitologica, 2020)

Decadal losses of canopy‐forming algae along the warm temperate coastline of Brazil - Daniel Gorman; Paulo Horta; Augusto A. V. Flores; Alexander Turra; Flávio Augusto de Souza Berchez; Manuela B. Batista; Euro S. Lopes Filho; Mariana S. Melo; Barbara L. Ignacio; Ivan M. Carneiro; Roberto C. Villaça; Maria Teresa M. Széchy (Global Change Biology, 2020)
The loss of canopy‐forming seaweeds from urbanized coasts has intensified in response to warming seas and non‐climatic pressures such as population growth and declining water quality. Surprisingly, there has been little information on the extent of historical losses in the South‐western Atlantic, which limits our ability to place this large marine ecosystem in a global context. Here, we use meta‐analysis to examine long‐term (1969–2017) changes to the cover and biomass of Sargassum spp. and structurally simple algal turfs along more than 1,000 kilometres of Brazil's warm temperate coastline. Analysis revealed major declines in canopy cover that were independent of season (i.e., displaying similar trends for both summer and winter) but varied with coastal environmental setting, whereby sheltered bays experienced greater losses than coastal locations. On average, covers of Sargassum spp. declined by 2.6% per year, to show overall losses of 52% since records began (ranging from 20% to 89%). This contrasted with increases in the cover of filamentous turfs (24% over the last 27 years) which are known to proliferate along human‐impacted coasts. To test the relative influence of climatic versus non‐climatic factors as drivers of this apparent canopy‐to‐turf shift, we examined how well regional warming trends (decadal changes to sea surface temperature) and local proxies of coastal urbanization (population density, thermal pollution, turbidity and nutrient inputs) were able to predict the changes in seaweed communities. Our results revealed that the most pronounced canopy losses over the past 50 years were at sites exhibiting the greatest degree of coastal warming, the highest population growth and those located in semi‐enclosed sheltered bays. These findings contribute knowledge on the drivers of canopy loss in the South‐western Atlantic and join with global efforts to understand and mitigate declines of marine keystone species.

Removal of Zn and Cd from Overlying Water by Mangrove Sediments: Testing the Effects of Sediment Resuspension/Redeposition Events - K. N. Suzuki; R. J. M. Castro; M. N. Sondermann; E. C. Machado; A. B. Bellido; R. T. Lopes; W. Machado (Water, Air, & Soil Pollution, 2020)

Marker-assisted selection in Gossypium spp. for Meloidogyne incognita resistance and histopathological characterization of a near immune line - C. M. L. Lopes; N. D. Suassuna; J. E. Cares; A. C. M. M. Gomes; F. J. Perina; G. F. Nascimento; J. S. F. Mendonça; A. W. Moita; R. M. D. G. Carneiro (Euphytica, 2020)

A new computational model for flow in karst-carbonates containing solution-collapse breccias - Tuane V. Lopes; Aline C. Rocha; Marcio A. Murad; Eduardo L. M. Garcia; Patricia A. Pereira; Caroline L. Cazarin (Computational Geosciences, 2020)

Artemisia annua L. and photoresponse: from artemisinin accumulation, volatile profile and anatomical modifications to gene expression - Ellen M. Lopes; Fábia Guimarães-Dias; Thália do S. S. Gama; Arthur L. Macedo; Alessandra L. Valverde; Marcela C. de Moraes; Ana Cristina A. de Aguiar-Dias; Humberto R. Bizzo; Marcio Alves-Ferreira; Eliana S. Tavares; Andrea F. Macedo (Plant Cell Reports, 2020)

Electricity Production from Sugarcane Straw Recovered Through Bale System: Assessment of Retrofit Projects - Isabelle L. M. Sampaio; Terezinha F. Cardoso; Nariê R. D. Souza; Marcos D. B. Watanabe; Danilo J. Carvalho; Antonio Bonomi; Tassia Lopes Junqueira (BioEnergy Research, 2019)

Removal of bromate from drinking water using a heterogeneous photocatalytic mili-reactor: impact of the reactor material and water matrix - Gustavo S. Cunha; Sara G. S. Santos; Bianca M. Souza-Chaves; Tânia F.C.V. Silva; João Paulo Bassin; Márcia W.C. Dezotti; Rui A.R. Boaventura; Madalena M. Dias; José Carlos B. Lopes; Vítor J.P. Vilar (Environmental Science and Pollution Research, 2019)

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

Unveiling the binding and orientation of the antimicrobial peptide Plantaricin 149 in zwitterionic and negatively charged membranes - Patricia S. Kumagai; Victor K. Sousa; Maressa Donato; Rosangela Itri; Leila M. Beltramini; Ana P. U. Araujo; Jochen Buerck; B. A. Wallace; Jose L. S. Lopes (European Biophysics Journal, 2019)

Biogeographic differences in the allelopathy of leaf surface extracts of an invasive weed - Ramona E. Irimia; Susana M. M. Lopes; Gastón Sotes; Lohengrin A. Cavieres; Özkan Eren; Christopher J. Lortie; Kristine French; José L. Hierro; Christoph Rosche; Ragan M. Callaway; Teresa M. V. D. Pinho e Melo; Daniel Montesinos (Biological Invasions, 2019)

Multispecies biofilm formation by the contaminating microbiota in raw milk - G. S. Oliveira; D. R. G. Lopes; C. Andre; C. C. Silva; F. Baglinière; M. C. D. Vanetti (Biofouling, 2019)

Pathological and microbiological characterization of mastitis in dairy cows - Ronaldo M. Bianchi; Claiton I. Schwertz; Bianca S. de Cecco; Welden Panziera; Cíntia De Lorenzo; Lilian C. Heck; Gustavo G. M. Snel; Bruna C. Lopes; Fernando S. da Silva; Saulo P. Pavarini; David Driemeier (Tropical Animal Health and Production, 2019)

Technical approaches to evaluate the surfactant-enhanced biodegradation of biodiesel and vegetable oils - R. N. Montagnolli; J. M. Cruz; J. R. Moraes; C. R. Mendes; G. Dilarri; P. R. M. Lopes; E. D. Bidoia (Environmental Monitoring and Assessment, 2019)

Non-Peptidergic Nociceptive Neurons Are Essential for Mechanical Inflammatory Hypersensitivity in Mice - Larissa G. Pinto; Guilherme R. Souza; Ricardo Kusuda; Alexandre H. Lopes; Morena B. Sant’Anna; Fernando Q. Cunha; Sérgio H. Ferreira; Thiago M. Cunha (Molecular Neurobiology, 2019)

Quantitative variations of Constrictotermes cyphergaster (Isoptera) instars over time in a Neotropical semiarid ecosystem - E. F. Lucena; A. Vasconcellos; A. O. Lopes; F. M. S. Moura (Insectes Sociaux, 2019)

Bad moon rising? The influence of the lunar cycle on amphibian roadkills - F. Mestre; H. Lopes; T. Pinto; L. G. Sousa; A. Mira; S. M. Santos (European Journal of Wildlife Research, 2019)

Proceedings of the fourth international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Christine B. Ambrosone; Reiko Nishihara; Hugo J. W. L. Aerts; Melissa Bondy; Nilanjan Chatterjee; Montserrat Garcia-Closas; Marios Giannakis; Jeffrey A. Golden; Yujing J. Heng; N. Sertac Kip; Jill Koshiol; et al. (Cancer Causes & Control, 2019)

Structure-based design of δ-lactones for new antifungal drug development: susceptibility, mechanism of action, and toxicity - Daiane F. Dalla Lana; Ânderson R. Carvalho; William Lopes; Marilene H. Vainstein; Luciano S. P. Guimarães; Mário L. Teixeira; Luis F. S. de Oliveira; Michel M. Machado; Saulo F. de Andrade; Marcus M. Sá; Theo V. C. Russo; Gustavo P. Silveira; et al. (Folia Microbiologica, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Ten tips for developing interdisciplinary socio-ecological researchers - Rachel Kelly; Mary Mackay; Kirsty L. Nash; Christopher Cvitanovic; Edward H. Allison; Derek Armitage; Aletta Bonn; Steven J. Cooke; Stewart Frusher; Elizabeth A. Fulton; Benjamin S. Halpern; Priscila F. M. Lopes; et al. (Socio-Ecological Practice Research, 2019)

The Impact of the Right Coronary Artery Geometric Parameters on Hemodynamic Performance - N. Pinho; L. C. Sousa; C. F. Castro; C. C. António; M. Carvalho; W. Ferreira; R. Ladeiras-Lopes; N. D. Ferreira; P. Braga; N. Bettencourt; S. I. S. Pinto (Cardiovascular Engineering and Technology, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Convergent inactivation of the skin-specific C-C motif chemokine ligand 27 in mammalian evolution - Mónica Lopes-Marques; Luís Q. Alves; Miguel M. Fonseca; Giulia Secci-Petretto; André M. Machado; Raquel Ruivo; L. Filipe C. Castro (Immunogenetics, 2019)

Labelling halophilic Archaea using 13C and 15N stable isotopes: a potential tool to investigate haloarchaea consumption by metazoans - R. M. A. Lopes-dos-Santos; Marleen De Troch; Peter Bossier; Gilbert Van Stappen (Extremophiles, 2019)

Choice of improved phenotyping methods for bean plant reactions to white mold by non-linear model adjustments of symptom progression - A. C. M. Porto; R. Gwinner; R. N. Miranda; F. S. Lopes; W. A. Pereira; M. Pasqual; J. B. Santos (Australasian Plant Pathology, 2019)

Globally Consistent Quantitative Observations of Planktonic Ecosystems - Fabien Lombard; Emmanuel Boss; Anya M. Waite; Meike Vogt; Julia Uitz; Lars Stemmann; Heidi M. Sosik; Jan Schulz; Jean-Baptiste Romagnan; Marc Picheral; Jay Pearlman; Mark D. Ohman; et al. (Frontiers in Marine Science, 2019)

Lipidomic signature of the green macroalgae Ulva rigida farmed in a sustainable integrated multi-trophic aquaculture - Diana Lopes; Ana S. P. Moreira; Felisa Rey; Elisabete da Costa; Tânia Melo; Elisabete Maciel; Andreia Rego; Maria H. Abreu; Pedro Domingues; Ricardo Calado; Ana I. Lillebø; M. Rosário Domingues (Journal of Applied Phycology, 2019)

Development of a road traffic emission inventory with high spatial–temporal resolution in the world’s most densely populated region—Macau - X. Li; D. Lopes; K. M. Mok; A. I. Miranda; K. V. Yuen; K. I. Hoi (Environmental Monitoring and Assessment, 2019)

α and β diversity of fishes in relation to a gradient of habitat structural complexity supports the role of environmental filtering in community assembly - Eduardo R. Cunha; Kirk O. Winemiller; João C. B. da Silva; Taise M. Lopes; Luiz C. Gomes; Sidinei M. Thomaz; Angelo A. Agostinho (Aquatic Sciences, 2019)

Regeneration of Diabetic Foot Ulcers Based on Therapy with Red LED Light and a Natural Latex Biomembrane - S. S. R. F. Rosa; M. F. F. Rosa; M. P. Marques; G. A. Guimarães; B. C. Motta; Y. C. L. Macedo; P. Inazawa; A. Dominguez; F. S. Macedo; C. A. P. Lopes; A. F. da Rocha (Annals of Biomedical Engineering, 2019)

Computational Comparison and Visualization of Viruses in the Perspective of Clinical Information - António M. Lopes; J. A. Tenreiro Machado; Alexandra M. Galhano (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Modulation of reactive oxygen levels and gene expression in sensitive and resistant tumoral cells by C-phyocyanin - E. Fernandes e Silva; F. S. Figueira; A. P. Lettnin; M. T. S. F. Salgado; A. C. Lopes; F. Rehbein; S. J. Kalil; A. P. S. Votto (Molecular Biology Reports, 2019)

Influence of PEG coating on the biodistribution and tumor accumulation of pH-sensitive liposomes - Shirleide Santos Nunes; Renata Salgado Fernandes; Carolina Henriques Cavalcante; Isabela da Costa César; Elaine Amaral Leite; Sávia Caldeira Araújo Lopes; Alice Ferretti; Domenico Rubello; Danyelle M. Townsend; Mônica Cristina de Oliveira; Valbert Nascimento Cardoso; André Luís Branco de Barros (Drug Delivery and Translational Research, 2019)

Deep-sea seven-arm octopus hijacks jellyfish in shallow waters - Rui Rosa; Jesse T. Kelly; Vanessa M. Lopes; José R. Paula; João Gonçalves; Ricardo Calado; Mark D. Norman; João P. Barreiros (Marine Biodiversity, 2019)

GI.1b/GI.1b/GI.2 recombinant rabbit hemorrhagic disease virus 2 (Lagovirus europaeus/GI.2) in Morocco, Africa - Ana M. Lopes; Carlos Rouco; Pedro J. Esteves; Joana Abrantes (Archives of Virology, 2019)

Weather research and forecasting model simulations over the Pearl River Delta Region - D. Lopes; J. Ferreira; K. I. Hoi; A. I. Miranda; K. V. Yuen; K. M. Mok (Air Quality, Atmosphere & Health, 2019)

Identification of a Novel Nucleobase-Ascorbate Transporter Family Member in Fish and Amphibians - Diogo Oliveira; André M. Machado; Tiago Cardoso; Mónica Lopes-Marques; L. Filipe C. Castro; Raquel Ruivo (Fishes, 2019)
Nucleobase-Ascorbate Transporter (NAT) family includes ascorbic acid, nucleobases, and uric acid transporters: With broad evolutionary distribution. In vertebrates, four members have been previously recognized, the ascorbate transporters Slc23a1 and Slc3a2, the nucleobase transporter Slc23a4 and an orphan transporter Slc23a3. Using phylogenetic and synteny analysis, we identify a fifth member of the vertebrate slc23 complement (slc23a5), present in neopterygians (gars and teleosts) and amphibians, and clarify the evolutionary relationships between the novel gene and known slc23 genes. Further comparative analysis puts forward uric acid as the preferred substrate for Slc23a5. Gene expression quantification, using available transcriptomic data, suggests kidney and testis as major expression sites in Xenopus tropicalis (western clawed frog) and Danio rerio (zebrafish). Additional expression in brain was detected in D. rerio, while in the Neoteleostei Oryzias latipes (medaka) slc23a5 expression is restricted to the brain. The biological relevance of the retention of an extra transporter in fish and amphibians is discussed.

Forecasting the spatiotemporal variability of soil CO2 emissions in sugarcane areas in southeastern Brazil using artificial neural networks - Luciana P. S. Freitas; Mara L. M. Lopes; Leonardo B Carvalho; Alan R. Panosso; Newton La Scala Júnior; Ricardo L. B. Freitas; Carlos R. Minussi; Anna D. P. Lotufo (Environmental Monitoring and Assessment, 2018)

Microalgal Biorefineries for Bioenergy Production: Can We Move from Concept to Industrial Reality? - Mariany C. Deprá; Aline M. dos Santos; Ihana A. Severo; Andriéli B. Santos; Leila Q. Zepka; Eduardo Jacob-Lopes (BioEnergy Research, 2018)

Factors that control the spatial and temporal distributions of phosphorus, nitrogen, and carbon in the sediments of a tropical reservoir - Sheila Cardoso-Silva; Paulo Alves de Lima Ferreira; Rubens César Lopes Figueira; Daniel Clemente Vieira Rêgo da Silva; Viviane Moschini-Carlos; Marcelo L. M. Pompêo (Environmental Science and Pollution Research, 2018)

Cetacea are natural knockouts for IL20 - Mónica Lopes-Marques; André M. Machado; Susana Barbosa; Miguel M. Fonseca; Raquel Ruivo; L. Filipe C. Castro (Immunogenetics, 2018)

Reduced intestinal epithelial mitochondrial function enhances in vitro interleukin-8 production in response to commensal Escherichia coli - Alpana Saxena; Fernando Lopes; Derek M. McKay (Inflammation Research, 2018)

Metal loads and biomarker suite responses in a tropical carnivorous fish indicative of anthropogenic impacts in a Southeastern Brazilian lagoon - R. S. C. Coimbra; M. S. Mascarenhas; V. B. Saraiva; C. R. Santos; R. M. Lopes; R. A. Hauser-Davis; V. P. S. Oliveira; M. M. Molisani; M. G. Almeida; C. E. Rezende; C. E. V. Carvalho; M. M. Oliveira (Environmental Monitoring and Assessment, 2018)

Characterization of esterase activity from an Acetomicrobium hydrogeniformans enzyme with high structural stability in extreme conditions - Patricia S. Kumagai; Raissa F. Gutierrez; Jose L. S. Lopes; Julia M. Martins; David M. Jameson; Aline M. Castro; Luiz F. Martins; Ricardo DeMarco; Nelma R. S. Bossolan; B. A. Wallace; Ana P. U. Araujo (Extremophiles, 2018)

Tree influence on soil and pasture: contribution of proximal sensing to pasture productivity and quality estimation in montado ecosystems - João Serrano; Shakib Shahidian; J. Marques Da Silva; E. Sales-Baptista; I. Ferraz De Oliveira; J. Lopes De Castro; Alfredo Pereira; M. Cancela De Abreu; Eliana Machado; Mário de Carvalho (International Journal of Remote Sensing, 2018)

Morphological and molecular characterization of Diaporthe (anamorph Phomopsis) complex and pathogenicity of Diaporthe aspalathi isolates causing stem canker in soybean - Bruna B. Brumer; Valéria S. Lopes-Caitar; Aline S. Chicowski; Jessica D. Beloti; Fernanda M. Castanho; Danielle C. Gregório da Silva; Sandremir de Carvalho; Ivani O. N. Lopes; Rafael M. Soares; Claudine D. S. Seixas; Ricardo V. Abdelnoor; Francismar C. Marcelino-Guimarães (European Journal of Plant Pathology, 2018)

Spatial distance and climate determine modularity in a cross‐biomes plant–hummingbird interaction network in Brazil - Andréa Cardoso Araujo; Ana M. Martín González; Brody Sandel; Pietro K. Maruyama; Erich Fischer; Jeferson Vizentin‐Bugoni; Francielle Paulina de Araújo; Aline Góes Coelho; Rogério Rodrigues Faria; Glauco Kohler; Flor Maria Guedes Las‐Casas; Ariadna Valentina Lopes; et al. (Journal of Biogeography, 2018)
Aim We examined the effects of space, climate, phylogeny and species traits on module composition in a cross‐biomes plant–hummingbird network. Location Brazil, except Amazonian region. Methods We compiled 31 local binary plant–hummingbird networks, combining them into one cross‐biomes metanetwork. We conducted a modularity analysis and tested the relationship between species’ module membership with traits, geographical location, climatic conditions and range sizes, employing random forest models. We fitted reduced models containing groups of related variables (climatic, spatial, phylogenetic, traits) and combinations of groups to partition the variance explained by these sets into unique and shared components. Results The Brazilian cross‐biomes network was composed of 479 plant and 42 hummingbird species, and showed significant modularity. The resulting six modules conformed well to vegetation domains. Only plant traits, not hummingbird traits, differed between modules, notably plants’ growth form, corolla length, flower shape and colour. Some modules included plant species with very restricted distributions, whereas others encompassed more widespread ones. Widespread hummingbirds were the most connected, both within and between modules, whereas widespread plants were the most connected between modules. Among traits, only nectar concentration had a weak effect on among‐module connectivity. Main conclusions Climate and spatial filters were the main determinants of module composition for hummingbirds and plants, potentially related to resource seasonality, especially for hummingbirds. Historical dispersal‐linked contingency, or environmental variations not accounted for by the explanatory factors here evaluated, could also contribute to the spatial component. Phylogeny and morphological traits had no unique effects on the assignment of species to modules. Widespread species showed higher within‐ and/or among‐module connectivity, indicating their key role connecting biomes, and, in the case of hummingbirds, communities within biomes. Our results indicate that biogeography and climate not only determine the variation of modularity in local plant–animal networks, as previously shown, but also affect the cross‐biomes network structure.

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Hippocampal Deformations and Entorhinal Cortex Atrophy as an Anatomical Signature of Long-Term Cognitive Impairment: from the MCAO Rat Model to the Stroke Patient - C. Delattre; C. Bournonville; F. Auger; R. Lopes; C. Delmaire; H. Henon; A. M. Mendyk; S. Bombois; J. C. Devedjian; D. Leys; C. Cordonnier; R. Bordet; et al. (Translational Stroke Research, 2018)

Near infrared spectroscopy as a tool for intensive mapping of vineyards soil - M. Lopo; C. A. Teixeira dos Santos; R. N. M. J. Páscoa; A. R. Graça; João A. Lopes (Precision Agriculture, 2018)

Cyanobacterial diversity held in microbial biological resource centers as a biotechnological asset: the case study of the newly established LEGE culture collection - Vitor Ramos; João Morais; Raquel Castelo-Branco; Ângela Pinheiro; Joana Martins; Ana Regueiras; Ana L. Pereira; Viviana R. Lopes; Bárbara Frazão; Dina Gomes; Cristiana Moreira; Maria Sofia Costa; et al. (Journal of Applied Phycology, 2018)

Predicting ground-level ozone concentrations by adaptive Bayesian model averaging of statistical seasonal models - K. M. Mok; K. V. Yuen; K. I. Hoi; K. M. Chao; D. Lopes (Stochastic Environmental Research and Risk Assessment, 2018)

Effect of Alpha-Linolenic Acid Sources in Diets for Nile Tilapia on Fatty Acid Composition of Fish Fillet Using Principal Component Analysis - Maria Eugênia Petenuci; Vanessa V A Schneider; Ana Paula Lopes; Renata M Gonçalves; Vanessa J Dos Santos; Makoto Matsushita; Jesuí V Visentainer (Journal of Aquatic Food Product Technology, 2018)

Bioaccumulation Study of Produced Water Discharges from Southeastern Brazilian Offshore Petroleum Industry Using Feral Fishes - Rafael André Lourenço; Eleine Francioni; Antonio Henrique M. F. T. da Silva; Caio Augusto Magalhães; Fabiana Dias Costa Gallotta; Fabio Francisco de Oliveira; João Maximino de Souza; Leandro Franco Macena de Araújo; Liliane Pequeno de Araújo; Marcus Antonio G. de Araújo Júnior; Maria de Fátima Guadalupe Meniconi; Monica Aparecida Ferreira de Souza Bindes Gomes Lopes (Archives of Environmental Contamination and Toxicology, 2018)

Spathaspora piracicabensis f. a., sp. nov., a d-xylose-fermenting yeast species isolated from rotting wood in Brazil - Camila S. Varize; Raquel M. Cadete; Lucas D. Lopes; Renata M. Christofoleti-Furlan; Marc-André Lachance; Carlos A. Rosa; Luiz C. Basso (Antonie van Leeuwenhoek, 2018)

Microbiota associated with tubes of Escarpia sp. from cold seeps in the southwestern Atlantic Ocean constitutes a community distinct from that of surrounding marine sediment and water - Renata Medina-Silva; Rafael R. Oliveira; Fernanda J. Trindade; Luiz G. A. Borges; Taiz L. Lopes Simão; Adolpho H. Augustin; Fernanda P. Valdez; Marcelo J. Constant; Carolina L. Simundi; Eduardo Eizirik; Claudia Groposo; Dennis J. Miller; et al. (Antonie van Leeuwenhoek, 2018)

Correction to: How healthy will be the air quality in 2050? - A. Monteiro; E. Sá; A. Fernandes; C. Gama; S. Sorte; C. Borrego; M. Lopes; M. A. Russo (Air Quality, Atmosphere & Health, 2018)

How healthy will be the air quality in 2050? - A. Monteiro; E. Sá; A. Fernandes; C. Gama; S. Sorte; C. Borrego; M. Lopes; M. A. Russo (Air Quality, Atmosphere & Health, 2018)

Diversity, biogeography and conservation of freshwater mussels (Bivalvia: Unionida) in East and Southeast Asia - Alexandra Zieritz; Arthur E. Bogan; Elsa Froufe; Olga Klishko; Takaki Kondo; Uthaiwan Kovitvadhi; Satit Kovitvadhi; Jin Hee Lee; Manuel Lopes-Lima; John M. Pfeiffer; Ronaldo Sousa; Tu Van Do; et al. (Hydrobiologia, 2018)

Atmospheric emissions from pellet energy supply chain: a Portuguese case study - S. Coelho; S. Rafael; S. Silva; M. Pinho; L. Tarelho; M. Lopes (Air Quality, Atmosphere & Health, 2018)

Full genome sequences are key to disclose RHDV2 emergence in the Macaronesian islands - Ana M. Lopes; Jose Blanco-Aguiar; Aaron Martín-Alonso; Manuel Leitão; Pilar Foronda; Marco Mendes; David Gonçalves; Joana Abrantes; Pedro J. Esteves (Virus Genes, 2018)

Climate change can reduce shrimp catches in equatorial Brazil - Priscila F. M. Lopes; Maria Grazia Pennino; Fúlvio Freire (Regional Environmental Change, 2018)

Usefulness of zebrafish larvae to evaluate drug-induced functional and morphological renal tubular alterations - Rita Gorgulho; Raquel Jacinto; Susana S. Lopes; Sofia A. Pereira; Erin M. Tranfield; Gabriel G. Martins; Emilio J. Gualda; Rico J. E. Derks; Ana C. Correia; Evelyne Steenvoorden; Petra Pintado; Oleg A. Mayboroda; et al. (Archives of Toxicology, 2018)

Cerebellar Gray Matter Alterations in Huntington Disease: A Voxel-Based Morphometry Study - Paula C de Azevedo; Rachel P Guimarães; Camila C Piccinin; Luiza G Piovesana; Lidiane S Campos; Juliana R Zuiani; Eliza M. Tamashiro; Giordanna Pinheiro; Augusto C Amato-Filho; Fernando Cendes; Iscia Lopes-Cendes; Anelyssa D’Abreu (The Cerebellum, 2017)

Flood risk assessment in a coastal lagoon under present and future scenarios: Ria de Aveiro case study - Carina L. Lopes; Fátima L. Alves; João M. Dias (Natural Hazards, 2017)

Threatened fish and fishers along the Brazilian Atlantic Forest Coast - Alpina Begossi; Svetlana Salivonchyk; Gustavo Hallwass; Natalia Hanazaki; Priscila F. M. Lopes; Renato A. M. Silvano (Ambio, 2017)

The bone degenerative processes in senile fishes from Holocene Brazilian shell mounds - O Aguilera; I Rocha; M S Lopes; I Lima; R T Lopes; A S Machado; R B Guimarães; M A C Crapez; M C Tenório; A Nepomuceno (Journal of Fish Diseases, 2017)
Zooarchaeological collections from shell mounds in Rio de Janeiro (2,470–4,632 cal BP ) contain a high prevalence of swollen fish bones belonging to the Atlantic spadefish ( Chaetodipterus faber ), crevalle jack ( Caranx hippos ) and fat snook ( Centropomus parallelus ). Given the lack of knowledge of the bone degenerative process in senile fishes, this study analysed hyperostotic bone in zooarchaeological and modern specimens to obtain high‐resolution morphology and microstructure reconstruction. We used micro CT as well as X‐ray diffraction to characterize the crystallographic changes associated with fish senility. Our results showed that trabecular microstructures in hyperostotic bones were consistent with estimated values of the per cent bone volume‐to‐total volume ratio ( BV / TV ) and were greater than 60% in cortical bone. Hyperostotic bones indicated a high radiograph density, and X‐ray diffractograms showed a decrease in hydroxyapatite [Ca 10 ( PO 4 ) 6 ( OH ) 2 ] and calcite (Ca CO 3 ) neocrystallization. These crystalline and density changes revealed an advanced stage of fish senile and indicate the vulnerability of ageing fish populations.

Environmental factors driving phytoplankton taxonomic and functional diversity in Amazonian floodplain lakes - Simone J. Cardoso; João Carlos Nabout; Vinicius F. Farjalla; Paloma M. Lopes; Reinaldo L. Bozelli; Vera L. M. Huszar; Fábio Roland (Hydrobiologia, 2017)

National emission ceilings in Portugal—trends, compliance and projections - J. Ferreira; J. Leitão; A. Monteiro; M. Lopes; A. I. Miranda (Air Quality, Atmosphere & Health, 2017)

Gene networks for total number born in pigs across divergent environments - Lucas L. Verardo; Marcos S. Lopes; Pramod Mathur; Ole Madsen; Fabyano F. Silva; Martien A. M. Groenen; Egbert F. Knol; Paulo S. Lopes; Simone E. F. Guimarães (Mammalian Genome, 2017)

Biology and ecology of the world’s largest invertebrate, the colossal squid (Mesonychoteuthis hamiltoni): a short review - Rui Rosa; Vanessa M. Lopes; Miguel Guerreiro; Kathrin Bolstad; José C. Xavier (Polar Biology, 2017)

Study of macro and microelements in fish from the Cienfuegos Bay. Relationship with its content in sediments - M. Peña-Icart; E. Rodrigues Pereira-Filho; L. Lopes Fialho; J. A. Nóbrega; C. Alonso-Hernández; Y. Bolaños-Alvarez; A. Muñoz-Caravaca; M. S. Pomares-Alfonso (Environmental Monitoring and Assessment, 2017)

Molecular evidence of the presence of Dictyota dichotoma (Dictyotales: Phaeophyceae) in Argentina based on sequences from mtDNA and cpDNA and a discussion of its possible origin - Erick Alves Pereira Lopes‐Filho; Fabiano Salgueiro; Silvia Mattos Nascimento; M. Cecilia Gauna; Elisa R. Parodi; Joel Campos De Paula (New Zealand Journal of Botany, 2017)
Dictyota is a brown algae genus inhabiting tropical to warm temperate environments where it is an important food source, shelter and substrate to several species of invertebrates and other algae. The taxonomy of this genus is troublesome, with poor species delimitation and doubtful records in the literature. Dictyota dichotoma , the type species of the genus, was commonly accepted as a cosmopolitan species because of the inaccurate geographical distributional range as a consequence of misidentification in several parts of the world. Recent studies with molecular data revealed new species and a new understanding of the evolution and biogeography of the genus Dictyota . These studies confined natural populations of D. dichotoma to Europe (Atlantic and Mediterranean coasts) and Macaronesian islands (Azores, Madeira and Canary archipelagos). Also, they confirmed its presence in South Africa, but whether the species was native or introduced in South Africa could not be verified. In the present study two regions of cpDNA ( psb A, rbc L) and one region of mtDNA ( nad 1) from Argentinian samples, identified morphologically as D. dichotoma , were analysed and compared to other Dictyota species. The identity of these samples as D. dichotoma was confirmed. A haplotype network analysis using all available psb A sequences distinguished seven haplotypes divided into two geographic groups: Atlantic–Mediterranean and Canarian. In Argentina and South Africa only the most common haplotype of the Atlantic–Mediterranean group was observed. According to the paleoceanographic currents and the presence of a European haplotype, the introduced nature of D. dichotoma is indicated.

Phylogeography and phylogeny of the genus Acanthonyx (Decapoda, Epialtidae) in the north‐east Atlantic and Mediterranean - Ana I. Tavares; M. Pilar Cabezas; Raquel Xavier; Madalena Branco; Fernando P. Lima; Rui Seabra; Pedro A. Ribeiro; Evandro P. Lopes; António M. Santos (Zoologica Scripta, 2017)
The genus Acanthonyx Latreille, 1828 (Majoidea, Epialtidae) contains 17 or 18 known species, depending on competing taxonomic views, that are widely distributed across the world. Morphologically, most species look superficially alike, and therefore, similar taxonomic concepts have been described under different names. Consequently, there is today a considerable list of synonyms, which further complicates the taxonomy of the genus Acanthonyx . In this study, we conducted a phylogeographical and phylogenetic analysis of populations of the genus Acanthonyx in the NE Atlantic, Mediterranean and Macaronesia using the mitochondrial cytochrome oxidase subunit I ( COI ) and the nuclear 28S rRNA loci. Our phylogenetic and phylogeographical results revealed that Acanthonyx lunulatus sensu lato is a complex of three distinct lineages: one corresponding to the previously described Acanthonyx brevifrons , another to A. lunulatus sensu stricto and a third to a yet undescribed group. Whereas our results confirms that A. brevifrons deserves the status of a species, as it can be easily distinguishable from A. lunulatus by a few morphological traits, we could not find any such traits suitable for the discrimination between A. lunulatus sensu stricto and the third lineage. Furthermore, the degree of COI divergence between this lineage and A. lunulatus is below average levels for Decapoda species. Yet, no shared haplotypes have been detected between them. The differences found in the nuclear gene (indels), together with the sympatric occurrence of the two forms, prompt for a more detailed analysis of this group. Overall, the results show that significant genetic differentiation between specimens with similar morphology occurs in the Epialtidae, thus reinforcing the importance of combining morphological and genetic tools to fully resolve the taxonomy of these decapods.

Biology of the relict fungus-farming ant Apterostigma megacephala Lattke, including descriptions of the male, gyne, and larva - J. Sosa-Calvo; A. Ješovnik; C. T. Lopes; A. Rodrigues; C. Rabeling; M. Bacci; H. L. Vasconcelos; T. R. Schultz (Insectes Sociaux, 2017)

Ultramorphological changes in gill rakers of Astyanax altiparanae (Characidae) kept in contaminated environments - F. P. Lopes; B. F. Pereira; R. M. S. Alves; J. R. T. Valim; F. A. T. Figueiredo; D. L. Pitol; F. H. Caetano (Fish Physiology and Biochemistry, 2017)

Global patterns of interaction specialization in bird–flower networks - Thais B. Zanata; Bo Dalsgaard; Fernando C. Passos; Peter A. Cotton; James J. Roper; Pietro K. Maruyama; Erich Fischer; Matthias Schleuning; Ana M. Martín González; Jeferson Vizentin‐Bugoni; Donald C. Franklin; Stefan Abrahamczyk; et al. (Journal of Biogeography, 2017)
Aim Among the world's three major nectar‐feeding bird taxa, hummingbirds are the most phenotypically specialized for nectarivory, followed by sunbirds, while the honeyeaters are the least phenotypically specialized taxa. We tested whether this phenotypic specialization gradient is also found in the interaction patterns with their floral resources. Location Americas, Africa, Asia and Oceania/Australia. Methods We compiled interaction networks between birds and floral resources for 79 hummingbird, nine sunbird and 33 honeyeater communities. Interaction specialization was quantified through connectance ( C ), complementary specialization ( H 2 ′), binary ( Q B ) and weighted modularity ( Q ), with both observed and null‐model corrected values. We compared interaction specialization among the three types of bird–flower communities, both independently and while controlling for potential confounding variables, such as plant species richness, asymmetry, latitude, insularity, topography, sampling methods and intensity. Results Hummingbird–flower networks were more specialized than honeyeater–flower networks. Specifically, hummingbird–flower networks had a lower proportion of realized interactions (lower C ), decreased niche overlap (greater H 2 ′) and greater modularity (greater Q B ). However, we found no significant differences between hummingbird– and sunbird–flower networks, nor between sunbird– and honeyeater–flower networks. Main conclusions As expected, hummingbirds and their floral resources have greater interaction specialization than honeyeaters, possibly because of greater phenotypic specialization and greater floral resource richness in the New World. Interaction specialization in sunbird–flower communities was similar to both hummingbird–flower and honeyeater–flower communities. This may either be due to the relatively small number of sunbird–flower networks available, or because sunbird–flower communities share features of both hummingbird–flower communities (specialized floral shapes) and honeyeater–flower communities (fewer floral resources). These results suggest a link between interaction specialization and both phenotypic specialization and floral resource richness within bird–flower communities at a global scale.

Interaction of nucleus reuniens and entorhinal cortex projections in hippocampal field CA1 of the rat - M. J. Dolleman-van der Weel; F. H. Lopes da Silva; M. P. Witter (Brain Structure and Function, 2017)

An update on the rabbit hemorrhagic disease virus (RHDV) strains circulating in Portugal in the 1990s: earliest detection of G3-G5 and G6 - Ana M. Lopes; Maria J. Magalhães; Paulo C. Alves; Pedro J. Esteves; Joana Abrantes (Archives of Virology, 2017)

Human topoisomerase inhibition and DNA/BSA binding of Ru(II)–SCAR complexes as potential anticancer candidates for oral application - Rone A. De Grandis; Mariana S. de Camargo; Monize M. da Silva; Érica O. Lopes; Elias C. Padilha; Flávia A. Resende; Rosângela G. Peccinini; Fernando R. Pavan; Alessandro Desideri; Alzir A. Batista; Eliana A. Varanda (BioMetals, 2017)

RA Differentiation Enhances Dopaminergic Features, Changes Redox Parameters, and Increases Dopamine Transporter Dependency in 6-Hydroxydopamine-Induced Neurotoxicity in SH-SY5Y Cells - Fernanda M. Lopes; Leonardo Lisbôa da Motta; Marco A. De Bastiani; Bianca Pfaffenseller; Bianca W. Aguiar; Luiz F. de Souza; Geancarlo Zanatta; Daiani M. Vargas; Patrícia Schönhofen; Giovana F. Londero; Liana M. de Medeiros; Valder N. Freire; et al. (Neurotoxicity Research, 2017)

Mutagenicity assessment of aerosols in emissions from domestic combustion processes - Nuno Canha; Isabel Lopes; Estela Domingos Vicente; Ana M. Vicente; Benjamin A. Musa Bandowe; Susana Marta Almeida; Célia A. Alves (Environmental Science and Pollution Research, 2017)

Characterization of bacterial communities from Masseiras, a unique Portuguese greenhouse agricultural system - Cristina Becerra-Castro; Ana Rita Lopes; Sara Teixeira; M. Elisabete F. Silva; Elisabete Pimenta; Célia M. Manaia; Olga C. Nunes (Antonie van Leeuwenhoek, 2017)

An integrated approach for wind fields assessment in coastal areas, based on bioindicators, CFD modeling, and observations - Bruno M. Meneses; António Lopes (Theoretical and Applied Climatology, 2017)

In vitro metabolism studies of natural products are crucial in the early development of medicines - Fernanda L. Moreira; Lucas M. M. Marques; Norberto P. Lopes; Anderson R. M. de Oliveira (Phytochemistry Reviews, 2017)

Using dendritic cells to evaluate how Burkholderia cenocepacia clonal isolates from a chronically infected cystic fibrosis patient subvert immune functions - M. Guadalupe Cabral; Marília Pereira; Zélia Silva; Inês Iria; Carla Coutinho; Andreia Lopes; Isabel Sá-Correia; Paula A. Videira (Medical Microbiology and Immunology, 2017)

Tracing of aerosol sources in an urban environment using chemical, Sr isotope, and mineralogical characterization - Regina M. B. O. Duarte; João T. V. Matos; Andreia S. Paula; Sónia P. Lopes; Sara Ribeiro; José Francisco Santos; Carla Patinha; Eduardo Ferreira da Silva; Rosário Soares; Armando C. Duarte (Environmental Science and Pollution Research, 2017)

Preparation, characterization and environmental applications of Sr1 − x (La,Bi) x TiO3 perovskites immobilized on Ni-foam: photodegradation of the Acid Orange 7 - M. J. Nunes; A. Lopes; M. J. Pacheco; L. Ciríaco (Environmental Science and Pollution Research, 2017)

Structure and diversity of fishes in a freshwater and coastal subtropical lagoon - N. C. Ferreira; R. M. Guereschi; C. Machado; C. A. Lopes; A. P. O. Nuñer (Journal of Fish Biology, 2017)
This study examined the fish communities of Peri Lagoon in southern Brazil to aid in the development of an effective management plan because the area is under threat from human activities. Sampling of fish fauna, ichthyoplankton and limnological data were compared between sites, differing by habitat type and characteristics such as depth, substratum composition and vegetation type. Results were significantly related to site, with the highest diversity and abundance recorded at shallow vegetated sites. A total of 14 fish species were recorded throughout the lagoon, with the most abundant being Hyphessobrycon luetkenii . Of the 14 species, half were sampled at their larval stage, suggesting a healthy and protected system. Significantly more larvae and eggs were collected during colder months (autumn to winter) and at sites closer to stream flow, possibly owing to increased food sources and habitat protection. This study highlights the importance of Peri Lagoon as a nursery ground for a wide range of fish species, providing essential information for incorporation into the future protection of fish stocks throughout Brazil.

Increased Plasma Levels of Select Deoxy-ceramide and Ceramide Species are Associated with Increased Odds of Diabetic Neuropathy in Type 1 Diabetes: A Pilot Study - Samar M. Hammad; Nathaniel L. Baker; Jad M. El Abiad; Stefanka D. Spassieva; Jason S. Pierce; Barbara Rembiesa; Jacek Bielawski; Maria F. Lopes-Virella; Richard L. Klein (NeuroMolecular Medicine, 2017)

Bacteria and fungi inactivation by photocatalysis under UVA irradiation: liquid and gas phase - Caio Rodrigues-Silva; Sandra M. Miranda; Filipe V. S. Lopes; Mário Silva; Márcia Dezotti; Adrián M. T. Silva; Joaquim L. Faria; Rui A. R. Boaventura; Vítor J. P. Vilar; Eugénia Pinto (Environmental Science and Pollution Research, 2017)

Fatigue and Its Associated Factors in Spinocerebellar Ataxia Type 3/Machado-Joseph Disease - Alberto R. M. Martinez; Marcelo B. Nunes; Ingrid Faber; Anelyssa D’Abreu; Íscia Lopes-Cendes; Marcondes C. França (The Cerebellum, 2017)

Nonneurological Involvement in Late-Onset Friedreich Ataxia (LOFA): Exploring the Phenotypes - Alberto R. M. Martinez; Adriana Moro; Agessandro Abrahao; Ingrid Faber; Conrado R. Borges; Thiago J. R. Rezende; Carlos R. Martins; Mariana Moscovich; Renato P. Munhoz; Sandra Leistner Segal; Walter O. Arruda; Maria Luiza Saraiva-Pereira; et al. (The Cerebellum, 2017)

Elucidating constraints for differentiation of major human Klebsiella pneumoniae clones using MALDI-TOF MS - C. Rodrigues; Â. Novais; C. Sousa; H. Ramos; T. M. Coque; R. Cantón; J. A. Lopes; L. Peixe (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

d-Xylose fermentation, xylitol production and xylanase activities by seven new species of Sugiyamaella - Letícia M. F. Sena; Camila G. Morais; Mariana R. Lopes; Renata O. Santos; Ana P. T. Uetanabaro; Paula B. Morais; Marcos J. S. Vital; Marcos A. de Morais; Marc-André Lachance; Carlos A. Rosa (Antonie van Leeuwenhoek, 2017)

Erratum to: Habitat selection disruption and lateralization impairment of cryptic flatfish in a warmer, hypercapnic, and contaminated ocean - Eduardo Sampaio; Ana Luísa Maulvault; Vanessa M. Lopes; José R. Paula; Vera Barbosa; Ricardo Alves; Pedro Pousão-Ferreira; Tiago Repolho; António Marques; Rui Rosa (Marine Biology, 2016)

Behavioural lateralization and shoaling cohesion of fish larvae altered under ocean acidification - A. F. Lopes; P. Morais; M. Pimentel; R. Rosa; P. L. Munday; E. J. Gonçalves; A. M. Faria (Marine Biology, 2016)

Dietary indispensable amino acids profile affects protein utilization and growth of Senegalese sole larvae - Paula Canada; Sofia Engrola; Nadège Richard; Ana Filipa Lopes; Wilson Pinto; Luísa M. P. Valente; Luís E. C. Conceição (Fish Physiology and Biochemistry, 2016)

Impact of air exposure on the photobiology and biochemical profile of an aggressive intertidal competitor, the zoanthid Palythoa caribaeorum - Inês C. Rosa; Rui J. M. Rocha; Ana Lopes; Igor C. S. Cruz; Ricardo Calado; Narcisa Bandarra; Ruy K. Kikuchi; Amadeu M. V. M. Soares; João Serôdio; Rui Rosa (Marine Biology, 2016)

Guiana dolphins form social modules in a large population with high ranging overlap and small demographic changes - L. Beirão-Campos; M. Cantor; L. Flach; P. C. Simões-Lopes (Behavioral Ecology and Sociobiology, 2016)

Investigating ozone episodes in Portugal: a wavelet-based approach - A. Monteiro; S. Gouveia; M. G. Scotto; J. Lopes; C. Gama; M. Feliciano; A. I. Miranda (Air Quality, Atmosphere & Health, 2016)

The Importance of Reedbeds and Riparian Areas for Cetti’s Warbler Cettia cetti throughout its Annual Cycle - Pedro M. Araújo; Pedro B. Lopes; Luís P. da Silva; Jaime A. Ramos (Wetlands, 2016)

Habitat selection disruption and lateralization impairment of cryptic flatfish in a warm, acid, and contaminated ocean - Eduardo Sampaio; Ana Luísa Maulvault; Vanessa M. Lopes; José R. Paula; Vera Barbosa; Ricardo Alves; Pedro Pousão-Ferreira; Tiago Repolho; António Marques; Rui Rosa (Marine Biology, 2016)

Prevalence of hypertension and its associated factors in contaminated areas of the Santos-São Vicente Estuarine region and Bertioga, Brazil: 2006-2009 - T. S. Ribeiro; D. P. Carvalho; M. T. Guimarães; N. N. Campina; M. R. Lobarinhas; A. L. J. Lopes; M. G. Cunha; I. B. Souza; V. L. F. Oliveira; L. C. Martins; A. Gomes; L. A. A. Pereira; et al. (Environmental Science and Pollution Research, 2016)

Indomethacin treatment reduces microglia activation and increases numbers of neuroblasts in the subventricular zone and ischaemic striatum after focal ischaemia - Rosana S Lopes; Marcelo M Cardoso; Arthur O Sampaio; Mario Santos Barbosa; Celice C Souza; Michelle C da Silva; Elane Magno N Ferreira; Marco Aurelio M Freire; Rafael Rodrigues Lima; Walace Gomes-Leal (Journal of Biosciences, 2016)

Temporal changes in pelagic copepod assemblages off Ubatuba, Brazil - Mauro Melo Júnior; Catarina R. Marcolin; Leonardo K. Miyashita; Rubens M. Lopes (Marine Ecology, 2016)
The inner shelf waters off Southeastern Brazil are periodically enriched by bottom intrusions of the cold and nutrient‐rich South Atlantic Central Water ( SACW ), which is transported offshore by the Brazil Current. This study examined the temporal contrasts in abundance and structure of pelagic copepod assemblages in a neritic station off Ubatuba, in relation to hydrography and phytoplankton biomass, to investigate the effects of SACW bottom intrusions on copepod population dynamics during three consecutive years. The water‐column characteristics shifted from a well‐mixed, more turbid and phytoplankton‐poor scenario during subsidence conditions to a stratified, less turbid and high Chl‐ a concentration scenario during SACW bottom intrusions, leading to increased copepod diversity, abundance, and biomass. The rise in copepod diversity during SACW intrusions was related to the contribution of oceanic species in addition to coastal water species. The copepod community was numerically dominated by small‐sized species, such as Oncaea waldemari , Oithona plumifera , and clausocalanid and paracalanid copepodids, regardless of seasonality and SACW intrusions. Some large calanoid species contributed considerably to the total copepod biomass during intrusions. In addition to confirming that SACW seasonal intrusions play a key role in pelagic processes off Southeast Brazil, this study showed that the multiannual variability of SACW seasonal intrusions is important in regulating the structure and dynamics of copepod communities in this subtropical area.

Enhancement of the antibiotic activity of aminoglycosides by extracts from Anadenanthera colubrine (Vell.) Brenan var. cebil against multi-drug resistant bacteria - Humberto M. Barreto; Kivia M.R.N. Coelho; Josie H.L. Ferreira; Bernadete H.C. dos Santos; Aislan P.L. de Abreu; Henrique D.M. Coutinho; Romezio A.C. da Silva; Taciana O. de Sousa; Antonia M. das G.L. Citó; José A.D. Lopes (Natural Product Research, 2016)

Comparative study on metal biosorption by two macroalgae in saline waters: single and ternary systems - Paula Figueira; Bruno Henriques; Ana Teixeira; Cláudia B. Lopes; Ana T. Reis; Rui J. R. Monteiro; A. C. Duarte; M. A. Pardal; E. Pereira (Environmental Science and Pollution Research, 2016)

Mutagenicity assessment of aerosols in emissions from domestic combustion processes - Nuno Canha; Isabel Lopes; Estela Domingos Vicente; Ana M. Vicente; Benjamin A. Musa Bandowe; Susana Marta Almeida; Célia A. Alves (Environmental Science and Pollution Research, 2016)

Axonal elongation and dendritic branching is enhanced by adenosine A2A receptors activation in cerebral cortical neurons - Filipa F. Ribeiro; Raquel Neves-Tomé; Natália Assaife-Lopes; Telma E. Santos; Rui F. M. Silva; Dora Brites; Joaquim A. Ribeiro; Mónica M. Sousa; Ana M. Sebastião (Brain Structure and Function, 2016)

Meta-analysis review of fish trophic level at marine protected areas based on stable isotopes data - J. J. De LOPE ARIAS; G. MATEU-VICENS; M. DEUDERO COMPANY (Mediterranean Marine Science, 2016)
Stable isotopes (δ15N) are used to determine trophic level in marine food webs. We assessed if Marine Protected Areas (MPAs) affect trophic level of fishes based on stable isotopes on the Western Mediterranean. A total of 22 studies including 600 observations were found and the final dataset consisted of 11 fish species and 146 observations comparing trophic level inside and outside MPAs. The database was analysed by meta-analysis and the covariate selected was the level of protection (inside vs. outside MPAs). The results indicate significant difference between trophic levels inside and outside MPAs. However, results differ from expectations since the trophic level inside was lower than outside MPAs. Three habitats were analysed (coastal lagoons, demersal and littoral) and significant differences were found among them. Trophic level was higher in demersal habitats than in coastal lagoons and littoral areas. No significant differences were found in species classified by trophic functional groups. We consider several hypotheses explaining the obtained results linked to protection level of the MPAs, time since protection and MPAs size. We debate the suitability of using the stable isotope (δ15N) as direct indicator of trophic level in evaluating MPAs effects on food webs.

Short-term impact of soybean management on ammonia oxidizers in a Brazilian savanna under restoration as revealed by coupling different techniques - E. C. P. Catão; F. A. C. Lopes; M. R. Rubini; G. B. Nardoto; J. I. Prosser; R. H. Krüger (Biology and Fertility of Soils, 2016)

Deficit in digestive capabilities of bamboo shark early stages under climate change - Rui Rosa; Marta Pimentel; Juan G. Galan; Miguel Baptista; Vanessa M. Lopes; Ana Couto; Miguel Guerreiro; Eduardo Sampaio; Joana Castro; Catarina Santos; Ricardo Calado; Tiago Repolho (Marine Biology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Oxaprozin-Loaded Lipid Nanoparticles towards Overcoming NSAIDs Side-Effects - José Lopes-de-Araújo; Ana Rute Neves; Virgínia M. Gouveia; Catarina C. Moura; Cláudia Nunes; Salette Reis (Pharmaceutical Research, 2016)

Exercise Improves Cognitive Impairment and Dopamine Metabolism in MPTP-Treated Mice - Aderbal S. Aguiar; Samantha C. Lopes; Fabrine S. M. Tristão; Daniel Rial; Gisele de Oliveira; Cláudio da Cunha; Rita Raisman-Vozari; Rui D. Prediger (Neurotoxicity Research, 2016)

Triaxial test of drained sand reinforced with plastic layers - S. Nouri; A. Nechnech; B. Lamri; M. Lurdes Lopes (Arabian Journal of Geosciences, 2016)

A high efficient protocol for soybean root transformation by Agrobacterium rhizogenes and most stable reference genes for RT-qPCR analysis - K. M. Kuma; V. S. Lopes-Caitar; C. C. T. Romero; S. M. H. Silva; M. K. Kuwahara; M. C. C. G. Carvalho; R. V. Abdelnoor; W. P. Dias; F. C. Marcelino-Guimarães (Plant Cell Reports, 2015)

Estimating zooplankton vertical distribution from combined LOPC and ZooScan observations on the Brazilian Coast - Catarina R. Marcolin; Rubens M. Lopes; George A. Jackson (Marine Biology, 2015)

Vitrification of Rattus norvegicus immature cumulus-oocyte complexes using hyaluronic acid - L. M. G. Paim; L. L. Gal; R. F. F. Lopes; A. T. D. Oliveira (In Vitro Cellular & Developmental Biology - Animal, 2015)

Community structure of resting egg banks and concordance patterns between dormant and active zooplankters in tropical lakes - Jayme M. Santangelo; Paloma M. Lopes; Monalisa O. Nascimento; Ana Paula C. Fernandes; Sandra Bartole; Marcos P. Figueiredo-Barros; João J. F. Leal; Francisco A. Esteves; Vinicius F. Farjalla; Claudia C. Bonecker; Reinaldo L. Bozelli (Hydrobiologia, 2015)

Oxidative stress markers in fish (Astyanax sp. and Danio rerio) exposed to urban and agricultural effluents in the Brazilian Pampa biome - D. G. Costa-Silva; M. E. M Nunes; G. L. Wallau; I. K. Martins; A. P. P Zemolin; L. C. Cruz; N. R. Rodrigues; A. R. Lopes; T. Posser; J. L. Franco (Environmental Science and Pollution Research, 2015)

Prevalence of liver diseases as referred by people living in the Santos and São Vicente Estuary - Daniele Fernandes Pena Carvalho; M. T. Guimarães; T. S. Ribeiro; N. N. Campina; M. R. Lobarinhas; A. L. J Lopes; M. G. Cunha; I. B. Souza; V. L. F. Oliveira; L. Braga E Braga; L. C. Martins; A. Gomes; et al. (Environmental Science and Pollution Research, 2015)

NTPDase and 5′-nucleotidase activities in synaptosomes of rabbits experimentally infected with BoHV-5 - Cássia B. da Silva; Francine C. Paim; Patricia Wolkmer; Fátima H. Abdalla; Fabiano B. Carvalho; Heloísa H. Palma; Camila B.E. Mello; Eduardo F. Flores; Cinthia M. Andrade; Sonia T.A. Lopes (Journal of NeuroVirology, 2015)

Early Warning Systems: Feasibility and End-Users' Point of View - C. S. Oliveira; F. Mota de Sá; M. Lopes; M. A. Ferreira; I. Pais (Pure and Applied Geophysics, 2015)

Assessing the ecotoxicity of metal nano-oxides with potential for wastewater treatment - V. Nogueira; I. Lopes; T. A. P. Rocha-Santos; M. G. Rasteiro; N. Abrantes; F. Gonçalves; A. M. V. M. Soares; A. C. Duarte; R. Pereira (Environmental Science and Pollution Research, 2015)

Current Approaches and Future Trends to Promote Tendon Repair - D. S. Morais; J. Torres; R. M. Guedes; M. A. Lopes (Annals of Biomedical Engineering, 2015)

Cannabidiol Exposure During Neuronal Differentiation Sensitizes Cells Against Redox-Active Neurotoxins - Patrícia Schönhofen; Liana M. de Medeiros; Ivi Juliana Bristot; Fernanda M. Lopes; Marco A. De Bastiani; Flávio Kapczinski; José Alexandre S. Crippa; Mauro Antônio A. Castro; Richard B. Parsons; Fábio Klamt (Molecular Neurobiology, 2015)

Effects of palatable cafeteria diet on cognitive and noncognitive behaviors and brain neurotrophins’ levels in mice - Daniela D. Leffa; Samira S. Valvassori; Roger B. Varela; Jésica Lopes-Borges; Francine Daumann; Luiza M. Longaretti; Ana Luiza F. Dajori; João Quevedo; Vanessa M. Andrade (Metabolic Brain Disease, 2015)

First results on the genetic diversity of the invasive signal crayfish Pacifastacus leniusculus (Dana, 1852) in Europe using novel microsatellite loci - E. Froufe; S. Varandas; A. Teixeira; R. Sousa; L. Filipová; A. Petrusek; L. Edsman; M. Lopes-Lima (Journal of Applied Genetics, 2015)

Relationships among bulk soil physicochemical, biochemical, and microbiological parameters in an organic alfalfa-rice rotation system - Ana R. Lopes; Diana Bello; Ángeles Prieto-Fernández; Carmen Trasar-Cepeda; Célia M. Manaia; Olga C. Nunes (Environmental Science and Pollution Research, 2015)

Dense macrophytes influence the horizontal distribution of fish in floodplain lakes - Taise M. Lopes; Eduardo R. Cunha; João Carlos B. Silva; Rômulo D. L. Behrend; Luiz C. Gomes (Environmental Biology of Fishes, 2015)

On the Determination of Effective Aerodynamic Roughness of Surfaces with Vegetation Patches - A. Silva Lopes; J. M. L. M. Palma; U. Piomelli (Boundary-Layer Meteorology, 2015)

Assessment of flood hazard during extreme sea levels in a tidally dominated lagoon - Carina L. Lopes; João M. Dias (Natural Hazards, 2015)

Unraveling the interactive effects of climate change and oil contamination on laboratory‐simulated estuarine benthic communities - Francisco J. R. C. Coelho; Daniel F. R. Cleary; Rui J. M. Rocha; Ricardo Calado; José M. Castanheira; Sílvia M. Rocha; Artur M. S. Silva; Mário M. Q. Simões; Vanessa Oliveira; Ana I. Lillebø; Adelaide Almeida; Ângela Cunha; et al. (Global Change Biology, 2015)
There is growing concern that modifications to the global environment such as ocean acidification and increased ultraviolet radiation may interact with anthropogenic pollutants to adversely affect the future marine environment. Despite this, little is known about the nature of the potential risks posed by such interactions. Here, we performed a multifactorial microcosm experiment to assess the impact of ocean acidification, ultraviolet B (UV‐B) radiation and oil hydrocarbon contamination on sediment chemistry, the microbial community (composition and function) and biochemical marker response of selected indicator species. We found that increased ocean acidification and oil contamination in the absence of UV‐B will significantly alter bacterial composition by, among other things, greatly reducing the relative abundance of Desulfobacterales , known to be important oil hydrocarbon degraders. Along with changes in bacterial composition, we identified concomitant shifts in the composition of oil hydrocarbons in the sediment and an increase in oxidative stress effects on our indicator species. Interestingly, our study identifies UV‐B as a critical component in the interaction between these factors, as its presence alleviates harmful effects caused by the combination of reduced pH and oil pollution. The model system used here shows that the interactive effect of reduced pH and oil contamination can adversely affect the structure and functioning of sediment benthic communities, with the potential to exacerbate the toxicity of oil hydrocarbons in marine ecosystems.

Suitability of enzymatic markers to assess the environmental condition of natural populations of Gambusia affinis and Daphnia magna—a case study - Inês Domingues; Cátia S. A. Santos; Nuno G. C. Ferreira; Luísa Machado; Rhaul Oliveira; Abel Ferreira; Isabel Lopes; Susana Loureiro; Amadeu M. V. M. Soares (Environmental Monitoring and Assessment, 2015)

Genetic characterization of the wheat association mapping initiative (WAMI) panel for dissection of complex traits in spring wheat - M. S. Lopes; S. Dreisigacker; R. J. Peña; S. Sukumaran; M. P. Reynolds (Theoretical and Applied Genetics, 2015)

Isolation and characterization of 23 microsatellite loci in the stingless bee Melipona subnitida using next-generation sequencing - Isis G. B. Souza; Ian Paterson; Meghan C. McBride; Bruno A. Souza; Fabia M. Pereira; Maria T. R. Lopes; Paul Bentzen; Fabio M. Diniz (Conservation Genetics Resources, 2015)

Complete genome sequence of two rabbit hemorrhagic disease virus variant b isolates detected on the Iberian Peninsula - K. P. Dalton; J. Abrantes; A. M. Lopes; I. Nicieza; Á. L. Álvarez; P. J. Esteves; F. Parra (Archives of Virology, 2015)

Heterogeneity in symbiotic effects facilitates Wolbachia establishment in insect populations - Caetano Souto-Maior; Joao S. Lopes; Erida Gjini; Claudio J. Struchiner; Luis Teixeira; M. Gabriela M. Gomes (Theoretical Ecology, 2015)

Bayesian GWAS and network analysis revealed new candidate genes for number of teats in pigs - L. L. Verardo; F. F. Silva; L. Varona; M. D. V. Resende; J. W. M. Bastiaansen; P. S. Lopes; S. E. F. Guimarães (Journal of Applied Genetics, 2015)

Superoxide Dismutase Enzymosomes: Carrier Capacity Optimization, in Vivo Behaviour and Therapeutic Activity - M. Luísa Corvo; H. Susana Marinho; Paulo Marcelino; Rui M. Lopes; Carlos A. Vale; Claúdia R. Marques; Luísa C.D. Martins; Peter Laverman; Gert Storm; M. Bárbara A.F. Martins (Pharmaceutical Research, 2015)

Evaluation of PAH contamination in soil treated with solid by-products from shale pyrolysis - Jaqueline Nicolini; Muhammad Y. Khan; M. Matsui; Lílian C. Côcco; Carlos I. Yamamoto; Wilson A. Lopes; Jailson B. de Andrade; Clenio N. Pillon; Gregorio G. Carbajal Arizaga; Antonio S. Mangrich (Environmental Monitoring and Assessment, 2015)

Fishers’ knowledge as a source of information about the estuarine dolphin (Sotalia guianensis, van Bénéden, 1864) - Maíra Fontes Manzan; Priscila F. M. Lopes (Environmental Monitoring and Assessment, 2015)

Solar photocatalytic gas-phase degradation of n-decane—a comparative study using cellulose acetate monoliths coated with P25 or sol-gel TiO2 films - Sandra M. Miranda; Filipe V. S. Lopes; Caio Rodrigues-Silva; Susana D. S. Martins; Adrián M. T. Silva; Joaquim L. Faria; Rui A. R. Boaventura; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2015)

Synthesis and characterization of N-modified titania nanotubes for photocatalytic applications - Ricardo A. R. Monteiro; Filipe V. S. Lopes; Rui A. R. Boaventura; Adrián M. T. Silva; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2015)

Evaluation and Selection of Indicators for Land Degradation and Desertification Monitoring: Types of Degradation, Causes, and Implications for Management - Or. Kairis; C. Kosmas; Ch. Karavitis; C. Ritsema; L. Salvati; S. Acikalin; M. Alcalá; P. Alfama; J. Atlhopheng; J. Barrera; A. Belgacem; A. Solé-Benet; et al. (Environmental Management, 2014)

Evaluation and Selection of Indicators for Land Degradation and Desertification Monitoring: Methodological Approach - C. Kosmas; Or. Kairis; Ch. Karavitis; C. Ritsema; L. Salvati; S. Acikalin; M. Alcalá; P. Alfama; J. Atlhopheng; J. Barrera; A. Belgacem; A. Solé-Benet; et al. (Environmental Management, 2014)

Stiffness parameters of municipal solid waste - Cristina C. Gomes; M. Lurdes Lopes; Paulo J. V. Oliveira (Bulletin of Engineering Geology and the Environment, 2014)

Do wood-based panels made with agro-industrial residues provide environmentally benign alternatives? An LCA case study of sugarcane bagasse addition to particle board manufacturing - Diogo Aparecido Lopes Silva; Francisco Antonio Rocco Lahr; Ana Laura Raymundo Pavan; Yovana M. B. Saavedra; Natalia Crespo Mendes; Sabrina Rodrigues Sousa; Roberta Sanches; Aldo Roberto Ometto (The International Journal of Life Cycle Assessment, 2014)

Continuous flow photo-Fenton treatment of ciprofloxacin in aqueous solutions using homogeneous and magnetically recoverable catalysts - Maria J. Lima; M. Enis Leblebici; Madalena M. Dias; José Carlos B. Lopes; Cláudia G. Silva; Adrián M. T. Silva; Joaquim L. Faria (Environmental Science and Pollution Research, 2014)

Characterization of “Candidatus Liberibacter Asiaticus” Populations by Double-Locus Analyses - X. Deng; S. Lopes; X. Wang; X. Sun; D. Jones; M. Irey; E. Civerolo; J. Chen (Current Microbiology, 2014)

Assessment of imposex and butyltin concentrations in Gemophos viverratus (Kiener, 1834), from São Vicente, Republic of Cabo Verde (Africa) - R. M. A. Lopes-dos-Santos; S. Galante-Oliveira; E. Lopes; C. Almeida; C. Barroso (Environmental Science and Pollution Research, 2014)

Helicobacter pylori Identification: A Diagnostic/Confirmatory Method for Evaluation - B. Mesquita; M. J. Gonçalves; P. Pacheco; J. Lopes; F. Salazar; M. Relvas; C. Coelho; J. J. Pacheco; C. Velazco (Current Microbiology, 2014)

A family history questionnaire improves detection of women at risk for hereditary gynecologic cancer: a pilot study - Margot M. Koeneman; Arnold-Jan Kruse; Simone J. S. Sep; Cynthia S. Gubbels; Brigitte F. M. Slangen; Toon van Gorp; Alberto Lopes; Encarna Gomez-Garcia; Roy F. P. M. Kruitwagen (Familial Cancer, 2014)

Erratum to: Ureaplasma diversum as a cause of pustular vulvovaginitis in bovine females in Vale Guapore, Mato Grosso State, Brazil - João Guilherme L. N. Gaeti; Marconni V. C. Lana; Gustavo S. Silva; Leticya L. Lopes; Camila G. de Campos; Fernanda H. Maruyama; Edson M. Colodel; Eduardo F. Costa; Luis G. Corbellini; Luciano Nakazato; Caroline A. Pescador (Tropical Animal Health and Production, 2014)

MALDI-TOF mass spectrometry as a tool for the discrimination of high-risk Escherichia coli clones from phylogenetic groups B2 (ST131) and D (ST69, ST405, ST393) - Â. Novais; C. Sousa; J. de Dios Caballero; A. Fernandez-Olmos; J. Lopes; H. Ramos; T. M. Coque; R. Cantón; L. Peixe (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

A Multidisciplinary Approach to Evaluate the Efficiency of a Clean-Up Technology to Remove Mercury from Water - Cláudia B. Lopes; Isabel Lopes; Luciana S. Rocha; Armando C. Duarte; Amadeu M. V. M. Soares; João Rocha; Eduarda Pereira (Bulletin of Environmental Contamination and Toxicology, 2014)

Efficiency of a cleanup technology to remove mercury from natural waters by means of rice husk biowaste: ecotoxicological and chemical approach - Luciana S. Rocha; I. Lopes; Cláudia B. Lopes; Bruno Henriques; Amadeu M. V. M. Soares; Armando C. Duarte; Eduarda Pereira (Environmental Science and Pollution Research, 2014)

Degradation of tetracycline at a boron-doped diamond anode: influence of initial pH, applied current intensity and electrolyte - C. I. Brinzila; N. Monteiro; M. J. Pacheco; L. Ciríaco; I. Siminiceanu; A. Lopes (Environmental Science and Pollution Research, 2014)

Mercury in Indigenous, Introduced and Farmed Fish from the Semiarid Region of the Jaguaribe River Basin, NE Brazil - L. D. Lacerda; B. G. B. C. Costa; D. N. Lopes; K. Oliveira; M. F. Bezerra; W. R. Bastos (Bulletin of Environmental Contamination and Toxicology, 2014)

Identification of potential leafhoppers vectors of phytoplasmas (16SrIII group) associated with broccoli stunt disease in Brazil - B. Eckstein; J. C. Barbosa; P. F. Kreyci; K. M. R. Zanol; L. B. N. Coelho; A. C. S. M. L. Gonçalves; K. R. Brunelli; J. R. S. Lopes; I. P. Bedendo (Australasian Plant Pathology, 2014)

Regulation of TrkB receptor translocation to lipid rafts by adenosine A2A receptors and its functional implications for BDNF-induced regulation of synaptic plasticity - Natália Assaife-Lopes; Vasco C. Sousa; Daniela B. Pereira; Joaquim A. Ribeiro; Ana M. Sebastião (Purinergic Signalling, 2014)

Alterations in the extracellular catabolism of nucleotides and platelet aggregation induced by high-fat diet in rats: effects of α-tocopherol - Jessié M. Gutierres; Fabiano B. Carvalho; Maria Rosa C. Schetinger; Marília V. Rodrigues; Juliano M. Vieira; Paula Maldonado; Maria do Carmo S. Araújo; Roberta Schmatz; Naiara Stefanello; Jeandre A. S. Jaques; Marcio Costa; Vera Morsch; et al. (Journal of Physiology and Biochemistry, 2014)

Tumor necrosis factor beta (TNF-β) NcoI polymorphism is associated with multiple sclerosis in Caucasian patients from Southern Brazil independently from HLA-DRB1 - A. P. Kallaur; S. R. Oliveira; A. N. C. Simão; E. R. D. de Almeida; H. K. Morimoto; J. Lopes; L. M. Pelegrino; W. L. C. J. de Pereira; Daniele Frizon Alfieri; R. M. Andrade; S. D. Borelli; M. A. E. Watanabe; et al. (Journal of Molecular Neuroscience, 2014)

Neotropical small mammals’ diversity in the early cycle of commercial Eucalyptus plantations - Luís M. Rosalino; Paula S. Martin; Carla Gheler-Costa; Paula C. Lopes; Luciano M. Verdade (Agroforestry Systems, 2014)

Resource Utilization and Temporal Segregation of Scarabaeinae (Coleoptera, Scarabaeidae) Community in a Caatinga Fragment - A M Medina; P P Lopes (Neotropical Entomology, 2014)

Shorebird low spillover risk of mosquito-borne pathogens on Iberian wetlands - Sara Pardal; José A. Alves; Líbia Zé-Zé; Hugo Osório; Afonso Rocha; Ricardo J. Lopes; Pete Potts; Fátima Amaro; Francisco Santiago-Quesada; Juan M. Sanchez-Guzman; José Masero; Maria J. Alves; et al. (Journal of Ornithology, 2014)

Remarkably low genetic diversity and strong population structure in common bottlenose dolphins (Tursiops truncatus) from coastal waters of the Southwestern Atlantic Ocean - Pedro F. Fruet; Eduardo R. Secchi; Fábio Daura-Jorge; Els Vermeulen; Paulo A. C. Flores; Paulo César Simões-Lopes; Rodrigo Cézar Genoves; Paula Laporta; Juliana C. Di Tullio; Thales Renato O. Freitas; Luciano Dalla Rosa; Victor Hugo Valiati; et al. (Conservation Genetics, 2014)

Co-management and Spatial Features Contribute to Secure Fish Abundance and Fishing Yields in Tropical Floodplain Lakes - Renato A. M. Silvano; Gustavo Hallwass; Priscila F. Lopes; Ariane R. Ribeiro; Renata P. Lima; Heinrich Hasenack; Anastácio A. Juras; Alpina Begossi (Ecosystems, 2014)

Resistance of Sugarcane Cultivars to Mahanarva fimbriolata (Stål) (Hemiptera: Cercopidae) - L L Dinardo-Miranda; V P da Costa; J V Fracasso; D Perecin; M C de Oliveira; T S Izeppi; D O P Lopes (Neotropical Entomology, 2014)

Cork stoppers as an effective sorbent for water treatment: the removal of mercury at environmentally relevant concentrations and conditions - Cláudia B. Lopes; Joana R. Oliveira; Luciana S. Rocha; Daniela S. Tavares; Carlos M. Silva; Susana P. Silva; Niels Hartog; Armando C. Duarte; E. Pereira (Environmental Science and Pollution Research, 2014)

Detection of RHDVa on the Iberian Peninsula: isolation of an RHDVa strain from a Spanish rabbitry - Joana Abrantes; Ana M. Lopes; Kevin P. Dalton; Francisco Parra; Pedro J. Esteves (Archives of Virology, 2014)

An empirical assessment of the consistency of taxonomic identifications - Philip F. Culverhouse; Norman Macleod; Robert Williams; Mark C. Benfield; Rubens M. Lopes; Marc Picheral (Marine Biology Research, 2014)

Oxidative stress parameters in blood, liver, and kidney of diabetic rats treated with curcumin and/or insulin - Heloisa Einloft Palma; Patrícia Wolkmer; Miguel Gallio; Marcos M. B. Corrêa; Roberta Schmatz; Gustavo R. Thomé; Luciane B. Pereira; Verônica S. P. Castro; Andréia B. Pereira; Andressa Bueno; Lizielle S. de Oliveira; Debora Rosolen; et al. (Molecular and Cellular Biochemistry, 2014)

Multidimensional scaling visualization of earthquake phenomena - António M. Lopes; J. A. Tenreiro Machado; C. M. A. Pinto; A. M. S. F. Galhano (Journal of Seismology, 2014)

Developmental and physiological challenges of octopus (Octopus vulgaris) early life stages under ocean warming - Tiago Repolho; Miguel Baptista; Marta S. Pimentel; Gisela Dionísio; Katja Trübenbach; Vanessa M. Lopes; Ana Rita Lopes; Ricardo Calado; Mário Diniz; Rui Rosa (Journal of Comparative Physiology B, 2014)

Seed structure, germination, and reserve mobilization in Butia capitata (Arecaceae) - N. C. C. Oliveira; P. S. N. Lopes; L. M. Ribeiro; M. O. Mercandante-Simões; L. A. A. Oliveira; F. O. Silvério (Trees, 2013)

Transboundary Socio-Ecological Effects of a Marine Protected Area in the Southwest Atlantic - Priscila F. M. Lopes; Renato A. M. Silvano; Vinicius A. Nora; Alpina Begossi (Ambio, 2013)

Characterization of a multidrug-resistant chronic myeloid leukemia cell line presenting multiple resistance mechanisms - Nathalia Daflon-Yunes; Flavio Eduardo Pinto-Silva; Raphael Silveira Vidal; Bruna Fortunato Novis; Tandressa Berguetti; Raphael Rodrigues Soares Lopes; Carla Polycarpo; Vivian M. Rumjanek (Molecular and Cellular Biochemistry, 2013)

Improving a Two-Equation Turbulence Model for Canopy Flows Using Large-Eddy Simulation - A.Silva Lopes; J. M. L. M. Palma; J. Viana Lopes (Boundary-Layer Meteorology, 2013)

Physiological and behavioral responses of temperate seahorses (Hippocampus guttulatus) to environmental warming - Maria Aurélio; Filipa Faleiro; Vanessa M. Lopes; Vanessa Pires; Ana Rita Lopes; Marta S. Pimentel; Tiago Repolho; Miguel Baptista; Luís Narciso; Rui Rosa (Marine Biology, 2013)

Antifungal activity of Ferulago capillaris essential oil against Candida, Cryptococcus, Aspergillus and dermatophyte species - E. Pinto; K. Hrimpeng; G. Lopes; S. Vaz; M. J. Gonçalves; C. Cavaleiro; L. Salgueiro (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Natural regeneration of the herbaceous community in a semiarid region in Northeastern Brazil - J. M. F. F. Santos; D. M. Santos; C. G. R. Lopes; K. A. Silva; E. V. S. B. Sampaio; E. L. Araújo (Environmental Monitoring and Assessment, 2013)

Complete coding sequences of European brown hare syndrome virus (EBHSV) strains isolated in 1982 in Sweden - Ana M. Lopes; Dolores Gavier-Widén; Ghislaine Le Gall-Reculé; Pedro J. Esteves; Joana Abrantes (Archives of Virology, 2013)

Reproductive traits of E uterpina acutifrons in a coastal area of S outheastern B razil - Mauro de Melo Júnior; Leonardo K. Miyashita; Naira J. Silva; Salvador A. Gaeta; Rubens M. Lopes (Marine Ecology, 2013)
We investigated the reproductive biology of the planktonic harpacticoid copepod Euterpina acutifrons , including morphometric data, egg production rates ( EPR ) and viability, and weight‐specific egg production. Experiments were carried out during 1 year in an inner‐shelf area off U batuba ( SE B razil), a site seasonally influenced by bottom intrusions of the relatively cold and nutrient‐rich South A tlantic C entral W ater ( SACW ). We hypothesized that E . acutifrons attain higher reproductive rates when SACW penetrates in this region. Live females were incubated individually in cell culture plates during two periods of 24 h each, under controlled temperature and light conditions. E uterpina acutifrons carried on average 16.9 ± 6.9 eggs·sac −1 , ranging between 10.8 ± 5.7 and 30.8 ± 7.4 eggs·sac −1 . Estimated EPR s ranged from 6.3 ± 3.4 to 13.6 ± 4.2 eggs·female −1 ·day −1 , with mean weight‐specific egg production rates of 0.06 ± 0.04 and 0.17 ± 0.08 per day. Euterpina acutifrons was not directly influenced by SACW intrusions, but body length and clutch size were positively related to temperature and chlorophyll content. Egg hatching time was clearly dependent on water temperature, as a 2 °C increase resulted in a decrease of 15 h in egg hatching time. This shows that even a small variation in temperature may considerably affect E . acutifrons population dynamics. Reproductive traits of this pelagic harpacticoid seem, therefore, to be controlled by the trade‐offs between increased food supply and the metabolic demands at low temperatures associated with SACW bottom intrusions toward this coastal area.

Pharmacological characterization of Solanum cernuum Vell.: 31-norcycloartanones with analgesic and anti-inflammatory properties - Luciane C. Lopes; João Ernesto de Carvalho; Marise Kakimore; Débora B. Vendramini-Costa; Maria A. Medeiros; Humberto M. Spindola; Javier Ávila-Román; Ana M. Lourenço; Virginia Motilva (Inflammopharmacology, 2013)

Genetic Diversity and Pathogenicity of Metarhizium spp. Associated with the White Grub Phyllophaga capillata (Blanchard) (Coleoptera: Melolonthidae) in a Soybean Field - R B Lopes; D A Souza; C M Oliveira; M Faria (Neotropical Entomology, 2013)

Betaine–homocysteine methyltransferase 742G>A polymorphism and risk of down syndrome offspring in a Brazilian population - Márcia R. Amorim; Cláudia M. Moura; Aline D. Gomes; Hazel N. Barboza; Roberta B. Lopes; Márcia G. Ribeiro; Marcelo A. Costa Lima (Molecular Biology Reports, 2013)

Blockade of cannabinoid receptors reduces inflammation, leukocyte accumulation and neovascularization in a model of sponge-induced inflammatory angiogenesis - Rodrigo Guabiraba; Remo C. Russo; Amanda M. Coelho; Mônica A. N. D. Ferreira; Gabriel A. O. Lopes; Ariane K. C. Gomes; Silvia P. Andrade; Luciola S. Barcelos; Mauro M. Teixeira (Inflammation Research, 2013)

Limit Equilibrium Analyses for Internal Design of Geosynthetic Reinforced Slopes: Influence of Potential Failure Surface and Strength Distribution - Castorina Silva Vieira; Maria de Lurdes Lopes; Laura M. Caldeira (Geotechnical and Geological Engineering, 2013)

Development and validation of an experimental life support system for assessing the effects of global climate change and environmental contamination on estuarine and coastal marine benthic communities - Francisco J. R. C. Coelho; Rui J. M. Rocha; Ana C. C. Pires; Bruno Ladeiro; José M. Castanheira; Rodrigo Costa; Adelaide Almeida; Ângela Cunha; Ana Isabel Lillebø; Rui Ribeiro; Ruth Pereira; Isabel Lopes; et al. (Global Change Biology, 2013)
An experimental life support system ( ELSS ) was constructed to study the interactive effects of multiple stressors on coastal and estuarine benthic communities, specifically perturbations driven by global climate change and anthropogenic environmental contamination. The ELSS allows researchers to control salinity, pH , temperature, ultraviolet radiation ( UVR ), tidal rhythms and exposure to selected contaminants. Unlike most microcosms previously described, our system enables true independent replication (including randomization). In addition to this, it can be assembled using commercially available materials and equipment, thereby facilitating the replication of identical experimental setups in different geographical locations. Here, we validate the reproducibility and environmental quality of the system by comparing chemical and biological parameters recorded in our ELSS with those prevalent in the natural environment. Water, sediment microbial community and ragworm (the polychaete Hediste diversicolor ) samples were obtained from four microcosms after 57 days of operation. In general, average concentrations of dissolved inorganic nutrients ( NO 3 − ; NH 4 + and PO 4 −3 ) in the water column of the ELSS experimental control units were within the range of concentrations recorded in the natural environment. While some shifts in bacterial community composition were observed between in situ and ELSS sediment samples, the relative abundance of most metabolically active bacterial taxa appeared to be stable. In addition, ELSS operation did not significantly affect survival, oxidative stress and neurological biomarkers of the model organism Hediste diversicolor . The validation data indicate that this system can be used to assess independent or interactive effects of climate change and environmental contamination on benthic communities. Researchers will be able to simulate the effects of these stressors on processes driven by microbial communities, sediment and seawater chemistry and to evaluate potential consequences to sediment toxicity using model organisms such as Hediste diversicolor .

Erratum to: QTL for yield and associated traits in the Seri/Babax population grown across several environments in Mexico, in the West Asia, North Africa, and South Asia regions - Marta S. Lopes; Matthew P. Reynolds; C. Lynne McIntyre; Ky L. Mathews; M. R. Jalal Kamali; Moussa Mossad; Yousef Feltaous; Izzat S. A. Tahir; Ravish Chatrath; Francis Ogbonnaya; Michael Baum (Theoretical and Applied Genetics, 2013)

Natural heavy metal and metalloid concentrations in sediments of the Minho River estuary (Portugal): baseline values for environmental studies - M. Mil-Homens; A. M. Costa; S. Fonseca; M. A. Trancoso; C. Lopes; R. Serrano; R. Sousa (Environmental Monitoring and Assessment, 2013)

Air quality assessment of Estarreja, an urban industrialized area, in a coastal region of Portugal - M. L. Figueiredo; A. Monteiro; M. Lopes; J. Ferreira; C. Borrego (Environmental Monitoring and Assessment, 2013)

Manganese-exposed developing rats display motor deficits and striatal oxidative stress that are reversed by Trolox - Fabiano M. Cordova; Aderbal S. Aguiar; Tanara V. Peres; Mark W. Lopes; Filipe M. Gonçalves; Daniela Z. Pedro; Samantha C. Lopes; Célso Pilati; Rui D. S. Prediger; Marcelo Farina; Keith M. Erikson; Michael Aschner; et al. (Archives of Toxicology, 2013)

Global environmental changes: setting priorities for Latin American coastal habitats - Alexander Turra; Aldo Cróquer; Alvar Carranza; Andrés Mansilla; Arsenio J. Areces; Camilo Werlinger; Carlos Martínez‐Bayón; Cristina Aparecida Gomes Nassar; Estela Plastino; Evangelina Schwindt; Fabrizio Scarabino; Fungyi Chow; et al. (Global Change Biology, 2013)
As the effects of the Global Climate Changes on the costal regions of Central and South Americas advance, there is proportionally little research being made to understand such impacts. This commentary puts forward a series of propositions of strategies to improve performance of Central and South American science and policy making in order to cope with the future impacts of the Global Climate Changes in their coastal habitats.

Inferred kinship patterns reveal low levels of extra-pair paternity in the endangered Neotropical Jabiru Stork (Jabiru mycteria, Aves: Ciconiiformes) - Iara F. Lopes; Carolina I. Miño; Cristiano D. Rocha; Dalci M. M. Oliveira; Silvia N. Del Lama (Genetica, 2013)

Chemical composition and in vitro schistosomicidal activity of the essential oil from the flowers of Bidens sulphurea (Asteraceae) - G.P. Aguiar; N.I. Melo; K.A.L. Wakabayashi; M.H.S. Lopes; A.L.L. Mantovani; H.J. Dias; M.J. Fukui; L.C. Keles; V. Rodrigues; M. Groppo; A.A. Silva-Filho; W.R. Cunha; et al. (Natural Product Research, 2013)

Competitive Removal of Cd2+ and Hg2+ Ions from Water Using Titanosilicate ETS-4: Kinetic Behaviour and Selectivity - Simão P. Cardoso; Cláudia B. Lopes; Eduarda Pereira; Armando C. Duarte; Carlos M. Silva (Water, Air, & Soil Pollution, 2013)

Characterization of Heavy-Metal Contamination in Surface Sediments of the Minho River Estuary by way of Factor Analysis - M. Mil-Homens; A. M. Costa; S. Fonseca; M. A. Trancoso; C. Lopes; R. Serrano; R. Sousa (Archives of Environmental Contamination and Toxicology, 2013)

QTL for yield and associated traits in the Seri/Babax population grown across several environments in Mexico, in the West Asia, North Africa, and South Asia regions - Marta S. Lopes; Matthew P. Reynolds; C. Lynne McIntyre; Ky L. Mathews; M. R. Jalal Kamali; Moussa Mossad; Yousef Feltaous; Izzat S. A. Tahir; Ravish Chatrath; Francis Ogbonnaya; Michael Baum (Theoretical and Applied Genetics, 2013)

Numerical simulation of sand dune erosion - A. M. G. Lopes; L. A. Oliveira; Almerindo D. Ferreira; J. P. Pinto (Environmental Fluid Mechanics, 2013)

Cytotoxic and leishmanicidal properties of garcinielliptone FC, a prenylated benzophenone from Platonia insignis - Joaquim S. Costa Júnior; Antonia Amanda Cardoso de Almeida; Alexandre de Barros Falcão Ferraz; Raíssa Rebés Rossatto; Teresinha G. Silva; Paulo B.N. Silva; Gardenia C.G. Militão; Antonia Maria das Graças Lopes Citó; Lorena Citó Lopes Resende Santana; Fernando Aécio de Amorim Carvalho; Rivelilson M. Freitas (Natural Product Research, 2013)

Lamellar Liquid Crystalline Phases for Cutaneous Delivery of Paclitaxel: Impact of the Monoglyceride - Jaclyn M. Hosmer; Alexandre A. Steiner; Luciana B. Lopes (Pharmaceutical Research, 2013)

Structure of the zygotic embryos and seedlings of Butia capitata (Arecaceae) - H. M. Magalhães; P. S. N. Lopes; L. M. Ribeiro; B. F. Sant’Anna-Santos; D. M. T. Oliveira (Trees, 2013)

Birds as reservoirs for Borrelia burgdorferi s.l. in Western Europe: circulation of B. turdi and other genospecies in bird–tick cycles in Portugal - A. C. Norte; J. A. Ramos; L. Gern; M. S. Núncio; I. Lopes de Carvalho (Environmental Microbiology, 2013)
Summary Birds are important in the ecology of Borrelia burgdorferi sensu lato (s.l.) because they are important hosts for vector tick immature stages and are known reservoirs for some Borrelia genospecies. The aim of our study was to assess the role of common passerine bird species as reservoirs for B. burgdorferi s.l. in Western Europe. We surveyed birds in enzootic areas in Portugal, where no information is available for birds as reservoirs for this aetiologic agent and where B. lusitaniae , for which few reservoirs have been identified, is the dominant genospecies. Twenty‐three birds (2.9%), including Turdus merula , T. philomelos , Parus major and Fringilla coelebs harboured infected ticks, but only Turdus sp. harboured infected tick larvae. In one study area, although B. lusitaniae was dominant in questing Ixodes ricinus , no ticks feeding on birds were infected with this genospecies, and B. valaisiana was the dominant genospecies in I. ricinus larvae feeding on birds. In the other area ticks collected from birds were mainly I. frontalis which were infected with B. turdi . Two skin biopsies (4.2%) from two T. merula were positive, one for B. valaisiana and the other for B. turdi . This is the first report for B. turdi in Western Europe.

Do different subspecies of Black-tailed Godwit Limosa limosa overlap in Iberian wintering and staging areas? Validation with genetic markers - Ricardo J. Lopes; José A. Alves; Jennifer A. Gill; Tómas G. Gunnarsson; Jos C. E. W. Hooijmeijer; Pedro M. Lourenço; Jose A. Masero; Theunis Piersma; Peter M. Potts; Bruno Rabaçal; Sandra Reis; Juan M. Sánchez-Guzman; et al. (Journal of Ornithology, 2013)

Analysis of longitudinal data of beef cattle raised on pasture from northern Brazil using nonlinear models - Fernando B. Lopes; Marcelo C. da Silva; Ednira G. Marques; Concepta M. McManus (Tropical Animal Health and Production, 2012)

Two New Species of Ectobiidae (Blattaria) Collected in the Santa Lúcia Biological Reserve, Espírito Santo, Brazil - S M Lopes; E H de Oliveira; M Assumpção (Neotropical Entomology, 2012)

Fluctuation analysis of respiratory impedance waveform in asthmatic patients: effect of airway obstruction - J. Veiga; A. J. Lopes; J. M. Jansen; P. L. Melo (Medical & Biological Engineering & Computing, 2012)

Reproduction in Octocorallia: Synchronous spawning and asynchronous oogenesis in the pennatulid Veretillum cynomorium - Vanessa M. Lopes; Miguel Baptista; Marta S. Pimentel; Tiago Repolho; Luis Narciso; Rui Rosa (Marine Biology Research, 2012)

Diversity and seasonal patterns of ticks parasitizing wild birds in western Portugal - A. C. Norte; I. Lopes de Carvalho; J. A. Ramos; M. Gonçalves; L. Gern; M. S. Núncio (Experimental and Applied Acarology, 2012)

Redox balance and mitochondrial glycerol phosphate dehydrogenase activity in trained rats - Gustavo Casimiro-Lopes; Dionizio Ramos; Martha M. Sorenson; Verônica P. Salerno (European Journal of Applied Physiology, 2012)

Competitive Sorption of Arsenate and Phosphate on Aluminum Mining By-product - E. T. S. Costa; L. R. G. Guilherme; G. Lopes; J. M. Lima; N. Curi (Water, Air, & Soil Pollution, 2012)

Development of a bovine luteal cell in vitro culture system suitable for co-culture with early embryos - M. Batista; A. Torres; P. Diniz; L. Mateus; L. Lopes-da-Costa (In Vitro Cellular & Developmental Biology - Animal, 2012)

Adenosine Deaminase Activity in Serum and Lymphocytes of Rats Infected with Sporothrix schenckii - Verônica S. P. Castro; Victor C. Pimentel; Aleksandro S. Da Silva; Gustavo R. Thomé; Patrícia Wolkmer; Jorge L. C. Castro; Márcio M. Costa; Cássia B. da Silva; Daniele C. Oliveira; Sydney H. Alves; Maria R. C. Schetinger; Sonia T. A. Lopes; et al. (Mycopathologia, 2012)

Ecological determinism increases with organism size - Vinicius F. Farjalla; Diane S. Srivastava; Nicholas A. C. Marino; Fernanda D. Azevedo; Viviane Dib; Paloma M. Lopes; Alexandre S. Rosado; Reinaldo L. Bozelli; Francisco A. Esteves (Ecology, 2012)
After much debate, there is an emerging consensus that the composition of many ecological communities is determined both by species traits, as proposed by niche theory, as well as by chance events. A critical question for ecology is, therefore, which attributes of species predict the dominance of deterministic or stochastic processes. We outline two hypotheses by which organism size could determine which processes structure ecological communities, and we test these hypotheses by comparing the community structure in bromeliad phytotelmata of three groups of organisms (bacteria, zooplankton, and macroinvertebrates) that encompass a 10 000‐fold gradient in body size, but live in the same habitat. Bacteria had no habitat associations, as would be expected from trait‐neutral stochastic processes, but still showed exclusion among species pairs, as would be expected from niche‐based processes. Macroinvertebrates had strong habitat and species associations, indicating niche‐based processes. Zooplankton, with body size between bacteria and macroinvertebrates, showed intermediate habitat associations. We concluded that a key niche process, habitat filtering, strengthened with organism size, possibly because larger organisms are both less plastic in their fundamental niches and more able to be selective in dispersal. These results suggest that the relative importance of deterministic and stochastic processes may be predictable from organism size.

Toxicity and genotoxicity of organic and inorganic nanoparticles to the bacteria Vibrio fischeri and Salmonella typhimurium - I. Lopes; R. Ribeiro; F. E. Antunes; T. A. P. Rocha-Santos; M. G. Rasteiro; A. M. V. M. Soares; F. Gonçalves; R. Pereira (Ecotoxicology, 2012)

Responses of CYP450 dependent system to aliphatic and aromatic hydrocarbons body burden in transplanted mussels from South coast of Portugal - B. Lopes; A. M. Ferreira; M. J. Bebianno (Ecotoxicology, 2012)

Sensory Handedness is not Reflected in Cortical Responses After Basic Nerve Stimulation: A MEG Study - Andrew C. N. Chen; Peter J. Theuvenet; Jan C. de Munck; Maria J. Peters; Jan M. van Ree; Fernando L. Lopes da Silva (Brain Topography, 2012)

Analysis of Insect Cuticular Compounds by Non-lethal Solid Phase Micro Extraction with Styrene-Divinylbenzene Copolymers - M. J. Ferreira-Caliman; I. C. C. Turatti; N. P. Lopes; R. Zucchi; F. S. Nascimento (Journal of Chemical Ecology, 2012)

von Willebrand Factor Permeates Small Vessels in CADASIL and Inhibits Smooth Muscle Gene Expression - Xiaojie Zhang; He Meng; Mila Blaivas; Elisabeth J. Rushing; Brian E. Moore; Jessica Schwartz; M. Beatriz S. Lopes; Bradford B. Worrall; Michael M. Wang (Translational Stroke Research, 2012)

Somatic embryogenesis induction system for cloning an adult Cyphomandra betacea (Cav.) Sendt. (tamarillo) - Sandra Correia; Maria Ludovina Lopes; Jorge M. Canhoto (Trees, 2011)

In vitro optimization of retinoic acid–induced neuritogenesis and TH endogenous expression in human SH-SY5Y neuroblastoma cells by the antioxidant Trolox - Mario Luiz Conte da Frota Junior; André Simões Pires; Fares Zeidán-Chuliá; Ivi Juliana Bristot; Fernanda M. Lopes; Matheus Augusto de Bittencourt Pasquali; Alfeu Zanotto-Filho; Guilherme Antônio Behr; Fabio Klamt; Daniel Pens Gelain; José Cláudio Fonseca Moreira (Molecular and Cellular Biochemistry, 2011)

How the concentration of insulin affects the development of preantral follicles in goats - R. N. Chaves; A. M. C. V. Alves; L. R. Faustino; K. P. L. Oliveira; C. C. Campello; C. A. P. Lopes; S. N. Báo; J. R. Figueiredo (Cell and Tissue Research, 2011)

Clustered transcripts that escape X inactivation at mouse XqD - Alexandra M. Lopes; Sarah E. Arnold-Croop; António Amorim; Laura Carrel (Mammalian Genome, 2011)

Decision‐making processes by small‐scale fishermen on the southeast coast of Brazil - P. F. M. LOPES; A. BEGOSSI (Fisheries Management and Ecology, 2011)
Brazilian shrimp trawlers and gillnetters were compared regarding their decisions concerning effort, processing of fish, time spent fishing and how they are affected by environmental, cultural and economic factors. Landings were recorded over 13 months ( n = 424) and comprised mainly sea bob shrimp ‐ Xyphopenaeus kroyeri (Heller) (95% of the trawler catch) and weakfish, Cynoscion jamaicensis (Vaillant & Bocourt) (30% of the gillnet catch). Catch per Unit of Effort varied across months, and the number of fishing trips per day was explained by wave height for both fisheries (trawlers: r 2 = 0.4; gillnetters: r 2 = 0.18). Trawlers spent more time fishing in the winter ( H = 11.6; P 0.05) and gillnetters in the summer ( F = 4.1; P 0.001), a decision that depended on the monetary profit they estimated beforehand or on the loss they had during the closed season. Cultural and economic variables (qualitatively addressed), such as how tedious they considered processing the catch or how much money they needed to make, affected their choice of processing it or not. Trawlers were subjected to taking risky actions, fishing on days when the return is highly variable ( r kg = 0.72; P 0.001; r $ = 0.65; P 0.001). Understanding such processes underpinning fishermen’s actions is essential for management.

Vertical inheritance and bursts of transposition have shaped the evolution of the BS non-LTR retrotransposon in Drosophila - Adriana Granzotto; Fabrício R. Lopes; Cristina Vieira; Claudia M. A. Carareto (Molecular Genetics and Genomics, 2011)

Reinforcement with Geosynthetics of Walls of the Saltpans of the Aveiro Lagoon - D. M. Carlos; Margarida Pinho-Lopes (Geotechnical and Geological Engineering, 2011)

Role of the Damping Ratio of Reinforcement on the Behaviour of Geogrids-Reinforced Systems - Agostinho Mendonça; M-Lurdes Lopes (Geotechnical and Geological Engineering, 2011)

Molecular analysis of microbial diversity in corrosion samples from energy transmission towers - Valéria M. Oliveira; Patrícia F. Lopes-Oliveira; Michel R.Z. Passarini; Claudia B.A. Menezes; Walter R.C. Oliveira; Adriano J. Rocha; Lara D. Sette (Biofouling, 2011)

Anti-inflammatory properties of Doxycycline and Minocycline in experimental models: an in vivo and in vitro comparative study - Liz M. Leite; Antônio Germano G. Carvalho; Pollyanna L. F. Tavares Ferreira; Igor Xavier Pessoa; Danilo O. Gonçalves; Amanda de Araújo Lopes; Jean Guilherme dos Santos Góes; Victor Costa de Castro Alves; Luzia Kalyne A. M. Leal; Gerly Anne Brito; Glauce S. B. Viana (Inflammopharmacology, 2011)

Effects of the compounds MV8608 and MV8612 obtained from Mandevilla velutina in the model of hemorrhagic cystitis induced by cyclophosphamide in rats - André A. Santos; Paulo C. Leal; Maria I. A. Edelweiss; Tiago Giuliani Lopes; João B. Calixto; Fernanda B. Morrone; Maria M. Campos (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Seasonal contrasts in abundance and reproductive parameters of Penilia avirostris (Cladocera, Ctenopoda) in a coastal subtropical area - Leonardo K. Miyashita; Mayza Pompeu; Salvador A. Gaeta; Rubens M. Lopes (Marine Biology, 2010)

Soil/Geotextile Interface Behaviour in Direct Shear and Pullout Movements - M. L. Lopes; R. Silvano (Geotechnical and Geological Engineering, 2010)

Erratum to: Cleanup of atrazine-contaminated soils: ecotoxicological study on the efficacy of a bioremediation tool with Pseudomonas sp. ADP - Sónia Chelinho; Matilde Moreira-Santos; Débora Lima; Cátia Silva; Paula Viana; Sandra André; Isabel Lopes; Rui Ribeiro; Arsénio M. Fialho; Cristina A. Viegas; José P. Sousa (Journal of Soils and Sediments, 2010)

New primers for the amplification and sequencing of nuclear loci in a taxonomically wide set of reptiles and amphibians - Catarina Pinho; Sara Rocha; Bruno M. Carvalho; Susana Lopes; Sofia Mourão; Marcelo Vallinoto; Tuliana O. Brunes; Célio F. B. Haddad; Helena Gonçalves; Fernando Sequeira; Nuno Ferrand (Conservation Genetics Resources, 2010)

Biodegradation of epoxyconazole and piraclostrobin fungicides by Klebsiella sp. from soil - Flavio M. Lopes; Karla A. Batista; Gustavo L. A. Batista; Sydnei Mitidieri; Luiz Artur M. Bataus; Kátia F. Fernandes (World Journal of Microbiology and Biotechnology, 2010)

Investigation of the 22q11.2 candidate region in patients with midline facial defects with hypertelorism - M. Simioni; É. Lopes Freitas; T. Paiva Vieira; I. Lopes-Cendes; V. Lúcia Gil-da-Silva-Lopes (Journal of Applied Genetics, 2010)

Oral and parenteral vaccines against Flavobacterium columnare: evaluation of humoral immune response by ELISA and in vivo efficiency in Nile tilapia (Oreochromis niloticus) - C. A. G. Leal; G. A. Carvalho-Castro; P. S. C. Sacchetin; C. O. Lopes; A. M. Moraes; H. C. P. Figueiredo (Aquaculture International, 2010)

Comparative anticonvulsant activities of the essential oils (EOs) from Cymbopogon winterianus Jowitt and Cymbopogon citratus (DC) Stapf. in mice - Monalisa Ribeiro Silva; Rafael Matos Ximenes; José Galberto Martins da Costa; L. Kalyne A. M. Leal; Amanda A. de Lopes; Glauce Socorro de Barros Viana (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Kalirin: a novel genetic risk factor for ischemic stroke - Tiago Krug; Helena Manso; Liliana Gouveia; João Sobral; Joana M. Xavier; Isabel Albergaria; Gisela Gaspar; Manuel Correia; Miguel Viana-Baptista; Rita Moiron Simões; Amélia Nogueira Pinto; Ricardo Taipa; et al. (Human Genetics, 2010)

Cleanup of atrazine-contaminated soils: ecotoxicological study on the efficacy of a bioremediation tool with Pseudomonas sp. ADP - Sónia Chelinho; Matilde Moreira-Santos; Débora Lima; Cátia Silva; Paula Viana; Sandra André; Isabel Lopes; Rui Ribeiro; Arsénio M. Fialho; Cristina A. Viegas; José P. Sousa (Journal of Soils and Sediments, 2010)

Evaluation of Chlorine Decay in Drinking Water Systems for Different Flow Conditions: From Theory to Practice - Helena M. Ramos; D. Loureiro; A. Lopes; C. Fernandes; D. Covas; L. F. Reis; M. C. Cunha (Water Resources Management, 2010)

Establishment and characterization of androgen-independent human prostate cancer cell lines, PcBra1, PcBra2, and PcBra3 - Camila B. Piantino; Juliana M. Sousa-Canavez; Marta Bellodi-Privato; Miguel Srougi; Luiz Heraldo Camara-Lopes; Gilka Jorge Figaro Gattás; Fernanda de Toledo Gonçalves; Cintia Fridman; Katia R. M. Leite (In Vitro Cellular & Developmental Biology - Animal, 2010)

Establishment and characterization of human bladder cancer cell lines BexBra1, BexBra2, and BexBra4 - Camila B. Piantino; Juliana M. Sousa-Canavez; Victor Srougi; Fernanda Salvadori; Raphael Kato; Pedro Paulo R. Ayres; Miguel Srougi; Luiz Heraldo Camara-Lopes; Gilka Jorge Figaro Gattás; Cintia Fridman; Fernanda de Toledo; Isaque Santana; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

Comparison of a test battery for assessing the toxicity of a bleached-kraft pulp mill effluent before and after secondary treatment implementation - R. Rosa; M. Moreira-Santos; I. Lopes; L. Silva; J. Rebola; E. Mendonça; A. Picado; R. Ribeiro (Environmental Monitoring and Assessment, 2010)

European bee-eater (Merops apiaster) populations under arsenic and metal stress: evaluation of exposure at a mining site - I. Lopes; A. Sedlmayr; M. Moreira-Santos; I. Moreno-Garrido; J. Blasco; R. Ribeiro (Environmental Monitoring and Assessment, 2010)

A moderate intake of phytosterols from habitual diet affects cholesterol metabolism - T. Sanclemente; I. Marques-Lopes; M. Fajó-Pascual; M. Cofán; E. Jarauta; E. Ros; J. Puzo; A. L. García-Otín (Journal of Physiology and Biochemistry, 2009)

TP53 germline mutations in Portugal and genetic modifiers of age at cancer onset - Carla Pinto; Isabel Veiga; Manuela Pinheiro; Ana Peixoto; Armando Pinto; José M. Lopes; Rui M. Reis; Carla Oliveira; Manuela Baptista; Lúcia Roque; Fernando Regateiro; Luís Cirnes; et al. (Familial Cancer, 2009)

Chemical Signals in the Stingless Bee, Frieseomelitta varia, Indicate Caste, Gender, Age, and Reproductive Status - Túlio M. Nunes; Izabel C. C. Turatti; Norberto P. Lopes; Ronaldo Zucchi (Journal of Chemical Ecology, 2009)

Expression Profile and Distribution of Efhc1 Gene Transcript During Rodent Brain Development - Fábio F. Conte; Patrícia A. O. Ribeiro; Rafael B. Marchesini; Vinícius D. B. Pascoal; Joelcimar M. Silva; Amanda R. Oliveira; Rovílson Gilioli; Lourenço Sbragia; Jackson C. Bittencourt; Iscia Lopes-Cendes (Journal of Molecular Neuroscience, 2009)

Mercury pollution in Ria de Aveiro (Portugal): a review of the system assessment - M. E. Pereira; A. I. Lillebø; P. Pato; M. Válega; J. P. Coelho; C. B. Lopes; S. Rodrigues; A. Cachada; M. Otero; M. A. Pardal; A. C. Duarte (Environmental Monitoring and Assessment, 2009)

Multiplicity of aspartic proteinases from Cynara cardunculus L. - Ana Cristina Sarmento; Henrique Lopes; Cláudia S. Oliveira; Rui Vitorino; Bart Samyn; Kjell Sergeant; Griet Debyser; Jozef Van Beeumen; Pedro Domingues; Francisco Amado; Euclides Pires; M. Rosário M. Domingues; et al. (Planta, 2009)

Cyclodextrins improve the antimicrobial activity of the chloride salt of Ruthenium(II) chloro-phenanthroline-trithiacyclononane - Joana Marques; Teresa M. Braga; Filipe A. Almeida Paz; Teresa M. Santos; Maria de Fátima Silva Lopes; Susana S. Braga (BioMetals, 2009)

Microemulsions Containing Medium-Chain Glycerides as Transdermal Delivery Systems for Hydrophilic and Hydrophobic Drugs - Jaclyn Hosmer; Rachel Reed; M. Vitória L.B. Bentley; Adwoa Nornoo; Luciana B. Lopes (AAPS PharmSciTech, 2009)

Three new species of Isospora Schneider, 1881 (Apicomplexa: Eimeriidae) from the buffy-fronted seedeater Sporophila frontalis Verreaux (Passeriformes: Emberizidae) in South America - Bruno P. Berto; Lianna M. C. Balthazar; Walter Flausino; Carlos W. G. Lopes (Systematic Parasitology, 2009)

Physiological responses of different olive genotypes to drought conditions - Eunice Areal Bacelar; José M. Moutinho-Pereira; Berta C. Gonçalves; João I. Lopes; Carlos M. Correia (Acta Physiologiae Plantarum, 2009)

Toxicity of MCPA on non-green potato tuber calli - Francisco P. Peixoto; M. Ludovina Lopes; Vítor M. C. Madeira; Joaquim A. F. Vicente (Acta Physiologiae Plantarum, 2009)

Relevant principal component analysis applied to the characterisation of Portuguese heather honey - Rui C. Martins; Victor V. Lopes; Patrícia Valentão; João C.M.F. Carvalho; Paulo Isabel; Maria T. Amaral; Maria T. Batista; Paula B. Andrade; Branca M. Silva (Natural Product Research, 2008)

Development and Sensitivity of a 12-h Laboratory Test with Daphnia magna Straus Based on Avoidance of Pulp Mill Effluents - R. Rosa; M. Moreira-Santos; I. Lopes; A. Picado; E. Mendonça; R. Ribeiro (Bulletin of Environmental Contamination and Toxicology, 2008)

Seasonal cell differentiation and olfactory potency of secretions by the anal glands of male peacock blenny Salaria Pavo - R. M. Serrano; O. Lopes; P. C. Hubbard; J. Araújo; A. V. M. Canário; E. N. Barata (Journal of Fish Biology, 2008)
The current study shows cytological differences between the anal glands of pre‐spawning and spawning peacock blennies Salaria pavo . The cytological differences in the anal gland coincide with higher olfactory potency of their secretions in spawning males, suggesting that seasonal differentiation of cell clusters secreting neutral mucins is related to the production and release of the putative sex pheromone.

Extracted and farmed shrimp fisheries in Brazil: economic, environmental and social consequences of exploitation - P. F. M. Lopes (Environment, Development and Sustainability, 2008)

A New Missense Mutation Found in the FLNA Gene in a Family with Bilateral Periventricular Nodular Heterotopia (BPNH) Alters the Splicing Process - Simone S. Tsuneda; Fabio R. Torres; Maria A. Montenegro; Marilisa M. Guerreiro; Fernando Cendes; Iscia Lopes-Cendes (Journal of Molecular Neuroscience, 2008)

A Proposed EPR Approach to Evaluating Agonist Binding Site of a Peptide Receptor - Douglas D. Lopes; Erick F. Poletti; Renata F. F. Vieira; Guita N. Jubilut; Laerte Oliveira; Antonio C. M. Paiva; Shirley Schreier; Clovis R. Nakaie (International Journal of Peptide Research and Therapeutics, 2008)

Gene expression, cellular localisation and function of glutamine synthetase isozymes in wheat (Triticum aestivum L.) - Stéphanie M. Bernard; Anders Laurell Blom Møller; Giuseppe Dionisio; Thomas Kichey; Thomas P. Jahn; Frederic Dubois; Marcela Baudo; Marta S. Lopes; Thérèse Tercé-Laforgue; Christine H. Foyer; Martin A. J. Parry; Brian G. Forde; et al. (Plant Molecular Biology, 2008)

ABCB1 (P-glycoprotein) but not ABCC1 (MRP1) is downregulated in peripheral blood mononuclear cells of spontaneously hypertensive rats - Raphael C. Valente; Luiz S. Capella; Clarissa R. Nascimento; Filipe Braga; Juliana Echevarria-Lima; Aníbal G. Lopes; Márcia A. M. Capella (Pflügers Archiv - European Journal of Physiology, 2008)

Animal Models for Genetic Neuromuscular Diseases - Mariz Vainzof; Danielle Ayub-Guerrieri; Paula C. G. Onofre; Poliana C. M. Martins; Vanessa F. Lopes; Dinorah Zilberztajn; Lucas S. Maia; Karen Sell; Lydia U. Yamamoto (Journal of Molecular Neuroscience, 2008)

The source of the 1722 Algarve earthquake: evidence from MCS and Tsunami data - M. A. Baptista; J. M. Miranda; Fernando C. Lopes; Joaquim F. Luis (Journal of Seismology, 2007)

Influence of biochemical, mineral and morphological features of natural food on tropical cladocerans - Claudia Fileto; Marlene S. Arcifa; Juliana M. Marchetti; Izabel C. Turati; Norberto P. Lopes (Aquatic Ecology, 2007)

Compressed matrix core tablet as a quick/slow dual-component delivery system containing ibuprofen - Carla Martins Lopes; José M. Sousa Lobo; João F. Pinto; Paulo C. Costa (AAPS PharmSciTech, 2007)

Simulation of the Askervein flow. Part 2: Large-eddy simulations - A. Silva Lopes; J. M. L. M. Palma; F. A. Castro (Boundary-Layer Meteorology, 2007)

Taxonomy of Euretidae (Porifera, Hexactinellida, Hexactinosida) of Campos Basin, southwestern Atlantic, with a description of a new species - Daniela A. Lopes; Eduardo Hajdu; Henry M. Reiswig (Marine Biology Research, 2007)

Ecological success of the cladoceran Penilia avirostris in the marine environment: feeding performance, gross growth efficiencies and life history - Dacha Atienza; Albert Calbet; Enric Saiz; Rubens M. Lopes (Marine Biology, 2007)

Physiological behaviour, oxidative damage and antioxidative protection of olive trees grown under different irrigation regimes - Eunice A. Bacelar; Dario L. Santos; José M. Moutinho-Pereira; João I. Lopes; Berta C. Gonçalves; Timóteo C. Ferreira; Carlos M. Correia (Plant and Soil, 2007)

Microzooplankton grazing of phytoplankton in a tropical upwelling region - George B. McManus; Barbara A. Costas; Hans G. Dam; Rubens M. Lopes; Salvador A. Gaeta; Sylvia M. Susini; Carol H. Rosetta (Hydrobiologia, 2007)

Cortical Characterization and Inter-Dipole Distance Between Unilateral Median Versus Ulnar Nerve Stimulation of Both Hands in MEG - Peter J. Theuvenet; Bob W. van Dijk; Maria J. Peters; Jan M. van Ree; Fernando L. Lopes da Silva; Andrew C. N. Chen (Brain Topography, 2006)

Taxonomic Considerations in Listing Subspecies Under the U.S. Endangered Species Act - SUSAN M. HAIG; ERIK A. BEEVER; STEVEN M. CHAMBERS; HOPE M. DRAHEIM; BRUCE D. DUGGER; SUSIE DUNHAM; ELISE ELLIOTT‐SMITH; JOSEPH B. FONTAINE; DYLAN C. KESLER; BRIAN J. KNAUS; IARA F. LOPES; PETE LOSCHL; et al. (Conservation Biology, 2006)
The U.S. Endangered Species Act (ESA) allows listing of subspecies and other groupings below the rank of species. This provides the U.S. Fish and Wildlife Service and the National Marine Fisheries Service with a means to target the most critical unit in need of conservation. Although roughly one‐quarter of listed taxa are subspecies, these management agencies are hindered by uncertainties about taxonomic standards during listing or delisting activities. In a review of taxonomic publications and societies, we found few subspecies lists and none that stated standardized criteria for determining subspecific taxa. Lack of criteria is attributed to a centuries‐old debate over species and subspecies concepts. Nevertheless, the critical need to resolve this debate for ESA listings led us to propose that minimal biological criteria to define disjunct subspecies (legally or taxonomically) should include the discreteness and significance criteria of distinct population segments (as defined under the ESA). Our subspecies criteria are in stark contrast to that proposed by supporters of the phylogenetic species concept and provide a clear distinction between species and subspecies. Efforts to eliminate or reduce ambiguity associated with subspecies‐level classifications will assist with ESA listing decisions. Thus, we urge professional taxonomic societies to publish and periodically update peer‐reviewed species and subspecies lists. This effort must be paralleled throughout the world for efficient taxonomic conservation to take place.

Effect of age of donor on embryo production in Morada Nova (white variety) ewes participating in a conservation programme in Brazil - E. S. Lopes Júnior; E. L. M. M. Maia; N. R. O. Paula; D. I. A. Teixeira; A. B. S. Villarroel; D. Rondina; V. J. F. Freitas (Tropical Animal Health and Production, 2006)

The effects of fructose-1,6-bisphosphate and dexamethasone on acute inflammation and T-cell proliferation - R. Pestana Lopes; A. Lunardelli; T. Preissler; C. E. Leite; J. C. F. Alves-Filho; F. Bordignon Nunes; J. Rodrigues de Oliveira; M. E. Bauer (Inflammation Research, 2006)

The ecological significance of the zooplanktivores, snipefish Macroramphosus spp. and boarfish Capros aper , in the food web of the south‐east North Atlantic - M. Lopes; A. G. Murta; H. N. Cabral (Journal of Fish Biology, 2006)
The diets of slender snipefish Macroramphosus gracilis , longspine snipefish Macroramphosus scolopax and boarfish Capros aper , three very abundant species on the Portuguese coast, were studied from samples collected between July 2002 and April 2003. Variations in the diet with fish size, season and area, as well as diet overlap and diversity, are explored in this study. The diets of slender snipefish and boarfish were mainly composed of copepods, with the main prey being Temora spp. and Calanus spp., respectively. Mysid shrimps were the most important food item in the diet of longspine snipefish. During the summer season, when the availability of different prey items was highest, the two species of snipefish and the boarfish fed on different prey. Temora spp. were the most important prey in the stomachs of slender snipefish in the summer on the south‐west coast, while Calanus spp. started appearing in the stomachs of boarfish in the spring in the north, increasing their abundance in the summer on the south and south‐west coasts. The abundance of mysids appeared to increase in the autumn on the south‐west coast, being at that time an important food item for both longspine snipefish and boarfish. For slender snipefish and boarfish, the differences in stomach species diversity were explained firstly by the season and then by the area and fish size. For longspine snipefish, the area did not explain the species diversity variability, season being the first variable determining the differences. Of all three species, slender snipefish was the one with highest diversity of stomach contents, particularly in spring and summer on the north and south‐west coasts. Diet overlap between species was very low. No predation on eggs and larval stages of fishes was found for any of these fish species. This work is the first to address the diets of snipefish species and boarfish in the south‐east North Atlantic, in a large spatio‐temporal coverage. These species are important prey for many commercial species on the Portuguese coast and, given their abundance, may have a great impact on zooplankton communities, thus assuming a pivotal position in marine food webs.

Reverse Hexagonal Phase Nanodispersion of Monoolein and Oleic Acid for Topical Delivery of Peptides: in Vitro and in Vivo Skin Penetration of Cyclosporin A - Luciana B. Lopes; Denise A. Ferreira; Daniel de Paula; M. Tereza J. Garcia; José A. Thomazini; Márcia C. A. Fantini; M. Vitória L. B. Bentley (Pharmaceutical Research, 2006)

Gp63-Like Molecules in Phytomonas serpens: Possible Role in the Insect Interaction - Claudia M. d’Avila-Levy; Lívia O. Santos; Fernanda A. Marinho; Felipe A. Dias; Angela H. Lopes; André L.S. Santos; Marta H. Branquinha (Current Microbiology, 2006)

Inactivation status of PCDH11X: sexual dimorphisms in gene expression levels in brain - Alexandra M. Lopes; Norman Ross; James Close; Adam Dagnall; António Amorim; Timothy J. Crow (Human Genetics, 2006)

In situ probing of Xylella fastidiosa in honeydew of a xylem sap‐feeding insect using 16S rRNA‐targeted fluorescent oligonucleotides - Jorge L. M. Rodrigues; Maria E. Silva‐Stenico; Adriane N. De Souza; João R. S. Lopes; Siu M. Tsai (Environmental Microbiology, 2006)
Summary Xylella fastidiosa is a plant pathogen that threatens a US$ 4.6 billion worldwide wine and citrus industry. Monitoring its presence and distribution in plants and vectors is crucial for designing control strategies, as well as for understanding its ecological role and fate. We developed two fluorescent oligonucleotide probes complementary to different regions of the 16S rRNA gene of X. fastidiosa . The specificity of the newly designed probes S‐S‐X.fas‐0067‐a‐A‐18 and S‐S‐X.fas‐1439‐a‐A‐18 was demonstrated using fluorescence in situ hybridization (FISH) for 12 Xylella isolates, 15 closely related microorganisms and three plant endophytes. These probes were used to detect and quantify X. fastidiosa in plant sap (average value of 2.9 ± 0.3 × 10 6 cells ml −1 ) from three different citrus orchards. In a second experiment, cells were quantified in honeydew (2.2 ± 0.2 × 10 4 cells ml −1 ) collected from the insect vector Bucephalogonia xanthophis during the acquisition access period on an infected plant. The number of pathogen cells retained or digested by the insect is 10 000 times greater than the estimated minimum value to ensure an efficient transmission. Polymerase chain reaction (PCR) amplification using specific primers with plant sap and honeydew samples, followed by sequencing, confirmed the presence of the plant pathogen. This is the first demonstration of FISH being used for environmental samples, such as plant sap and insect honeydew, to estimate the abundance of a plant pathogen during infection.

Infertility and marker chromosomes: Application of molecular cytogenetic techniques in a case of inv dup(15) - Tânia M. Vulcani-Freitas; Vera L. Gil-da-Silva-Lopes; Marileila Varella-Garcia; Andréa T. Maciel-Guerra (Journal of Applied Genetics, 2006)

Comparison of antagonistic ability against enteropathogens by G+ and G− anaerobic dominant components of human fecal microbiota - D. A. Gomes; A. M. L. Souza; R. V. Lopes; A. C. Nunes; J. R. Nicoli (Folia Microbiologica, 2006)

Cervical cancer and CYP2E1 polymorphisms: implications for molecular epidemiology - Paula M. Ferreira; Raquel Catarino; Deolinda Pereira; Ana Matos; Daniela Pinto; Ana Coelho; Carlos Lopes; Rui Medeiros (European Journal of Clinical Pharmacology, 2006)

Pathogenicity of Phytophthora species to Anthurium andraeanum in Brazil - M. C. A. Paim; E. D. M. N. Luz; J. T. De Souza; A. O. Cerqueira; J. R. M. Lopes (Australasian Plant Pathology, 2006)

Selection and Optimization of Culture Medium for Exopolysaccharide Production by Coriolus (Trametes) Versicolor - A. P. A. Tavares; M. S. M. Agapito; M. A. M. Coelho; J. A. Lopes da Silva; A. Barros-Timmons; J. A. J. Coutinho; A. M. R. B. Xavier (World Journal of Microbiology and Biotechnology, 2005)

Genetic Characterization of Brazilian Annual Arachis Species from Sections Arachis and Heteranthae using RAPD Markers - Silvana Creste; Siu Mui Tsai; José F. M. Valls; Marcos A. Gimenes; Catalina Romero Lopes (Genetic Resources and Crop Evolution, 2005)

Morphological, Biochemical and Molecular Approaches for Comparing Typical and Atypical Paracoccidioides brasiliensis Strains - Cìntia M. Borba; Ester A. L. Vinhas; Leila M. Lopes-Bezerra; Norma Lucena-Silva (Antonie van Leeuwenhoek, 2005)

Short term spatial and temporal variation of phytoplankton in a shallow tropical oligotrophic reservoir, southeast Brazil - Maria Rosélia Marques Lopes; Carlos E. de M. Bicudo; M. Carla Ferragut (Hydrobiologia, 2005)

Comparative Study of the Skin Penetration of Protein Transduction Domains and a Conjugated Peptide - Luciana B. Lopes; Colleen M. Brophy; Elizabeth Furnish; Charles R. Flynn; Olivia Sparks; Padmini Komalavilas; Lokesh Joshi; Alyssa Panitch; M. Vitoria L. B. Bentley (Pharmaceutical Research, 2005)

The effects of peroxovanadate and peroxovanadyl on glucose metabolism in vivo and identification of signal transduction proteins involved in the mechanism of action in isolated soleus muscle - Ricado Key Yamazaki; Sandro M. Hirabara; Osvaldo Tchaikovski; Maria Cecília Pascoal Lopes; Claudia Nogata; Júlia Aikawa; Everson A. Nunes; Ricardo A. Tanhoffer; Maurício D. Lissa; L. C. Fernandes (Molecular and Cellular Biochemistry, 2005)

Lack of Evidence for Metallothionein Role in Tolerance to Copper by Natural Populations of Daphnia longispina - N. Martins; I. Lopes; L. Guilhermino; M. J. Bebianno; R. Ribeiro (Bulletin of Environmental Contamination and Toxicology, 2005)

Malarial parasites decrease reproductive success: an experimental study in a passerine bird - Alfonso Marzal; Florentino de Lope; Carlos Navarro; Anders Pape Mller (Oecologia, 2005)

Variation of Mercury Contamination in Chicks of Little Tern Sterna albifrons in Southwest Europe: Brood, Age, and Colony Related Effects - P. C. Tavares; L. R. Monteiro; R. J. Lopes; M. E. Pereira; A. C. Duarte; R. W. Furness (Bulletin of Environmental Contamination and Toxicology, 2005)

Cytogenetic analysis of Ctenostomini by C-banding and rDNA localization and its relevance to the knowledge of the evolution of tiger beetles (Coleoptera: Cicindelidae) - Adilson Ariza Zacaro; Snia J. R. Proena; Cristiano Lopes-andrade; Artur R. M. Serrano (Genetica, 2004)

Binding of adenosine receptor ligands to brain of adenosine receptor knock-out mice: evidence that CGS 21680 binds to A1 receptors in hippocampus - Linda Halldner; Luisa V. Lopes; Elisabetta Dar; Karin Lindstrm; Bjrn Johansson; Catherine Ledent; Rodrigo A. Cunha; Bertil B. Fredholm (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Pleural empyema due to Salmonella enteritidis in a non-immunocompromised patient - M. Len Lope; P. Batalha; M. Sosa; F. J. Rodrguez-Gmez; A. Snchez-Muoz; E. Pujol; J. M. Aguado (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Does Aliphatic Chain Length Influence Carbocyanines' Orientation in Supported Lipid Multilayers? - S. Lopes; M. A. R. B. Castanho (Journal of Fluorescence, 2004)

Male reproductive system in the South American catfish Conorhynchus conirostris - D. C. J. R. Lopes; N. Bazzoli; M. F. G. Brito; T. A. Maria (Journal of Fish Biology, 2004)
The testes of the catfish Conorhynchus conirostris ( n = 67) from the São Francisco River, Minas Gerais, Brazil were of the fringed type, similar to those of some Pimelodidae. The germ, Sertoli and Leydig cells showed characteristics which are general for all vertebrates although the spermatozoa had a peculiar morphology, with an ovoid head without an acrosome, inverted U‐shaped nucleus, a short midpiece and a long tail, typical of teleosts showing external fertilization. The spermatic duct and genital papilla performed a secretory function.

Intraspecific Variation of Mercury Contamination in Chicks of Black-Winged Stilt ( Himantopus himantopus ) in Coastal Wetlands from Southwestern Europe - P. C. Tavares; L. R. Monteiro; R. J. Lopes; M. M. Correia Santos; R. W. Furness (Bulletin of Environmental Contamination and Toxicology, 2004)

Peroxidase and the biosynthesis of terpenoid indole alkaloids in the medicinal plant Catharanthus roseus (L.) G. Don - M. Sottomayor; I. Lopes Cardoso; L.G. Pereira; A. Ros Barceló (Phytochemistry Reviews, 2004)

Genetic variation within and among species of five sections of the genus Arachis L. (Leguminosae) using RAPDs - V. Sérgio Emílio Dos Santos; M. Aparecido Gimenes; J. Francisco Montenegro Valls; C. Romero Lopes (Genetic Resources and Crop Evolution, 2003)

Sperm utilisation by Melipona quadrifasciata Lepeletier (Hymenoptera, Apidae) queens subjected to multiple mating - D. M. Lopes; M. G. Tavares; L. A. O. Campos (Insectes Sociaux, 2003)

Magnesium-Dependent Ecto-ATP Diphosphohydrolase Activity in Herpetomonas muscarum muscarum - M. Alves-Ferreira; P.M.L. Dutra; A.H.C.S. Lopes; A. Ferreira-Pereira; H.M. Scofano; J.R. Meyer-Fernandes (Current Microbiology, 2003)

Resistance gene homologues in Theobroma cacao as useful genetic markers - D. N. Kuhn; M. Heath; R. J. Wisser; A. Meerow; J. S. Brown; U. Lopes; R. J. Schnell (Theoretical and Applied Genetics, 2003)

Construction and post-construction behaviour of a geogrid-reinforced steep slope - Agostinho Mendonça; M-Lurdes Lopes; Margarida Pinho-Lopes (Geotechnical and Geological Engineering, 2003)

Simulation of the Askervein Flow. Part 1: Reynolds Averaged Navier–Stokes Equations (k ∈ Turbulence Model) - F. A. Castro; J. M. L. M. Palma; A. Silva Lopes (Boundary-Layer Meteorology, 2003)

Reduced production of hyperalgesic substances by mononuclear cells from aged rats incubated with carrageenan: role of interleukin 2 and prostaglandins - L. S. M. Pereira; D. L. Ferreira-Alves; M. A. de Resende; V. A. Romualdo; W. G. P. dos Reis; M. T. P. Lopes; M. M. Santoro; J. N. Francischi (Inflammation Research, 2003)

Helicobacter pylori Virulence Genotypes in Portuguese Children and Adults with Gastroduodenal Pathology - M. Oleastro; M. Gerhard; A. I. Lopes; P. Ramalho; J. Cabral; A. Sousa Guerreiro; L. Monteiro (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Dexamethasone induces the secretion of annexin I in immature lymphoblastic cells by a calcium-dependent mechanism - M. Castro-Caldas; C.B. Duarte; A.P. Carvalho; M.C. Fernandes Lopes (Molecular and Cellular Biochemistry, 2002)

Arginine vasopressin regulates CFTR and ClC-2 mRNA expression in rat kidney cortex and medulla - Marcelo M. Morales; Danielle S. Nascimento; Márcia A. Capella; Aníbal G. Lopes; William B. Guggino (Pflügers Archiv - European Journal of Physiology, 2001)

Interaction between the adrenal and the pineal gland in chronic experimental inflammation induced by BCG in mice - C. Lopes; M. Mariano, R.P. Markus (Inflammation Research, 2001)

Effects of Human Colonization on the Abundance and Diversity of Mammals in Eastern Brazilian Amazonia - M. Aparecida Lopes; Stephen F. Ferrari (Conservation Biology, 2000)

Effects of Human Colonization on the Abundance and Diversity of Mammals in Eastern Brazilian Amazonia - M. Aparecida Lopes; Stephen F. Ferrari (Conservation Biology, 2000)
With its long history of colonization, eastern Amazonia has the highest population density in Brazilian Amazonia and represents the typical pattern of recent human occupation. Between 1991 and 1995, we surveyed the mammalian fauna at five sites, representing different degrees of human disturbance. We used line transects (1511 km surveyed) to describe differences in diversity and abundance at each site and to evaluate the effects of environmental factors. Twenty‐two of the expected 44 species were recorded during surveys, but no more than 18 were recorded at any one site, and only 3 species were observed at all five sites. Despite a minimum transect length of 202 km, most species were recorded relatively infrequently at all sites, although overall sighting rates at different sites varied by more than 100%. Between‐site differences were even more pronounced when we compared specific groups (e.g., arboreal, terrestrial, game, nongame), reflecting the differential effects of factors such as hunting, logging, and forest clearing. In general terms, species diversity, abundance, total biomass, and mean biomass all tended to decrease with increasing human disturbance. Two more specific patterns were also distinguished: decreasing abundance and biomass of game species with increasing hunting pressure and increasing abundance of nongame species with increasing forest disturbance. Intense hunting pressure alone may have deleterious short‐term effects on abundance, but not necessarily on diversity, whereas prolonged hunting pressure, combined with forest clearing, results in marked distortions in the mammalian community. Overall, the study emphasizes the relative paucity of the mammalian fauna of eastern Amazonia, in terms of both species diversity and abundance, and its vulnerability to the ongoing process of human colonization in the region.

Dual-energy computerized tomography in compacted soil - D. Braz; R. T. Lopes; L. M. G. Motta (Geotechnical and Geological Engineering, 2000)

Identification of microsatellite loci in olive ( Olea europaea ) and their characterization in Italian and Iberian olive trees - K. M. Sefc; M. S. Lopes; D. Mendonça; M. Rodrigues Dos Santos; M. Laimer Da Câmara Machado; A. Da Câmara Machado (Molecular Ecology, 2000)

Experimental Chagas disease: Phagocytosis of apoptotic lymphocytes deactivates macrophages and fuels parasite growth - M. F. Lopes; G. A. DosReis (Apoptosis, 2000)

Sex chromosome evolution in fish. II. Second occurrence of an X1X2Y sex chromosome system in Gymnotiformes - Lurdes F. de Almeida-Toledo; M. F. Z. Daniel-Silva; C. E. Lopes; Silvio de A. Toledo-Filho (Chromosome Research, 2000)

The Marine Mussel Perna perna (Mollusca, Bivalvia, Mytilidae) as an Indicator of Contamination by Heavy Metals in the Ubatuba Bay, SÃo Paulo, Brazil - W. E. P. Avelar; F. L. M. Mantelatto; A. C. Tomazelli; D. M. L. Silva; T. Shuhama; J. L. C. Lopes (Water, Air, & Soil Pollution, 2000)

Microsatellite variability in grapevine cultivars from different European regions and evaluation of assignment testing to assess the geographic origin of cultivars - K. M. Sefc; M. S. Lopes; F. Lefort; R. Botta; K. A. Roubelakis-Angelakis; J. Ibáñez; I. Pejić; H. W. Wagner; J. Glössl; H. Steinkellner (Theoretical and Applied Genetics, 2000)

Potential Utility of Random Amplified Polymorphic DNA (RAPD) and Restriction Endonuclease Assay (REA) as Typing Systems for Madurella mycetomatis - Maria M. Lopes; Graciete Freitas; Patrick Boiron (Current Microbiology, 2000)

Survival Time of Ceriodaphnia dubia in Acid Waters with Metal Contamination - R. Ribeiro; I. Lopes; A. M. M. Pereira; F. Gonçalves; A. M. V. M. Soares (Bulletin of Environmental Contamination and Toxicology, 2000)

Hematoxylin staining as a phenotypic index for aluminum tolerance selection in tropical maize (Zea mays L.) - G. M. A. Cançado; L. L. Loguercio; P. R. Martins; S. N. Parentoni; E. Paiva; A. Borém; M. A. Lopes (Theoretical and Applied Genetics, 1999)

Distribution patterns of epipelagic copepods off Rio de Janeiro (SE Brazil) in summer 1991/1992 and winter 1992 - Rubens M. Lopes; Frederico P. Brandini; Salvador A. Gaeta (Hydrobiologia, 1999)

The use of microsatellites for germplasm management in a Portuguese grapevine collection - M. S. Lopes; K. M. Sefc; E. Eiras Dias; H. Steinkellner; M. Laimer Câmara Machado; A. Câmara Machado (Theoretical and Applied Genetics, 1999)

Somatic embryogenesis and plant regeneration in myrtle (Myrtaceae) - Jorge M. Canhoto; Maria L. Lopes; Gil S. Cruz (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Effects of over-expression of strictosidine synthase and tryptophan decarboxylase on alkaloid production by cell cultures of Catharanthus roseus - Camilo Canel; M. Inês Lopes-Cardoso; Serap Whitmer; Leslie van der Fits; Giancarlo Pasquali; Robert van der Heijden; J. Harry C. Hoge; Robert Verpoorte (Planta, 1998)

Body composition and biochemical profile as affected by diet and renal transplantation among renal patients - M. Martin; I. M. Lopes; P. Errasti; J. A. Martínez (Journal of Physiology and Biochemistry, 1998)

Linear servo-controlled pressure generator for forced oscillation measurements - P. Lopes de Melo; M. Martins Werneck; A. Giannella-Neto (Medical & Biological Engineering & Computing, 1998)

Effects of Cadmium and Parathion Exposure on Hematology and Blood Biochemistry of Adult Male Rats - L. Guilhermino; A. M. V. M. Soares; A. P. Carvalho; M. C. Lopes (Bulletin of Environmental Contamination and Toxicology, 1998)

Agrobacterium-mediated transformation of the terpenoid indole alkaloid-producing plant species Tabernaemontana pandacaqui - M. I. Lopes Cardoso; A. H. Meijer; J. Harry C. Hoge (Plant Cell Reports, 1997)

Suspension cultured transgenic cells of Nicotiana tabacum expressing tryptophan decarboxylase and strictosidine synthase cDNAs from Catharanthus roseus produce strictosidine upon secologanin feeding - D. Hallard; R. van der Heijden; R. Verpoorte; M. I. Lopes Cardoso; G. Pasquali; J. Memelink; J. H. C. Hoge (Plant Cell Reports, 1997)

Nonlinear dynamics of epileptic seizures on basis of intracranial EEG recordings - Jan Pieter M. Pijn; Demetrios N. Velis; Marcel J. van der Heyden; Jaap DeGoede; Cees W. M. van Veelen; Fernando H. Lopes da Silva (Brain Topography, 1997)

Foraging costs of a tail ornament: Experimental evidence from two populations of barn swallows Hirundo rustica with different degrees of sexual size dimorphism - A. P. Moller; F. de Lope; J. M. López Caballero (Behavioral Ecology and Sociobiology, 1995)

Foraging costs of a tail ornament: Experimental evidence from two populations of barn swallows Hirundo rustica with different degrees of sexual size dimorphism - A. P. Mller; F. de Lope; J. M. Lpez Caballero (Behavioral Ecology and Sociobiology, 1995)

The emergence of long-lasting transients of activity in simple neural networks - A. van Ooyen; J. van Pelt; M. A. Corner; F. H. Lopes da Silva (Biological Cybernetics, 1992)

The emergence of long-lasting transients of activity in simple neural networks - A. van Ooytien; J. van Pelt; M. A. Corner; F. H. Lopes da Silva (Biological Cybernetics, 1992)